Antifungal mechanism of slightly acidic electrolyzed water against Phomopsis longanae Chi, the major pathogen causing fruit spoilage in postharvest longans - Qingqing Liu; Fanling Chen; Qin Zheng; Yifen Lin; Ruiling Zhuo; Yen-Con Hung; Hetong Lin; Yihui Chen (Food Control, 2027)

Highly sensitive lateral flow immunoassays targeting PirA and PirB toxins for early on-site diagnosis of AHPND in shrimp - Chia-Chun Hsiao; You-Shan Cai; Shin-Yu Chou; Hung-Yun Lin; Shao-Chieh Yen; Han-Jia Lin; Shih-Chung Chang (Aquaculture, 2027)

Combined membrane aeration and membrane filtration for space-efficient nitrogen control in reuse-oriented biological pretreatment - Hsin-Chieh Lin; Ting-Wei Wu; Yu-Tzu Huang; Ho Kyong Shon; Chia-Hung Hou (Desalination, 2026)

Development of an isoform-discriminating RT-qPCR assay for transcript-level profiling of human ASAH2 in colorectal cancer cell models - You Shan Ngui; Yi-Wen Huang; Shao-Chi Hung; Shih-Han Huang; Chieh-Ju Wen; Yi-An Chang; Hsing-Chen Wu; Hsiu-Chuan Chan; Mei-Lin Chan; Liang-Yin Ke; Hua-Chen Chan (Molecular Biology Reports, 2026)

Enhancement by Ce addition to La-Zr-mixed oxide supported Ni catalysts on the mid-temperature steam reforming of methane - Li-Chun Lin; Teng-Li Yu; Cheng-Yao Hung; Guan-Yu Chen; Yi-Ning Chao; Shawn D. Lin (Fuel, 2026)

Chronic exposure to chlorate at regulatory safety limits induces p21/p16-mediated neuronal senescence and Parkinsonian-like decline - Cai-Jhen Wu; Chien-Tai Hong; Jiun-Lin Horng; Hung-Shao Lai; Hao-Yu Tsai; Tsorng-Harn Fong; Chen-Yuan Hsiao; Cheng-Ying Chu; Yvonne Jing Mei Liew; Tien-Chun Yang (Environmental Pollution, 2026)

Novel D-A1-A2-π-A self-assembled monolayer in suppressing the Voc deficit of the wide-bandgap perovskite solar cells - Dong-Tai Wu; Yu Hsuan Lin; Yi-Chen Lin; Hsin Li; Yu-Chen Liang; Yu-Tong Hung; Yi-Sheng Lin; Wei-Jia Qiu; Shi-Chun Liu; Yuan Jay Chang; Chieh-Ting Lin (Chemical Engineering Journal, 2026)

SHAP-TAG: Operationalizing explainable AI for urban heat governance through attribution-severity typologies and policy triggers - Hung Lin; Chiho Ochiai (Sustainable Cities and Society, 2026)

Synergistic modulation of nickel–manganese glycerate via sequential sulfurization and oxidation for high-performance battery–supercapacitor hybrids - Tsung-Rong Kuo; Lu-Yin Lin; Tzu-Han Chou; You-Zher Yu; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen (Journal of Environmental Chemical Engineering, 2026)

Mangiferin attenuates aflatoxin B1–Induced ferroptosis by activating of Nrf2-Signaling and mitochondrial biogenesis in human ovarian granulosa cells - Chi-Wai Ruan; Hsin-Yi Tsai; Chih-Hsin Hung; Ming-Wei Lin (Food and Chemical Toxicology, 2026)

Multi-level biomarker responses in Eisenia fetida co-exposed to PE-MPs and DiBP: An ecological risk assessment based on physiological, biochemical, and molecular indicators - Yanan Zhang; Yumu Luo; Zhensi Meng; Jun Luo; Ke Li; Yuhang Lin; Minle Li; Rongren Bin; Mingming Fu; Ming Hung Wong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Scalable cancer cell-derived liposome capable of homologous tumor-homing to encapsulate near-infrared light-responsive drug delivery nanocomposites for enhanced combination therapy - Fang-Yi Hsu; Wen-Jyun Wang; Li-Ting Yang; Yi-Zi Chen; Ting-Chi Lo; Jia-Sin Chen; Wei-Lun Huang; Yen-Liang Li; Hidenobu Takahashi; Wen-Chun Hung; Chi-Wen Luo; Shu-Yi Lin; et al. (Chemical Engineering Journal, 2026)

Epitaxial high-entropy relaxor ferroelectric films for flexible piezoelectric sensors and MEMS - Yu-En Pan; Yu-Hao Tu; Li-Hui Tsao; Yu-Ju Lin; Sheng-Yao Hung; Yi-Chun Chen; Mengyao Xiao; Qibin Zeng; Huajun Liu; Chengkuo Lee; Ying-Hao Chu (Chemical Engineering Journal, 2026)

Pyridoxine and valproic acid co-exposure induces ER-mediated calcium dysregulation and cardiac toxicity in zebrafish - Wei-Hsiang Chen; Po-Yuan Chen; Wen-Yu Chung; Tein-Yu Chiu; Wei-Ling Lin; Chen-Yu Huang; Hui-Hua Chang; Chin-Wei Huang; Bing-Hung Chen; Lin Kang; Tzu-Fun Fu (Chemico-Biological Interactions, 2026)

Significant crust-thinning beneath the Ilan Plain of Taiwan for revealing westward impingement of the Okinawa Trough opening into Taiwan Orogeny - Ya-Chuan Lai; Cheng-Horng Lin; Min-Hung Shih; Yoko Tao-Lin Tu; Hsin-Chieh Pu; Wen-Yen Chang (Tectonophysics, 2026)

Uncovering an aseismic slab for showing the flipping of subduction polarity in the Taiwan area - Lin Cheng-Horng; Min-Hung Shih; Ya-Chuan Lai; Yoko Tao-Lin Tu; Hsin-Chieh Pu; Wen-Yen Chang (Journal of Asian Earth Sciences, 2026)

Corrigendum to “Susceptibility of Spodoptera frugiperda to novel insecticides and detection of known target-site mutations following invasion of Taiwan” [J. Asia-Pac. Entomol. 29(3) (2026)102584] - Hung-Ming Chao; Wen-Jer Wu; Li Lin; Hurng-Yi Wang; Ju-Chun Hsu (Journal of Asia-Pacific Entomology, 2026)

Susceptibility of Spodoptera frugiperda to novel insecticides and detection of known target-site mutations following invasion of Taiwan - Hung-Ming Chao; Wen-Jer Wu; Li Lin; Hurng-Yi Wang; Ju-Chun Hsu (Journal of Asia-Pacific Entomology, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Engineering bimetallic Cobalt–Iron glycerate Co-Catalysts on bismuth vanadate for improved charge transfer and photoelectrochemical catalytic water oxidation - Tsung-Rong Kuo; He-Jin Li; Kai-Jie Chuang; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen; Lu-Yin Lin (Fuel, 2026)

Optimization of sequential co-fermentation with Hanseniaspora opuntiae enhances aroma-active ester biosynthesis and sensory quality of rice beer - Wei-Ting Hung; Kai-Ler Ng; Yen-Tso Lai; Chang-Wei Hsieh; Chien-Hao Chen; Christoper Caesar Yudho Sutopo; Shella Permatasari Santoso; Kaemwich Jantama; Hui-Wen Lin; Kuan-Chen Cheng (Food Bioscience, 2026)

Real-world emission factors and inhalation health risks of PM-bound metals from workboats using ultra-low sulfur marine fuel - Po-Yen Chien; Chia-Hsiang Lai; Chia C. Wang; Dhruv Vishal Patel; Ajay Pillarisetti; Wu-Xing Chen; Chia-Hung Chen; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Dong-Ni Wu; I-Hsuan Wu; et al. (Environmental Pollution, 2026)

Exploring spatial and temporal variations in methane emissions from rice paddies - Shang-Hung Pao; Huey-Lin Lee; Chiao-Wen Lin; Wei-Jen Lin; Hsing-Juh Lin (European Journal of Agronomy, 2026)

Integrated multi-matrix bile acid metabolic metrics (BAMMs): A methodological framework for functional metabolic phenotyping in human subjects - Cheng-Hung Yang; Hsiang-Yu Tang; Chun-Ming Fan; Jui-Fen Lin; Mei-Ling Cheng (Analytica Chimica Acta, 2026)

Phylogeny and taxonomic revisions of Piper (Piperaceae) in Taiwan - Po-Hao Chen; Chia-Hao Chang; Kuan-Ning Kung; Hung‑Chih Lin; An-Ching Chung; Chia-Ying Ou; Shih-Hui Liu (Journal of Plant Research, 2026)
Taiwan, located at the northernmost extent of Huxley’s Line, marks the furthest point along this biogeographic boundary where exchanges of flora and fauna occur. The genus Piper , a globally distributed and taxonomically complex group of both economic and evolutionary importance, has a convoluted taxonomic history in this transitional zone that requires comprehensive study. Here, we integrate morphological, molecular, and distributional data to revise the taxonomy of Taiwanese Piper , resolve their evolutionary relationships, and infer their biogeographic history. Our revision recognizes 11 species in Taiwan, including seven native taxa, of which three are endemic. The present analysis establishes the first comprehensive phylogenetic framework for Taiwanese Piper and reveals that native species arose from lineages on both sides of Wallace’s Line. Collectively, these findings provide the first evidence of bidirectional expansion within a genus in Taiwan and position Piper as an exemplary system for examining phylogeographic dynamics in transitional biogeographic zones.

Late Holocene human-environment interactions on a small island of the Taiwan Strait - Ranjan Kumar Mohanty; Abdur Rahman; Yi-Chen Ho; Yu-Chen Lu; Cheng-Tao Lin; Hung-Chun Chao; Ling-Ho Chung; Chin-Yung Chao; Liang-Chi Wang (Quaternary International, 2026)

Differential thermal sensitivity among shallow-water octocorals and its association with holobiont composition - Hsien-Yu Cheng; Yu-Chien Wang; Yan-Zhen Meng; Chien-Yi Wu; An-Chi Liu; Yen-Chih Lin; Jui-Hsun Hung; Shan-Hua Yang (Marine Environmental Research, 2026)

Poly(lactic-co-glycolic acid) (PLGA)-based vaccine delivery systems for fish: physicochemical properties, immunological mechanisms, and applications - Shu-Chun Chuang; Yi-Chen Lin; Ya-Shuan Chou; Shang-Pin Liu; Shao-Wen Hung; Ti-Chun Chang; Chung-Hwan Chen; Chung-Da Yang (Fish & Shellfish Immunology, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

Enhanced label-free SERS detection of uremic toxins in clinical spent dialysate - Han Lee; Jiunn-Der Liao; Yi-Shan Guo; Chung-Yu Wang; Kuan-Hung Liu; Szu-Hsueh Lai; Bo-Shen Lin (Analytica Chimica Acta, 2026)

AlgaePath 2.0: An updated database for revealing algal coding and non-coding gene interactions in metabolic pathways - Kuan-Chieh Tseng; Wen-Lin Wang; Yen-Lin Shen; Hung-Teng Wang; Ching-Ya Yuan; Chien-Wen Yang; Ching-Nen Nathan Chen; Wen-Chi Chang (Algal Research, 2026)

Microbial-derived metabolites coordinate growth regulation and stress tolerance in Phalaenopsis orchids - Nur Izzatul Maulidah; I-Hung Lin; Yun-Teng Yen; Ting-Yu Liou; Huey-wen Chuang (Journal of Plant Physiology, 2026)

Green synthesized Cu2O/TiO2 nanotube heterojunction for pharmaceutical mineralization and simultaneous hydrogen evolution: mechanistic insight and toxicity assessment - Fang-Yu Liang; Dong-Ni Wu; Wan-Chun Lin; Yi-Ching Lin; Chia-En Tsai; Chia-Hua Lin; Wu-Xing Chen; Chia-Hung Chen; Yen-Ping Peng (Journal of Environmental Management, 2026)

Pollutant-specific pathways linking gaseous air pollution to adolescent depressive symptoms: Direct and sleep-mediated effects in a population-based retrospective cohort study - Chun-Ji Lin; Po-Ya Chang; Yu-Ling Li; Chih-Da Wu; Chao-Ying Tu; Chih-Yi Wu; Szu-Ying Chen; Hung-Yi Chiou (Environmental Research, 2026)

Evaluating UERT for submarine power cable surveys: Characterizing installation-induced sediment densification in shallow coastal waters - Chun-Hung Lin; Yi-Hao Chen (Engineering Geology, 2026)

Mechanically robust and electrolyte-stable 2D MOF-based nanocomposite membrane with rich low-resistance highways for high-performance osmotic energy harvesting - Chia-An Lung; Guang Hui Teoh; Wen-Hung Lin; Kalon Gopinadhan; Soorathep Kheawhom; Li-Hsien Yeh (Chemical Engineering Journal, 2026)

Correction to: Isolation of Proteus sp. Closely Related to P. Vulgaris (Vulgaris/hauseri Complex) from Ornamental Koi (Cyprinus rubrofuscus) and its Pathogenicity - Crystal Jia Jing Lim; Hung Hui Chung; Melinda Mei Lin Lau; Cindy Jia Yung Kho; Leonard Whye Kit Lim; Kristene Ling Yong; Pei Xuan Hew (Current Microbiology, 2026)

Heteronemin suppresses chemoresistant oral squamous cell carcinoma cells through ROS-mediated apoptosis and cuproptosis-associated mitochondrial stress - Chiung-Wei Huang; Fan-Li Lin; Chun-Feng Chang; Hsiao-Hsuan Huang; Wan-Ju Wu; Hui-Min Chang; Mei-Ying Lin; Jue-Liang Hsu; Shih-Ya Hung; Chien Hsing Lee (Apoptosis, 2026)

Efficient Underwater Image Super-Resolution via Learnable Color Conversion and Dual-Branch Mamba Network - Yu-Yang Lin; Wan-Jen Huang; Chia-Hung Yeh; Yi-Shiuan Yang; Chua-Chin Wang (Journal of Marine Science and Engineering, 2026)
Underwater image super-resolution plays an important role in marine exploration, as it aims to recover clearer and higher-resolution images from degraded low-resolution observations. However, in underwater environments, this task is particularly challenging due to non-uniform spectral attenuation and particle scattering. Underwater, red light fades quickly, leading to color distortion and loss of details. To address this while keeping the model lightweight, we propose a dynamic color-space network for single-image super-resolution. Traditional methods use fixed color conversion and cannot handle non-uniform attenuation well. We instead use a learnable module to adaptively obtain luminance (Y) and chrominance (CbCr) representations. Building upon this representation, we employ a highly efficient dual-branch architecture where the Y-channel features are processed using light Mamba blocks to capture spatial dependencies with linear complexity, while the CbCr-channel features are restored by a lightweight convolutional neural network. Finally, a lightweight residual model utilizing depth-wise separable convolutions (DSC), deformable convolutions, and pixel attention mechanisms is introduced to refine the features and suppress artifacts. Experimental results demonstrate that while achieving competitive restoration quality, the proposed method drastically reduces computational complexity and parameter count compared to other large-scale models. This balance between visual quality and computational efficiency makes the proposed method well-suited for real-time deployment on resource-constrained autonomous underwater vehicles (AUVs).

Reconceptualizing chorioamnionitis as an immune-mediated inflammatory disorder at the maternal–fetal interface - Tzu-Ming Wang; Chung-Min Shen; Shih-Chang Lin; Wu-Shiun Hsieh; Yi-Li Hung; Jiun-Wen Guo (Inflammation Research, 2026)

Ganoderma formosanum— advances in biotechnological fermentation, bioactive metabolites, and health-promoting applications: a critical review (2017–2025) - Kitipong Assatarakul; Khanom Simarani; Chen-Che Hsieh; Shin-Ping Lin; Isaya Kijpatanasilp; Yueh-Hao Ronny Hung; Saeid Jafari; Kuan-Chen Cheng (Critical Reviews in Food Science and Nutrition, 2026)

Valorization of baghouse dust from lime industry through carbonation processes - Hung-Chieh Liang; Cheng-You Lin; Hsing-Jung Ho; Cheng-Han Lee (Waste Management, 2026)

A compact, low-impact seismic source reshapes monitoring of offshore CO2 storage - Takeshi Tsuji; Tarek Imam; Ahmad Ahmad; Kazutoshi Sakamoto; Arata Kioka; Tetsuro Tsuru; Fernando Hutapea; Masaharu Ueki; Hao Kuo-Chen; Zhuo-Kang Guan; Chun-Hung Lin (International Journal of Greenhouse Gas Control, 2026)

Short-term exposure to nitrogen dioxide and risk of stroke-related re-admission: An analysis of the Taiwan National Health Insurance Research Database - Chen-Ting Yang; Yu-hsiang Lin; Hung-Lin Lin; Der-Cherng Chen; Chun-Chung Chen; Der-Yang Cho (Atmospheric Environment, 2026)

Integrated assessment of boiler air pollution control policy: Impacts on emissions, air quality, and public health in Taiwan - Dennis Kao; Hung-Jui Lin; I-Chun Tsai; I-Yun Lisa Hsieh (Atmospheric Pollution Research, 2026)

Purification, Identification, and Functional Validation of Anti-Inflammatory Peptides from Protein Hydrolysates of Asian Seabass, Lates Calcarifer by-Product - Hui-Chen Lin; Chung-Chih Tseng; Jia-Yu Lu; Hua-Yi Liang; Chun-Hung Liu (Marine Biotechnology, 2026)

Coupling fine-scale molecular approaches with hydrodynamic modeling to inform conservation management of the endangered and endemic fiddler crab Xeruca formosensis - Kun-Ching Hung; Hui-Chen Lin (Journal of Environmental Management, 2026)

Development of appropriate conditions for determination of multiple nitrated polycyclic aromatic hydrocarbons (nitro-PAHs) and PAH 4 in roasted chicken drumsticks and assessment of their consumption risk - Yin-Hung Lai; Tuzz-Ying Song; Yi-Hsieng Samuel Wu; Chao-Chun Liao; Jau-Tien Lin; Deng-Jye Yang (Food Research International, 2026)

Environmental metrics and trade-off for aeration-driven nitrogen removal in a pilot-scale hybrid membrane-aerated biofilm reactor treating low-C/N municipal wastewater - Hsin-Chieh Lin; Ting-Wei Wu; Mengshan Lee; Ho Kyong Shon; Chia-Hung Hou (Desalination, 2026)

Single-cell transcriptomics reveal PRRC1 as a malignant cell enriched driver of DNA repair and therapy resistance in glioblastoma - Sachin Kumar; Ming-Cheng Tsai; Dahlak Daniel Solomon; Juan Lorell Ngadio; Do Thi Minh Xuan; Ching-Chung Ko; Hung-Yun Lin; Meng-Chi Yen; I-Jeng Yeh; Yung-Kuo Lee; Hui-Ru Lin; Jian-Ying Chuang; et al. (DNA Repair, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Laminar nanofiltration composite membranes based on two-dimensional aluminum-tetrakis(4-carboxyphenyl)porphyrin (Al-TCPP) nanosheets for efficient dye/salt wastewater treatment - Shao-Ju Lu; Chun-Po Hu; Chien-Chieh Hu; Chia-Her Lin; Wei-Song Hung; Kueir-Rarn Lee; Juin-Yih Lai (Journal of Environmental Chemical Engineering, 2026)

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Validation of a numerical model for seismic behavior of wind turbine nacelle components using experimental data - Wei-Hung Hsu; Bai-Yi Huang; Juin-Fu Chai; Fan-Ru Lin (Engineering Structures, 2026)

Thiourea-based networks with nanocarbon fillers for antistatic, self-healing, and plasma-resistant elastomers - Tse-Yu Lo; Shu-Fan Li; Chia-Wei Chang; Huan-Wei Lin; Heng-Hsuan Su; Kuan-Hung Liu; Po-Chia Huang; Jiun-Tai Chen (Chemical Engineering Journal, 2026)

Effect of somatosensory games on arterial stiffness and antioxidant status in postmenopausal women - Yi-Hung Liao; Kunanya Masodsai; Yu-Chi Kuo; Hsiao-Kuan Wu; Yi-Yuan Lin (European Journal of Applied Physiology, 2026)

Zebrafish Model Reveals Early Electrocardiographic and Molecular Signatures of Doxorubicin-Induced Cardiotoxicity - Zih-Yin Lai; Chi-Ying Lee; Yu-Ching Chiu; Chia-Hung Lin; Chung-Chi Yang; Chia-Chia Ho; Lawrence Yu-Min Liu; Yung-Jen Chuang (Cardiovascular Toxicology, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Determination of local site characteristics in the Hanoi urban area using microtremor data - Tien-Hung Nguyen; Hong-Phuong Nguyen; Le-Minh Nguyen; Che-Min Lin; Van-Duong Nguyen; Van-Bang Phung; The-Truyen Pham; An-Nguyen Tran; Quang-Khoi Le (Acta Geophysica, 2026)

Generative data augmentation for AIoT-based smart pig farming: The PigTalk 2.0 system - Whai-En Chen; Shih-Che Lin; Hsin-Hung Cho (Computers and Electronics in Agriculture, 2026)

Insertion of the PgRE1 retrotransposon into the promoter region of PgACS1, a system-2 ACC synthase gene, leads to variation in ripening ethylene production and the storability of different guava varieties - Margo Sulistio; You-Siang Liao; Hsin-Hung Yeh; Ching-Ping Lin; Hung-Yeh Hsieh; Chun-Ta Wu (Postharvest Biology and Technology, 2026)

Vulnerability and pathways of global renewable energy transition under climate exposure - Yang Chen; Wen Yi; Jingke Hong; Hung-lin Chi; Jin Shao (Environmental Impact Assessment Review, 2026)

Triarylamine-based epoxy thermosets featuring bright polyelectrochromic energy-storage and energy-saving behaviors - Yu-Jen Shao; Peng-Yi Lin; Hung-Lin Ho; Hsuan-Hsi Pai; William Sun; Yu-Jie Wang; Cha-Wen Chang; Guey-Sheng Liou (Chemical Engineering Journal, 2026)

Synergistic co-preintercalation of nickel and aluminum ions into vanadium oxide hydrate as positive electrode material in ultrahigh-rate and high-capacity aqueous zinc-ion batteries - Hung-Lin Chen; Tsung-Yi Chen; En-Hao Li; Yen-Lin Chen; Wen-Hsuan Lu; Hsu-Chen Cheng; Shu-Yu Chen; Jue-Hua Pan; Hsiang-Jung Chen; Syuan-Cen Lin; Ruey-An Doong; Sanna Gull; et al. (Chemical Engineering Journal, 2026)

Cellular vesicle–electrically conducting polymer integrating with microalgae attenuate retinal inflammation associated with IL-6, immunomodulation, and pro-inflammatory cytokines in diabetes-related retinal disease - Andrew E.-Y. Chuang; Yo-Lin Chen; Chia-Hung Liu; Hieu Trung Nguyen; Tsung-Jen Wang; I-Chan Lin (Chemical Engineering Journal, 2026)

Impact of PM2.5 exposure on gut microbiota abundance and composition in chronic disease patients - Yi-Hsueh Liu; Po Peng; Wei-Chun Hung; Ping-Hsun Wu; Chun-Chi Lu; Yi-Hsiung Lin; Chih-Da Wu; Chao-Hung Kuo; Szu-Chia Chen (Air Quality, Atmosphere & Health, 2026)

Phylogeographic Pattern and Genetic Structure of the Cyprinid Fish Microphysogobio kachekensis (Oshima 1926) in Mainland China and Hainan Island Based on Mitochondrial and Nuclear DNA - Jin-Quan Yang; Jiabo Chen; Junjie Wang; Tian-Qi Zhou; Yuh-Wen Chiu; Hung-Du Lin; Wen-Sheng Ou (Fishes, 2026)
South China’s freshwater biodiversity has been shaped by Quaternary climatic oscillations and persistent geological barriers. We investigated the phylogeography and conservation implications of the primary freshwater fish Microphysogobio kachekensis across mainland China and Hainan Island using mitochondrial (cyt b and control region) and nuclear (RAG2 and rpS7-1) markers from 200 individuals. Mitochondrial analyses recovered two major lineages and multiple sublineages largely structured by drainage basins, whereas nuclear data resolved four geographically concordant lineages. Population differentiation was strong (high FST), and SAMOVA/AMOVA supported major barriers restricting gene flow, including the Qiongzhou Strait, Gulf of Tonkin, Yunkai Mountains, and Nanling Mountains. Ancestral-area reconstruction inferred the Pearl River region as the most likely source area, followed by dispersal to northern Hainan and subsequent expansion to southern Hainan and the Red River, with additional northward expansion to the Zhejiang–Fujian region. Despite high haplotype diversity, within-population nucleotide diversity was low, consistent with long-term river isolation and complex demographic history. We propose six ESUs and four MUs for evolutionarily informed conservation and to guide stock enhancement in southern China.

Rare and underexplored lobane- and prenyleudesmane-type diterpenes primarily from corals with additional plant sources—Biosynthesis and pharmacological perspectives - Lo-Yun Chen; Bo-Rong Peng; You-Ying Chen; Huong-Giang Le; Ngoc-Thac Pham; Yi-Ying Lin; Hung-Yi Chen; Pei-Jhen Hsieh; Mohamed El-Shazly; Kuei-Hung Lai (Phytochemistry, 2026)

Peroxymonosulfate activation by metal-free cocoa pod husk biochar for tetracycline degradation: Efficiency and embryotoxicity in zebrafish (Danio rerio) - Chang-Mao Hung; Chia-Hao Lin; Hsuan-Yi Hsu; Tzu-Chen Lo; Yi-Chen Wang; Tsai-Hsuan Ho (Environmental Research, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Effects of dietary selenium supplementation on physiological parameters, tissue fatty acid composition, and fatty acid-metabolism relative gene expression of grouper (Epinephelus coioides) fed high plant protein diets - Yen-Chun Lee; Ying-Chieh Lin; Yu-Sheng Huang; Yu-Hung Lin (Fish Physiology and Biochemistry, 2026)

A review on integrated isotopic and receptor model approaches for urban REE source appointment - Muhammad Ubaid Ali; Muhammad Adnan; Xiao Yan Lin; Sajid Ali; Zhuanxi Luo; Yu Yan; Gongren Hu; Ruilian Yu; Ming Hung Wong (Environmental Geochemistry and Health, 2026)

Isolation of Proteus sp. Closely Related to P. Vulgaris (Vulgaris/hauseri Complex) from Ornamental Koi (Cyprinus rubrofuscus) and its Pathogenicity - Crystal Jia Jing Lim; Hung Hui Chung; Melinda Mei Lin Lau; Cindy Jia Yung Kho; Leonard Whye Kit Lim; Kristene Ling Yong; Pei Xuan Hew (Current Microbiology, 2026)

Aqueous LC-MS/MS quantification of α-/β-nicotinamide mononucleotide in dietary supplements using a pentabromophenyl column - Chng Sze Hoei; Nian-Hua Wu; Chao-Ming Tsen; Ping-Wei Sun; Han-Wei Chang; Shin-Yuan Wang; Hung-Yu Lin (Analytica Chimica Acta, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Spermidine carbon quantum dots as an alternative antimicrobial agent for hatcheries rearing Pacific white shrimp (Litopenaeus vannamei) - Hung-Yun Lin; Han-Tso Lin; Yun-Ru Chiang; Ya-Yun Lu; James Pan; Hou-Ju Lin; Wan-Ching Kuo; Han-Jia Lin; Han-You Lin (Aquaculture, 2026)

Acidic electrolyzed-oxidizing water alleviates the storability decline in Phomopsis longanae Chi-infected longans by modulating the metabolisms of disease-resistance substances and cell wall polysaccharides - Shujuan Feng; Shaojie Zheng; Qin Lin; Mengshi Lin; Ruiling Zhuo; Yifen Lin; Yen-Con Hung; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2026)

Electrochemically activated polypyrrole for full-polymer electrochemical deionization: Unraveling potential-gated ion exchange behavior and its application to oxyanion removal - Hung-Yi Huang; Yi-Heng Tu; Yi-An Chen; Cheng-Wei Lin; Yu-Hung Cheng; Hsing-Mei Chou; Yu-Hsiang Yang; Yun Ku; Zhiyin Yang; Sophia Uemura; Hsin-Lung Chen; Richard B. Kaner; et al. (Chemical Engineering Journal, 2026)

Optimizing Light Quality to Enhance Morphological and Physiological Responses in Japonica and Indica Rice Seedlings - Yun-Wei Kuo; Kuan-Hung Lin; Yi-Zhang Chen; Yue-Cing Su; Hsin-Hung Lin (Journal of Plant Growth Regulation, 2026)

Harnessing pyroptosis to restrain melanoma through aripiprazole - Yu-Teng Chang; I-Hsiang Lin; Jeng-Jer Shieh; Tsuo-Hung Lan; Jia-Ning Syu; Shiau-Shian Huang; Po-Hsun Hou (Apoptosis, 2026)

Pilot study on integrating multidisciplinary technologies to implement an autonomous and smart harvester for asparagus - Joe-Air Jiang; Jen-Cheng Wang; Hung-Jen Lin; Cheng-Ying Chou; Chia-Chun Chien; Wei-Hao Huang; An-Chi Liu; Cheng-Chun Lee; Ming-Chi Guo; Jui-Chu Peng (Computers and Electronics in Agriculture, 2025)

Dual activation of AhR and Nrf2 pathways by the natural stilbenoid tapinarof protects against particulate matter-induced skin barrier dysfunction - Chia-Hsuan Lin; Horng-Huey Ko; Jin-Ye Wu; Hsun-Shuo Chang; Chia-Hung Yen; Chien-Chih Chiu; Yih-Fung Chen (Toxicology and Applied Pharmacology, 2025)

Involvements of respiratory, ROS and disease-resistance substance metabolisms in AEOW-enhanced the storability of navel oranges - Shujuan Feng; Longfeng Chen; Ziyao Lin; Mengshi Lin; Yen-Con Hung; Yihui Chen; Hetong Lin (Postharvest Biology and Technology, 2025)

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Significant wave height prediction at multiple sites using sequence decomposition and dynamic spatiotemporal graph neural networks - Chiwang Lin; Yongfeng Xie; Chia-Hung Wang (Ocean Engineering, 2025)

Outdoor-like running indoors: an enhanced adaptive treadmill with real-time physiological monitoring - Pei-Chun Hung; Yu-Chen Liu; Chun-Liang Lin; Wu-Chung Su; Chian-Yu Lu (Next Research, 2025)

Predictions about the hourly effluents in the real anaerobic-oxic wastewater treatment process made by the optimized bidirectional long short-term memory network - Yu-Hao Lin; Hung-Hsiao Hsu; Ping-Yu Liu (Journal of Water Process Engineering, 2025)

Tailoring nickel glycerate electrodes through precursor chemistry and sulfurization for enhanced battery-supercapacitor hybrid performance - Tsung-Rong Kuo; Yun-Hsi Wang; Bo-Yang Chuang; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen; Lu-Yin Lin (Journal of Environmental Chemical Engineering, 2025)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

Sustainable energy generation through engineered copper molybdate: a ternary metal oxide catalyst for efficient oxygen evolution in alkaline environments - Hung-Chang Cheng; Dhanapal Vasu; Hsin-Yu Lin; Zhen-Yuan Lan; Leggins Abraham; Tetsu Yonezawa; Te-Wei Chiu (Fuel, 2025)

Biocontrol potential and cryopreservation of marine ciliates for sustainable management of bacterial pathogens in aquaculture - Xin-Long Liu; Sin-Wei Lin; Wei-Yu Yeh; Hung-Yun Lin; Han-Jia Lin (Fish & Shellfish Immunology, 2025)

Establishment of a cobia (Rachycentron canadum) gill cell line: a valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

White spot syndrome virus facilitates and relies on shrimp de novo nucleotide synthesis to support viral pathogenesis - Cong-Yan Chen; Der-Yen Lee; Shih-Shun Lin; Chun-Hung Liu; Saengchan Senapin; Pakkakul Sangsuriya; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Near real-time subsidence monitoring and AI forecasting with multi-depth extensometers - Wei-Chia Hung; Cheinway Hwang; Luigi Tosi; Guan-Zhong Lin; Shao-Hung Lin; Yi-An Chen (Engineering Geology, 2025)

Influence of Human Activity on Wet Deposition and Nitrogen Species in Coastal and Marine Environments - Hung-Yu Chen; Jia-Han Lin; FuJung Tsai (Journal of Marine Science and Engineering, 2025)
In this study, 101 and 102 rainwater samples were collected from April 2020 to February 2024 in a coastal and marine area, respectively. The results show that the Cl/Na ratios in both study areas were lower than the seawater value (1.17), suggesting chloride depletion. The chloride depletion rates in both areas decreased after the COVID-19 lockdown period. The molar ratio of NH4+ to non-sea-salt sulfate (nss-SO42−) was 1.54, with a mixture of (NH4)2SO4 and NH4HSO4 in the coastal area, and 0.83, with NH4HSO4 as the main form, in the marine area. A decreasing trend attributed to high O3 and relative humidity (RH) levels occurred in 2022. Among the dissolved organic nitrogen (DON) species, DON accounted for 24% and 32% of the total dissolved nitrogen (TDN) in the coastal and marine areas, respectively, indicating a greater relative contribution under lower anthropogenic influence. On the basis of the correlation between the species and source analysis results, NO3− mainly originated from fossil fuel combustion, NH4+ originated from agricultural emissions and secondary aerosols, and DON originated from secondary aerosols via combustion processes and natural emissions. In terms of the flux, due to lockdown activities, the Dissolved Inorganic Nitrogen (DIN) flux decreased significantly from 40.6 to 19.3 mmol m−2 yr−1 in the coastal area and from 27.7 to 15.1 mmol m−2 yr−1 in the marine area. Additionally, a slight decrease occurred in the DON flux, from 21.6 to 19.3 mmol m−2 yr−1 and from 27.7 to 15.1 mmol m−2 yr−1, respectively. Regarding new production, based on nitrogen input, the level in the coastal area decreased from 5.83 to 2.10 g C m−2 yr−1, and that in the marine area decreased from 3.92 to 1.55 g C m−2 yr−1, indicating a significant reduction during the COVID-19 lockdown.

Real-world emissions and total output from fishing vessels in Taiwan - Po-Yen Chien; Chia-Hsiang Lai; Wu-Xing Chen; Chia-Hung Chen; Chia C. Wang; Amila Kasun Abeysinghe; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Yu-Lun Tseng; Pei-Shih Chen; Yen-Ping Peng (Transportation Research Part D: Transport and Environment, 2025)

Geotechnical reconnaissance of Hualien Port after the 2024 ML 7.2 hualien earthquake - Hsuan-Chih Yang; Chun-Jia Huang; Yung-Yen Ko; Kuan-Yu Chen; Chi-Chin Tsai; Chun-Hung Lin; Yu Wei Hwang; Min-Chien Chu; Yu-Syuan Jhuo; Yu-Ting Hsueh; Shodai Okano; LeeYi Wang; et al. (Soil Dynamics and Earthquake Engineering, 2025)

Effective peroxymonosulfate activation over cobalt oxide (CoO)/nitrogen-doped graphene aerogel for rhodamine b degradation - Xian-Lun Liao; Dhayanantha Prabu Jaihindh; Tzu-Ting Chang; Yi-Feng Lin; Wei-Hung Chiang; Yu-Chun Wang (Journal of Water Process Engineering, 2025)

Characterization of neutral fluids in the volcanic geothermal system under the Tatun Volcano Group, Taiwan - Yi-Chia Lu; Chyi Wang; Sheng-Rong Song; Pei-Ling Wang; Ting-Jui Song; Sachihiro Taguchi; Tsung-Ren Peng; Li-Hung Lin; Jian-Cheng Lee; Hong-Chun Li (Journal of Geochemical Exploration, 2025)

Machine learning and GC–MS revealing the characteristic flavour compounds of Cheddar cheese origin-independent at different ripening periods - Xinyue Hao; Liang Liu; Olayemi Eyituoyo Dudu; Baochao Hou; Weilian Hung; Jian He; Baolei Li; Kai Lin; Huaxi Yi; Lanwei Zhang; Pimin Gong (Food Research International, 2025)

Exogenous supplementation of key membrane lipid precursors enhances freeze-drying resistance in Lacticaseibacillus paracasei K56 by modulating membrane composition - Fengzhi Qiao; Xia Ma; Ting Sun; Baolei Li; Shaolei Wang; Shichao Xuan; Pimin Gong; Weilian Hung; Lanwei Zhang; Kai Lin (Food Chemistry, 2025)

Spatiotemporal variations and risks assessment of PAH-bound suspended particles across different Asian countries: Insights from multi-city sampling and source apportionment - Kai Hsien Chi; Yen-Shun Hsu; Sheng-Lun Lin; Charles C.-K Chou; Somporn Chantara; Sereeter Lodoisamba; Thi Tuyet-Hanh Tran; Delgerzul Lodoisamba; Yuan Cheng Hsu; Chih-Da Wu; Tuan Hung Ngo; Shih Yu Pan (Environmental Research, 2025)

Seismic behavior of innovative precast hybrid steel-concrete beam-column connections - Chien-Chung Chen; Hung-Jen Lee; Yi-Yao Zhao; Yin-Nan Huang; Chiu-Huang Lin; Hsiao-Wei Chan (Engineering Structures, 2025)

An in vivo NanoBiT-based pseudoviral biosensor for real-time monitoring of SARS-CoV-2 spike/hACE2 interactions and therapeutic screening - Cheng-Han Lin; Meng-Wei Lin; Xin-Rui Yang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chin-Hung Tsai; Chih-Sheng Lin (Analytica Chimica Acta, 2025)

Effects of l-carnitine supplementation in diet on growth, lipid metabolism, and carnitine biosynthesis in juvenile giant grouper (Epinephelus lanceolatus) fed high plant protein diets - Yu-Hung Lin; Yen-Chun Lee; Chih-Chieh Yeh (Aquaculture, 2025)

Damage-based seismic performance design of reinforced concrete bridges using capacity-based inelastic displacement dual spectra - P.H. Wang; T.K. Lin; P.H. Huang; R.T. Wu; H.H. Hung (Soil Dynamics and Earthquake Engineering, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Phytochemical analysis and quality control study of Dendrobium fimbriatum Hook. Flowers - Anham Abbasi; Yuan-Shiun Chang; Wu-Chang Chuang; Hung-Rong Yen; Michael Heinrich; Chia-Lin Lee (Phytochemistry Letters, 2025)

Fabrication of superwetting gelatin/phytic acid/cellulose composites with antibacterial characteristics for separating complex contaminants from wastewater - Guyita Berako Belachew; Chien-Chieh Hu; Chih-Feng Wang; Mei-Yi Liao; Wei-Song Hung; Ching-Hsuan Lin; Shiao-Wei Kuo; Juin-Yih Lai (Journal of Water Process Engineering, 2025)

Perhydroxylated benzoquinoid covalent triazine framework for ultra-high-density lithium-ion storage - Nhu T.H. Luu; Rajeshkumar Anbazhagan; Alexander S. Ivanov; Sung-En Lin; Chia-Hsin Chang; Chen-Yu Hung; Ilja Popovs; Jui-Chin Lee; Teng-Hao Chen; Watchareeya Kaveevivitchai (Chemical Engineering Journal, 2025)

Photoresponsive azobenzene-grafted thermoplastic elastomers with controlled hard segment ratios for fast-rewritable and tunable surface relief gratings - Ming-Chieh Lin; Wen-Kai Cheng; Mohamed Gamal Mohamed; Wei-Hung Su; Shiao-Wei Kuo (Chemical Engineering Journal, 2025)

Mechanistic insights into capacitive ion exchange for selective divalent ion removal using activated carbon electrodes - Ming-Han Tsai; Shu-Ju Chao; David Chiuni Wang; I-Hsuan Lin; Li-Ching Chung; Po-I Liu; Lap-Cuong Hua; Hung-Yi Huang; Chi-Chang Hu (Chemical Engineering Journal, 2025)

Seasonal growth and biomass production of cold-tolerant Napier Grass line L2201 - Swee-Suak Ko; Tzu-Rung Li; Jo-Chi Hung; Hsien-Chang Kuo; Min-Jeng Li; Jeng-Bin Lin; Ping-Han Chung; Lin-Hsiang Lee; Yueh-Hua Lin; Hong-Ping Lin; Charles C.-K Chou; Kuo-Chen Yeh (Biomass and Bioenergy, 2025)

Canagliflozin-driven cellular re-differentiation and migration inhibition in vascular smooth muscle cells via PTEN upregulation - Ming-Jer Hsieh; Dong-Yi Chen; Cheng-Hung Lee; Yu-Cih Liao; Miao‐Sui Lin; Jong-Hwei S. Pang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Development of single nucleotide polymorphisms markers associated with disease resistance towards Pseudomonas koreensis in empurau (Tor tambroides) using T-Plex ARMS PCR assay - Melinda Mei Lin Lau; Hung Hui Chung; Cindy Jia Yung Kho; Han Ming Gan; Azham Zulkharnain (Aquaculture International, 2025)

Lateral Cerebellar Theta Burst Stimulation Can Modulate Default Mode Network Connectivity in Autistic Adults - Hsing-Chang Ni; Heng Chien; Chun-Hung Yeh; Michael Cheng; Wei-Cheng Lin; Hsiang-Yuan Lin (The Cerebellum, 2025)

Fate and health implications of polycyclic aromatic hydrocarbons in a sustainable food waste recycling system using housefly maggots and Nile tilapia - Chao Zheng; Zhang Cheng; Zhi-Lin Chen; Yu Bon Man; Qiao Liu; Liu-Lan Zhao; Song Yang; Ming Hung Wong (Aquaculture, 2025)

Alisertib inhibits acute myeloid leukemia cell growth by inhibiting STAT3 activation - Pang-Ting Cheng; Ho Lin; Yu-Chiao Cheng; Tzu-Hung Hsiao; Pei-Pei Jhan; Jia-Rung Tsai; Mei-Chih Chen; Tai-Lin Chen; Chieh-Lin Jerry Teng (Toxicology and Applied Pharmacology, 2025)

Integrating machine learning and metabolomics to uncover new biomarkers for predicting pesticide exposure among patients with kidney function decline - Junne-Ming Sung; Yu-Chi Hung; Wan-Ru Wang; Chiau-Jun Chu; Yen-Ping Lin; Kuan-Hung Liu; Trias Mahmudiono; Hsiu-Ling Chen (Science of The Total Environment, 2025)

Block copolymer architectures with poly(ε-caprolactone) for modulating interactions to enhance selectivity and stability of semiconducting single-walled carbon nanotube dispersions - Mei-Nung Chen; Rin Iwasaki; Mayoh Ashiya; Haoyu Zhao; Qi-An Hong; Yen-Ting Li; Kai-Lin Chen; Maina Moses Mburu; Wei-Ting Li; Xiaodan Gu; Wei-Hung Chiang; Takuya Isono; et al. (Chemical Engineering Journal, 2025)

Five novel RNA viruses of the invasive big-headed ant (Pheidole megacephala) - Charly T. Hartle; Chih-Chi Lee; Hung-Wei Hsu; Chun-Yi Lin; Kuan-Ling Liu; Joey Yin-Xin Chang; John A. Lawrence; Jia-Wei Tay; Chin-Cheng Scotty Yang (Archives of Virology, 2025)
The African big-headed ant, Pheidole megacephala , is one of the most destructive invasive ant species, posing a significant threat to native biodiversity and ecosystem function, particularly in island ecosystems. Despite recent efforts to characterize pathogens in other major invasive ants, P . megacephala has received comparatively little attention. In this study, we characterized five novel RNA viruses actively replicating in P . megacephala , which we have named Pheidole megacephala virus 1–5 (PmV1-5), and examined viral diversity and prevalence in two invasive populations in Taiwan and Hawaii. This ant possesses a unique trait of true morphological worker dimorphism (major and minor), allowing us to test whether virus prevalence differs between the major and minor worker castes. Our findings indicate that all five novel viruses were present in both populations, but viral prevalence was higher in Hawaii than in Taiwan, potentially due to differences in supercolony structure. Multiple-virus infections were common, with coinfection by PmV1 and PmV5 being the most frequent. Notably, we found no significant difference in infection patterns between major and minor workers, suggesting that virus distribution is stable within colonies and that sampling different castes does not introduce bias in pathogen detection. This study represents the first characterization of viral pathogens in P . megacephala and may contribute to the development of microbial control strategies against this globally invasive ant.

Application of Deep Learning in Underwater Image Processing - Chia-Hung Yeh; Chua-Chin Wang; Guo-Shiang Lin (Journal of Marine Science and Engineering, 2025)
The ocean covers a significant portion of the Earth’s surface and harbors abundant natural resources, meaning that underwater exploration is of significant importance [...]

Methane dynamics controlled by subsurface metabolic architecture and tidal cycling in a mangrove wetland - Tzu-Hsuan Tu; Tai-Yi Lee; Zih-Huei Yu; Chun-Hung Lu; Yueh-Ting Lin; Pei-Ling Wang (Science of The Total Environment, 2025)

Comparative transcriptomic and metabolomic analyses reveal the role of acidic electrolyzed-oxidizing water in enhancing disease resistance in Phomopsis longanae Chi-infected longans - Meiling Li; Zhongqi Fan; Xiaoze Dai; Mengshi Lin; Yifen Lin; Hui Wang; Ruiling Zhuo; Yen-Con Hung; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2025)

Real-time assessment of PM1.0-bound trace metal cancer risk through high-resolution GED-ICP-MS and integrated ELCR analysis - Li-Ti Chou; Yi-Pin Lin; Chia-Hung Yu; Jun-Fa Ye; Wen-Che Hou; Ta-Chih Hsiao (Journal of Hazardous Materials, 2025)

SYNLAC Prime probiotics alleviate Enterocytozoon hepatopenaei-induced damage in white shrimp, Penaeus vannamei by enhancing growth, immunity, and resistance to Vibrio parahaemolyticus - Ann-Chang Cheng; Hsiao-Tung Chang; Ting-Yu Lee; Jin-Seng Lin; Chun-Hung Liu (Fish & Shellfish Immunology, 2025)

Targeted TGF-βR2 Silencing in the Retrotrapezoid Nucleus Mitigates Respiratory Dysfunction and Cognitive Decline in a Mouse Model of Cerebral Amyloid Angiopathy with and without Stroke - Ahmad El Hamamy; Zahid Iqbal; Ngoc Mai Le; Arya Ranjan; YuXing Zhang; Hung Wen Lin; Chunfeng Tan; Destiny Sumani; Anthony Patrizz; Louise D. McCullough; Jun Li (Translational Stroke Research, 2025)

Protecting Migrant Labor Rights in the Distant-Water Fisheries Sector: A Comparative Analysis of the Legal Framework of Three Major Fishing Nations in Eastern Asia - Wen-Hong Liu; Po-Chih Hung; Peter Vandergeest; Azmath Jaleel; Bruno Ciceri; Chih-Cheng Lin (Reviews in Fisheries Science & Aquaculture, 2025)

Mercury flows in a cement plant adopting circular economy policies - Liang Yu Chen; Chia Chi Hsu; Chin Lung Lin; Ming Lun Lu; Hung Lin Chiang; Moo Been Chang (Waste Management, 2025)

LINE-1 DNA methylation mediates smoking-related risk in site-specific urothelial carcinoma: a Taiwan case–control study - Chien-Hung Lin; Peir-Haur Hung; Chao-Hsiang Chang; Han Chang; Mu-Chi Chung; Wen-Chi Chang; Chi-Jung Chung (Archives of Toxicology, 2025)

Geothermal gas geochemistry in Southeast Tibetan Plateau margin influenced by magma chambers and fractures - Jia-Yi Wu; Hai Gang Cao; Peng Cheng Zhao; Yu Ping Guo; Xue-Gang Chen; Xiaohu Li; Jui-Fen Tsai; Pei-Ling Wang; Li-Hung Lin (Journal of Volcanology and Geothermal Research, 2025)

Manganese oxide and urea-assisted engineering of nickel-iron compounds for high-performance battery-supercapacitor hybrid devices - Shen-Fa Dong; Hamed Cheshideh; Chutima Kongvarhodom; Muhammad Saukani; Sibidou Yougbaré; Hung-Ming Chen; Yung-Fu Wu; Lu-Yin Lin (Journal of Environmental Chemical Engineering, 2025)

Facile synthesis of trimetallic compounds based on cobalt and nickel with ammonium fluoride-based complex for energy storage applications - Tsai-Mu Cheng; Pei-Chen Kuo; Yi-Chun Lai; Pin-Yan Lee; Chutima Kongvarhodom; Muhammad Saukani; Sibidou Yougbaré; Hung-Ming Chen; Kuo-Chuan Ho; Lu-Yin Lin (Journal of Environmental Chemical Engineering, 2025)

Dynamic weather-based scheduling for achieving energy savings in factories - Kung-Yueh Camyale Chao; Yi-Ting Liu; Chia-Yi Lee; Ji-Hong Lin; Chia-Ping Cheng; Ming-Hao Lee; Hung-Chi Kuo; Tai-Jen George Chen (Energy and Buildings, 2025)

High sensitivity mercury ion detection via thermal shock and quench with molecular sieve-functionalized FETs - Guan-Cheng Zeng; Hsuan-Wei Huang; Chia-Kai Lin; Jung-Chih Chen; Sheng-Chun Hung; Guo-Chun Dong; Yu-Lin Wang (Chemical Engineering Journal, 2025)

The influence of shading facilities on outdoor thermal comfort, pedestrian walking speed, and indoor satisfaction - Zi-En Lin; Shiang-Yu Wang; Kuo-An Hung; Chiao-Jou Hsieh; Tzu-Ping Lin (International Journal of Biometeorology, 2025)

Pathotyping and molecular serotyping of clinical isolates of Glaesserella parasuis in Taiwan - Wei-Hao Lin; Chia-Hung Yen; Cheng-Yao Yang; Chuen-Fu Lin; Yung-Fu Chang; Chao-Nan Lin; Ming-Tang Chiou (Brazilian Journal of Microbiology, 2025)

Quantifying carbon emissions in cold chain transport: A real-world data-driven approach - Hung-Jui Lin; Pei-Ci Chen; Hsuan-Po Lin; I-Yun Lisa Hsieh (Transportation Research Part D: Transport and Environment, 2025)

Retraction notice to ‘Applications of engineered biochar in remediation of heavy metal(loid)s pollution from wastewater: Current perspectives toward sustainable development goals’ [Sci. Total Environ., 926 (2024) 171859] - Thien-Khanh Tran; Loan Huynh; Hoang-Lam Nguyen; Minh-Ky Nguyen; Chitsan Lin; Tuan-Dung Hoang; Nguyen Tri Q. Hung; X. Hoan Nguyen; S. Woong Chang; D. Duc Nguyen (Science of The Total Environment, 2025)

Exploring Mitonuclear Discordance: Ghost Introgression From an Ancient Extinction Lineage in the Odorrana swinhoana Complex - Chin‐Chia Shen; Ikuo Miura; Tzong‐Han Lin; Mamoru Toda; Hung Ngoc Nguyen; Hui‐Yun Tseng; Si‐Min Lin (Molecular Ecology, 2025)
Mitonuclear discordance, the incongruence between mitochondrial DNA (mtDNA) and nuclear DNA (nuDNA), is a well‐documented phenomenon with various potential explanations. One emerging hypothesis, ghost introgression, refers to the genetic contribution of an ancient, extinct or unsampled lineage and can now be tested using modern genomic data and demographic models. In this study, we investigated the evolutionary history of the Odorrana swinhoana complex (Anura: Ranidae), which includes O. swinhoana , O. utsunomiyaorum and an unidentified population with highly divergent mtDNA. While mitochondrial phylogeny suggested this population as a basal lineage, nuclear data from ddRADseq revealed it as a mixture of the most derived O. swinhoana nuclear sequences combined with ancient mtDNA. Demographic modelling further supported ghost introgression, as all models incorporating a ghost population outperformed those without it. These findings suggest that an eastward expansion of western O. swinhoana replaced an ancient Odorrana lineage, leaving only its mtDNA and fragments of its nuclear genome in the hybrid population. Our results provide one of the first documented cases of ghost introgression in amphibians and highlight its potential as a widespread evolutionary process. This study also underscores the risks of relying solely on mtDNA for phylogenetic reconstruction and species delimitation.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Microplastic contamination in the gastrointestinal tracts of larval fish assemblages from coastal waters in southwestern Taiwan - Ming-Yih Leu; Sun-Hon Lin; Te-Yu Chen; Fung-Chi Ko; Shao-Hung Peng (Regional Studies in Marine Science, 2025)

Dynamic vertical land motion driven by climate and humans in the metropolitan Taipei Basin - Pei-Chin Wu; Meng (Matt) Wei; Jyr-Ching Hu; Steven D'Hondt; Hsin Tung; Shao-Hung Lin; Christopher J. Russoniello (Remote Sensing Applications: Society and Environment, 2025)

Characterization of the effects of micro-bubble treatment on the cleanliness of intestinal sludge, physicochemical properties, and textural quality of shrimp (Litopenaeus vannamei) - Ping-Hsiu Huang; Yi-Ying Wu; Ping-Hao Huang; Chia-Min Lin; Hsiu-Ling Chen; Min-Hung Chen; Ming-Kuei Shih; Chih-Yao Hou (Food Chemistry, 2025)

Do phenolic contents relate to their in-vitro cytotoxicity against colorectal cancer cell lines from Calvatia lilacina (puffball mushroom)? - Jie-Ling Cao; Jie-He Guo; Will Leung; Ya-Ting Liu; I-Lin Tsai; Shu-Ling Huang; Yi-Sheng Wang; Yin-Hung Lai (Food Bioscience, 2025)

Impact of bacterial cell concentration on microbial-mediated cerium carbonate precipitation for efficient heavy metal removal: Insights from adsorption isotherm, kinetics, and thermodynamics - Md. Taharia; Koyeli Das; Uttara Sukul; Hung-Chun Chao; Pritam Banerjee; Gobinda Dey; Raju Kumar Sharma; Pin-Yun Lin; Tung-Che Hung; Chien-Yen Chen (Bioresource Technology, 2025)

Enhancing resilience in isolated island communities: a disaster adaptation framework using importance-performance analysis - Yuh-Mei Lin; Bih-Chuan Lin; Chun-Hung Lee (Natural Hazards, 2025)

Exogenous mitochondria added on benefits for cellular prion protein overexpression in adipose-derived mesenchymal stem cells treatment on intracranial hemorrhage rat - Kun-Chen Lin; Jui-Ning Yeh; Pei‐Hsun Sung; Tsung-Cheng Yin; John Y. Chiang; Chi-Ruei Huang; Yi-Ling Chen; Yi-Ting Wang; Kuan-Hung Chen; Hon‐Kan Yip (Journal of Molecular Histology, 2025)

Investigating the Sensitivity of NIPAM Gel Dosimetry in CyberKnife Systems Using MRI-based R2 Mapping - Yu-Hsuan Lin; Shih-Wei Huang; Hung-Yi Chen; Hao-Ting Lan; Feng-Yi Su; Shin-Lei Peng; Chun-Hsu Yao (Journal of Medical and Biological Engineering, 2025)
Purpose The CyberKnife delivers precise radiation with sharp dose gradients challenging to measure. N-isopropylacrylamide (NIPAM) gel phantom can capture 3D dose distributions effectively. This study investigates the feasibility of using NIPAM gel dosimetry combined with magnetic resonance imaging (MRI)-based transverse relaxation rate (R2) mapping to verify dose distributions delivered by the CyberKnife system. Methods A total of 24 gel samples were divided into 8 dose groups (0, 3, 6, 9, 12, 15, 18, and 21 Gy), with three samples per dose group for repeat measurements. The NIPAM polymer gels were irradiated by a CyberKnife ® M6 FIM system with a 6 MV x-ray beam. MR images of the NIPAM gel phantom were made 24 h after irradiation using the 3T MRI scanner. The R2 maps corresponding to dose distribution were analyzed using Matlab software. Results Our results demonstrate that R2 values increase with rising irradiation doses, confirming dose-dependent sensitivity. The dose-response curve exhibits a slope of 0.1688 Gy⁻¹ s⁻¹, reflecting the gel dosimeter’s sensitivity, with a strong correlation (R² = 0.85, p = 0.001). Additionally, R2 values vary with depth, peaking at the 30 mm dose center point (D center ) and then gradually decreasing, indicating maximum dose accumulation at D center followed by a decline with increasing depth. Conclusion This study demonstrates that NIPAM gel dosimetry with MRI-based R2 mapping effectively verifies CyberKnife dose distributions. It exhibits strong dose sensitivity and accurately captures sharp gradients, highlighting its potential as a superior alternative to conventional dosimetry methods.

Landsat 8 OLI atmospheric correction neural network for inland waters in tropical regions - M. Van Nguyen; O. T. La; H. T. T. Nguyen; D. Heriza; B.-Y. Lin; G. Y. I. Ryadi; Chao-Hung Lin; Vinh Quang Pham (International Journal of Environmental Science and Technology, 2025)

Application of high-hydrostatic pressure to extend shelf life of miso-marinated escolar loins during cold storage - Pi-Chen Wei; Chung-Saint Lin; Yi-Chen Lee; Chi Kang; Chia-Hung Kuo; Todd Hsu; Yung-Hsiang Tsai (Food Control, 2025)

ZFP36L1 and ZFP36L2 reduce cyclin D1 expression by decreasing expression of E2F1 and long 3’UTR isoform of CCND1 transcripts - Tze-Sian Chan; Kun-Lin Lee; Ching-Sheng Hung; Hsin-Pei Chiang; Chia-Chen Chung; Yu-Chih Liang (Molecular and Cellular Biochemistry, 2025)

Indoxyl Sulfate Induces Ventricular Arrhythmias Attenuated by Secretoneurin in Right Ventricular Outflow Tract Cardiomyocytes - Yuan Hung; Chen-Chuan Cheng; Yen-Yu Lu; Shih-Yu Huang; Yao-Chang Chen; Fong-Jhih Lin; Wei-Shiang Lin; Yu-Hsun Kao; Yung-Kuo Lin; Shih-Ann Chen; Yi-Jen Chen (Cardiovascular Toxicology, 2025)

Induction of GPX4-regulated ferroptotic stress promotes epithelial-to-mesenchymal transition in renal tubule cells induced by PM2.5 - Chien-Hung Lin; Wen-Sheng Liu; Chuan Wan; Hsin-Hui Wang (Toxicology and Applied Pharmacology, 2025)

High performance catalyst CoNP for efficient electrochemical production of hydrogen peroxide - Ko-Shan Ho; Kuan-Ying Hung; Yu-Lin Hsiao; Hsiu-Chung Tu (Journal of Environmental Chemical Engineering, 2025)

Three echinoid assemblages with the earliest cidaroid (Echinodermata: Echinoidea) fossil record from the Middle Miocene of Taiwan - Hung-Kai Chen; Chia-Hsin Hsu; Jih-Pai Lin (Geobios, 2025)

The dissolved oxygen variation in seagrasses is influenced by DOC excretion and its associated microbes - Tzu-Hsuan Tu; En-Ju Lin; Chin-Chang Hung; Wen-Chen Chou; Yung-Yen Shih (Estuarine, Coastal and Shelf Science, 2025)

Ambient stable ZnBr2-assisted lead-free perovskite for enhanced piezoelectricity of polyvinylidene fluoride in versatile piezo-phototronic applications - Manikandan Venkatesan; Wei-Chun Lin; Wei-Cheng Chen; Jayashree Chandrasekar; Yu-Hang Huang; Kai-Wei Lin; Zih-Syuan Syu; Ja-Hon Lin; Wei-Hung Chiang; Wei-Ren Liu; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2025)

Optimizing sediment control by adjusting the relative spacing between trusses/beams in an open-type check dam - Hung-En Chen; Tzu-Yu Chen; Ya-Lin Zheng; Yen-Yu Chiu; Su-Chin Chen (Landslides, 2025)

Additional benefits of combined ceftriaxone and adipose-derived mesenchymal stem cells on revamping the outcomes in rodent after acute spinal infection - Tsung-Cheng Yin; Hung-Sheng Lin; Pei-Hsun Sung; John Y. Chiang; Chien-Hui Yang; Hon-Kan Yip; Kuan-Hung Chen (Journal of Molecular Histology, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Better objective sleep quality is associated with higher gut microbiota richness in older adults - Maria Teresa Wijaya; Ji-Tseng Fang; Geng-Hao Liu; Yuan-Ming Yeh; Ning-Hung Chen; Chih-Ming Lin; Kuain-Yi Wu; Chih-Mao Huang; Shwu-Hua Lee; Tatia M. C. Lee (GeroScience, 2025)
Aging is associated with disrupted sleep patterns, such as fragmented sleep and reduced efficiency, leading to negative health outcomes. There is evidence of a bidirectional relationship between sleep and gut microbiota, which plays a key role in the gut-brain axis and overall health. However, studies on this relationship in older adults have limited generalizability and show conflicting results, highlighting the need for further research. This study aimed to investigate the associations between sleep quality and gut microbiota composition in healthy Chinese older adults using subjective and objective sleep measures to capture various aspects of sleep quality and explore potential impacts on emotional well-being and cognitive performance. Subjective sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, while objective sleep quality was measured with actigraphy. Gut microbiota sequencing was performed on stool samples. The results show a robust positive association between gut microbiota richness and objective sleep quality in older adults, independent of subjective sleep quality and demographics, lifestyle, and health covariates. However, no significant link was found between gut microbiota richness and subjective sleep quality. Specific taxa like Bacteroidetes, Ruminococcus , Collinsella , Veillonella , and Holdemania were tentatively linked to sleep quality. These findings emphasize the connection between sleep quality and gut microbiota composition in older adults with potential research and clinical implications, improving our understanding of the mechanisms underlying the sleep-gut microbiota relationship and guiding the development of interventions for improving both sleep quality and gut health in older adults.

Dual-CycleGANs with Dynamic Guidance for Robust Underwater Image Restoration - Yu-Yang Lin; Wan-Jen Huang; Chia-Hung Yeh (Journal of Marine Science and Engineering, 2025)
The field of underwater image processing has gained significant attention recently, offering great potential for enhanced exploration of underwater environments, including applications such as underwater terrain scanning and autonomous underwater vehicles. However, underwater images frequently face challenges such as light attenuation, color distortion, and noise introduced by artificial light sources. These degradations not only affect image quality but also hinder the effectiveness of related application tasks. To address these issues, this paper presents a novel deep network model for single under-water image restoration. Our model does not rely on paired training images and incorporates two cycle-consistent generative adversarial network (CycleGAN) structures, forming a dual-CycleGAN architecture. This enables the simultaneous conversion of an underwater image to its in-air (atmospheric) counterpart while learning a light field image to guide the underwater image towards its in-air version. Experimental results indicate that the proposed method provides superior (or at least comparable) image restoration performance, both in terms of quantitative measures and visual quality, when compared to existing state-of-the-art techniques. Our model significantly reduces computational complexity, resulting in a more efficient approach that maintains superior restoration capabilities, ensuring faster processing times and lower memory usage, making it highly suitable for real-world applications.

Blockade of A2AR improved brain perfusion and cognitive function in a mouse model of Alzheimer’s disease - Mariana Sayuri Berto Udo; Julia Zaccarelli-Magalhães; Garrett Alan Clemons; Cristiane Teresinha Citadin; Julia Langman; Drew James Smith; Luiz Henrique Matuguma; Vesna Tesic; Hung Wen Lin (GeroScience, 2025)

Synergistic effect of probiotics and postbiotics on reducing cytokine storm, lung dysfunction, and immune escape phenomenon caused by SARS-CoV-2 infection - Yi-Heng Chiu; Hung-Pin Chiu; Meei-Yn Lin (Food Bioscience, 2025)

Inactivation of Salmonella Typhimurium on mung bean seeds by combined application of microbubbles and disinfections and its effect on sprouting - Hsiu-Ling Chen; Shih-Kao Chou; Rachelle D. Arcega; Chih-Yao Hou; Jong-Shinn Wu; Chih-Tung Liu; Chun-Ping Hsiao; Li-Yun Hung; Chia-Min Lin (Food Control, 2025)

Pitfalls in measuring solution toxicity using the level of bioluminescence inhibition in Aliivibrio fischeri - Cheng-Kun He; Ming-Chun Hung; Chong-Hao Hxu; Yi-Hsien Hsieh; Yung-Sheng Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Leveraging Bio-Waste onion skin for High-Performance triboelectric nanogenerators - Po-Yen Chang; Ting-Ying Huang; Chien-Hung Yang; Chia-Hsien Lee; Ru-Jong Jeng; Chih-Ping Chen; Meng-Fang Lin (Chemical Engineering Journal, 2025)

Checklist of marine fishes in the Beibu Gulf: fish classification, resource protection, and biodiversity challenge - Zhisen Luo; Murong Yi; Xiaodong Yang; Xiao Chen; Jinxi Wang; Changping Jiang; Fengming Liu; Konglan Luo; Xiongbo He; Hung-Du Lin; Bin Kang; Yunrong Yan (Journal of Oceanology and Limnology, 2025)

Deep learning in the advanced core sample porosity determination with XCT image - Hung-Yu Wu; Ching-Li Kuo; Chen-Yi Lin; Wei-Ta Chu (Earth Science Informatics, 2025)

Comprehensive evaluation of air quality: incense burning and night market emissions in Kaohsiung, Taiwan, using the ISCST3 air quality model - Pei-Cheng Cheng; Kassian T. T. Amesho; Yin-Cheng Huang; Yuan-Chung Lin; Feng-Chih Chou; Tsu-Nai Wang; Pei-Shih Chen; Kang-Shin Chen; Ken-Lin Chang; Chien-Hung Lee (Air Quality, Atmosphere & Health, 2025)

Performance of Convolutional Neural Network Models in Meningioma Segmentation in Magnetic Resonance Imaging: A Systematic Review and Meta-Analysis - Ting-Wei Wang; Jia-Sheng Hong; Wei-Kai Lee; Yi-Hui Lin; Huai-Che Yang; Cheng-Chia Lee; Hung-Chieh Chen; Hsiu-Mei Wu; Weir Chiang You; Yu-Te Wu (Neuroinformatics, 2024)
Background Meningioma, the most common primary brain tumor, presents significant challenges in MRI-based diagnosis and treatment planning due to its diverse manifestations. Convolutional Neural Networks (CNNs) have shown promise in improving the accuracy and efficiency of meningioma segmentation from MRI scans. This systematic review and meta-analysis assess the effectiveness of CNN models in segmenting meningioma using MRI. Methods Following the PRISMA guidelines, we searched PubMed, Embase, and Web of Science from their inception to December 20, 2023, to identify studies that used CNN models for meningioma segmentation in MRI. Methodological quality of the included studies was assessed using the CLAIM and QUADAS-2 tools. The primary variable was segmentation accuracy, which was evaluated using the Sørensen–Dice coefficient. Meta-analysis, subgroup analysis, and meta-regression were performed to investigate the effects of MRI sequence, CNN architecture, and training dataset size on model performance. Results Nine studies, comprising 4,828 patients, were included in the analysis. The pooled Dice score across all studies was 89% (95% CI: 87–90%). Internal validation studies yielded a pooled Dice score of 88% (95% CI: 85–91%), while external validation studies reported a pooled Dice score of 89% (95% CI: 88–90%). Models trained on multiple MRI sequences consistently outperformed those trained on single sequences. Meta-regression indicated that training dataset size did not significantly influence segmentation accuracy. Conclusion CNN models are highly effective for meningioma segmentation in MRI, particularly during the use of diverse datasets from multiple MRI sequences. This finding highlights the importance of data quality and imaging sequence selection in the development of CNN models. Standardization of MRI data acquisition and preprocessing may improve the performance of CNN models, thereby facilitating their clinical adoption for the optimal diagnosis and treatment of meningioma.

Changes in the small-molecule fingerprints of rice planted near an industrial explosion site in Taiwan - Wen-Ling Chen; Husan-Yu Tai; Chang-Chuan Chan; Hung-Chien Lin; Ting-Hsuan Hung; Mong-Hsun Tsai; Chia-Cheng Wei; Yu-San Han; Chuan-Chou Shen (Environmental Science and Pollution Research, 2024)

Potato Protein Hydrolysate (PPH902) treatment in adipocytes inhibits lipogenesis by activating AMPK - Yi-Ju Chen; Ching-Fang Chang; Rathinasamy Baskaran; Chih-Hung Liang; Hsin-Ning Kuo; Mosleh Mohammad Abomughaid; Wan-Teng Lin (South African Journal of Botany, 2024)

Carbonate precipitation-derived CO2 outgassing offsets the mineral weathering sink in the orogenic regime of southwestern Taiwan: Insights from triple Sr isotopes - Hou-Chun Liu; Yun-Cian Lin; Yan-Hong Chen; Meng-Xuan Li; Chen-Feng You; Kuo-Fang Huang; Wei-Jen Huang; Hung-Chun Chao (Science of The Total Environment, 2024)

SYNLAC prime probiotics enhances growth performance, and resistance of white shrimp, Penaeus vannamei to Enterocytozoon hepatopenaei and Vibrio alginollyticus: Insights into immune and metabolic pathway modulations - Ann-Chang Cheng; Hsiao-Tung Chang; Ting-Yu Lee; Jin-Seng Lin; Chun-Hung Liu (Fish & Shellfish Immunology, 2024)

Linking joint exposures to residential greenness and air pollution with adults’ social health in dense Hong Kong - Ting Zhang; Bo Huang; Sensen Wu; Jie Chen; Yizhen Yan; Yinyi Lin; Hung Wong; Samuel Yeung-Shan Wong; Roger Yat-Nork Chung (Environmental Pollution, 2024)

Seasonal distribution and population genetic structure of Psenopsis anomala (Japanese butterfish) inferred from otolith oxygen isotope ratios and mitochondrial DNA - Aafaq Nazir; Ting-Hung Lin; Tien-Hsia Kuo; Kotaro Shirai; Pei-Ling Wang; Jen-Chieh Shiao (Estuarine, Coastal and Shelf Science, 2024)

Injectable responsive chemodynamic hydrogel for the sustained and localized delivery of a ferroptosis inducer to improve anticancer therapy - Chu-Hung Chung; Tzu-Wei Lu; Chi Lin; Cheng-Wei Lin; Fwu-Long Mi (Chemical Engineering Journal, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Targeting PADI2 as a potential therapeutic strategy against metastasis in oral cancer via suppressing EMT-mediated migration and invasion and CCL3/5-induced angiogenesis - Shih-Kai Hung; Chih-Chia Yu; Hon-Yi Lin; Wen-Yen Chiou; Moon-Sing Lee; Ru-Inn Lin; Ming-Chi Lu (Clinical & Experimental Metastasis, 2024)

Validation of the constitution in Chinese medicine questionnaires with the newly developed blood-vacuity category: a rare Taiwanese case study - Ting-Yu Huang; Shi-Chen Ou; Wei-Te Huang; Yu-Chuan Lin; Hao-Hsiu Hung; Chin-Wei Chang; Kai-Yuan Hsiao; Yi-Wei Kao; Chien-Hua Wu; Wei-Shan Chang; Ben-Chang Shia; Sheng-Teng Huang (Advances in Traditional Medicine, 2024)

Toxicity, mutagenicity, and source identification of polycyclic aromatic hydrocarbons in ambient atmosphere and flue gas - Shih Yu Pan; Ya Syuan Wu; Yu-Cheng Chen; Yen-Shun Hsu; Yu Chi Lin; Pao Chen Hung; Charles C.-K. Chou; Somporn Chantara; Yuan Cheng Hsu; Kai Hsien Chi (Environmental Science and Pollution Research, 2024)
This study aimed to assess the characteristics of particulate matter (PM) and polycyclic aromatic hydrocarbons (PAHs) from various stationary and mobile emission sources in Taiwan, with a focus on source apportionment and associated health risks. The northern power plant, equipped with bag filters operating at 150 °C, had significantly lower FPM and CPM levels (0.44 and 0.13 mg/m 3 , respectively) compared to the central and southern power plants, which used electrostatic precipitators operating at 250 °C (FPM, 1.45–8.35 mg/m 3 ; CPM, 2.37–3.73 mg/m 3 ). Additionally, emissions from diesel vehicles under both idle and high-speed conditions exhibited higher FPM levels (3.46–4.67 mg/m 3 ) than gasoline vehicles (0.19–0.40 mg/m 3 ). In terms of PAH toxicity, diesel vehicle emissions had significantly higher BaP-TEQ (87.3 ng/m 3 ) and BaP-MEQ (25.9 ng/m 3 ) levels compared to power plants (BaP-TEQ, 5.49 ng/m 3 ; BaP-MEQ, 2.65 ng/m 3 ). The highest ambient concentrations of PM2.5, BaP-TEQ, and BaP-MEQ were recorded at traffic sites, with values of 48 ± 36 µg/m 3 , 0.29 ng/m 3 , and 0.11 ng/m 3 , respectively. Differences in PAH distributions between stationary and mobile sources were influenced by factors such as pollution control technologies, combustion temperatures, and fuel types. Diesel vehicle emissions were dominated by benzo[g,h,i]perylene (BghiP), indeno[1,2,3-cd]pyrene (IND), benzo[a]pyrene (BaP), and benzo[b]fluoranthene (BbF) under idle conditions, while phenanthrene (PA), pyrene (Pyr), and BghiP were prevalent under high-speed conditions. Source apportionment conducted using principal component analysis (PCA) and positive matrix factorization (PMF) identified diesel and gasoline vehicles as the dominant contributors to atmospheric PAHs in Taiwan, accounting for 38% of the total, followed by coal-fired power plants at 35%. The highest lifetime excess cancer risk (ECR) of 2.5 × 10⁻ 5 was observed in traffic-dense areas, emphasizing the public health implications of vehicle emissions. The study adds credibility to the source apportionment findings, and the health risk analysis highlights variations across different regions, including traffic, urban, rural, and background zones.

Investigating the role of membrane lipid composition differences on spray drying survival in Lactobacillus bulgaricus using non-targeted Lipidomics - Fengzhi Qiao; Shaolei Wang; Jian He; Weilian Hung; Xia Ma; Pimin Gong; Jiadong Li; Ting Sun; Cristabelle De Souza; Lanwei Zhang; Kai Lin (Food Chemistry, 2024)

Systematic establishment of the relationship between skin absorption and toxicity of furanoids via in silico, in vitro, and in vivo assessments - Yin-Ku Lin; Chien-Yu Hsiao; Chih-Jung Chen; Ahmed Alalaiwe; Chin Lee; Tse-Hung Huang; Jia-You Fang (Environmental Research, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Seismic rehabilitation of RC frames with innovative precast U-shaped UHPC jackets: Experimental evaluation and computational simulation - Chung-Chan Hung; Chin-Cheng Lin; Tuong Dat Dinh Do (Engineering Structures, 2024)

Gel electrolyte design for nonflammable lithium-ion batteries with high-rate and high-voltage characteristics - Po-Wei Huang; Qin-Cheng Zhang; Ming-Yuan Hung; Yan-Cheng Lin; Hong-Kang Tian; Yuh-Lang Lee; Jeng-Shiung Jan; Hsisheng Teng (Chemical Engineering Journal, 2024)

Role of HIF-1α-Activated IL-22/IL-22R1/Bmi1 Signaling Modulates the Self-Renewal of Cardiac Stem Cells in Acute Myocardial Ischemia - Wei Lee; Syuan-Ling Lin; Chih-Sheng Chiang; Jui-Yu Chen; Wee-Wei Chieng; Shu-Rou Huang; Ting-Yu Chang; B. Linju Yen; Mien-Chie Hung; Kuan-Cheng Chang; Hsu-Tung Lee; Long-Bin Jeng; et al. (Stem Cell Reviews and Reports, 2024)

Soluble Epoxide Hydrolase Inhibitor Ameliorates Olfactory Dysfunction, Modulates Microglia Polarization, and Attenuates Neuroinflammation after Ischemic Brain Injury - Chien-Fu Yeh; Tung-Yueh Chuang; Ming-Ying Lan; Yung-Yang Lin; Wei-Hao Huang; Yu-Wen Hung (Journal of Neuroimmune Pharmacology, 2024)

Enhanced removal of sulfamethoxazole via adsorption and photodegradation using biochar-modified iodine-doped TiO2 photocatalysts under simulated sunlight - Yung-Dun Dai; Jia-Hou Lin; Chung-Hsuang Hung; Ching Yuan (Process Safety and Environmental Protection, 2024)

Achieving over 42 % indoor efficiency in wide-bandgap perovskite solar cells through optimized interfacial passivation and carrier transport - Zhong-En Shi; Ta-Hung Cheng; Chien-Yu Lung; Chi-Wei Lin; Chih-Lin Wang; Bing-Huang Jiang; Yu-Sheng Hsiao; Chih-Ping Chen (Chemical Engineering Journal, 2024)

Synergistic Triple-Action morphological composite Anode: Integrating lattice Softening, Interfacial electric Fields, and dual confinement for superior Potassium-Ion battery performance - Jia-Sheng Lin; Yi-Yen Hsieh; Kai-Yuan Hsiao; Yi-Chun Yang; Che-Hung Wang; Ming-Yen Lu; Wen-Wei Wu; Hsing-Yu Tuan (Chemical Engineering Journal, 2024)

Targeting TGFβ receptor-mediated snail and twist: WSG, a polysaccharide from Ganoderma lucidum, and it-based dissolvable microneedle patch suppress melanoma cells - Hung-Chih Lo; Tzu-En Lin; Che-Yu Lin; Wei-Hao Wang; Yu-Chen Chen; Pei-Hsien Tsai; Jung-Chen Su; Mei-Kuang Lu; Wei-Hung Hsu; Tung-Yi Lin (Carbohydrate Polymers, 2024)

Long non-coding RNA FKSG29 regulates oxidative stress and endothelial dysfunction in obstructive sleep apnea - Yung-Che Chen; Po-Yuan Hsu; Mao-Chang Su; Yung-Lung Chen; Ya‐Ting Chang; Chien-Hung Chin; I.-Chun Lin; Yu-Mu Chen; Ting-Ya Wang; Yong-Yong Lin; Chiu-Ping Lee; Meng-Chih Lin; et al. (Molecular and Cellular Biochemistry, 2024)

Elevated surface ozone concentration caused by subtropical cyclones and topographical effect: Model simulation and field measurement - Kuo-Cheng Lo; Wen-Hsi Cheng; Chitsan Lin; Chung-Hsuang Hung; Chung-Shin Yuan; Yu-Lun Tseng (Urban Climate, 2024)

Combination of an enzyme-linked immunosorbent assay and an indirect fluorescence assay for a nationwide sero-survey of Toxoplasma gondii infection in pig herds in Taiwan - Kendy Tzu-Yun Teng; Chao-Chin Chang; Shao-Wen Hung; Ming-Tang Chiou; Chao-Nan Lin; Cheng-Yao Yang (Preventive Veterinary Medicine, 2024)

Review on personal protective equipment: Emerging concerns in micro(nano)plastic pollution and strategies for addressing environmental challenges - Van-Giang Le; Minh-Ky Nguyen; Chitsan Lin; Hoang-Lam Nguyen; Tri Quang Hung Nguyen; Nguyen K. Hue; Quoc-Minh Truong; Soon W. Chang; X. Hoan Nguyen; D. Duc Nguyen (Environmental Research, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Improvement of the Diagnostic Method for the Detection of Parasite Eggs Using the Formalin Ethyl Acetate Concentration Technique - Jia-Hung Liou; Te-Ling Lu; Hui-Fen Cheng; Long-Wei Lin; Po-Cheng Kung; Hong-Jing Chuang; Te-Hsiu Lee; Chee-Hong Chan; Te-Jung Lu (Acta Parasitologica, 2024)

Natural coral recovery despite negative population growth - Aziz J. Mulla; Vianney Denis; Che‐Hung Lin; Chia‐Ling Fong; Jia‐Ho Shiu; Yoko Nozawa (Ecology, 2024)
Demographic processes that ensure the recovery and resilience of marine populations are critical as climate change sends an increasing proportion on a trajectory of decline. Yet for some populations, recovery potential remains high. We conducted annual monitoring over 9 years (2012–2020) to assess the recovery of coral populations belonging to the genus Pocillopora . These populations experienced a catastrophic collapse following a severe typhoon in 2009. From the start of the monitoring period, high initial recruitment led to the establishment of a juvenile population that rapidly transitioned to sexually mature adults, which dominated the population within 6 years after the disturbance. As a result, coral cover increased from 1.1% to 20.2% during this time. To identify key demographic drivers of recovery and population growth rates (λ), we applied kernel‐resampled integral projection models (IPMs), constructing eight successive models to examine annual change. IPMs were able to capture reproductive traits as key demographic drivers over the initial 3 years, while individual growth was a continuous key demographic driver throughout the entire monitoring period. IPMs further detected a pulse of reproductive output subsequent to two further Category 5 typhoon events during the monitoring period, exemplifying key mechanisms of resilience for coral populations impacted by disturbance. Despite rapid recovery, (i.e., increased coral cover, individual colony growth, low mortality), IPMs estimated predominantly negative values of λ, indicating a declining population. Indeed, while λ translates to a change in the number of individuals, the recovery of coral populations can also be driven by an increase in the size of surviving colonies. Our results illustrate that accumulating long‐term data on historical dynamics and applying IPMs to extract demographic drivers are crucial for future predictions that are based on comprehensive and robust understandings of ecological change.

Fast-track development of an automated solar photovoltaic module detecting framework utilizing open-access multispectral satellite imagery - Pei-Cheng Wu; Meng-Chi Hung; Ruey-Shing Lin; Shu-Yen Huang; Zhao-Hui Lin (Remote Sensing Applications: Society and Environment, 2024)

Comparative transcriptome and metabolome reveal the role of acidic electrolyzed oxidizing water in improving postharvest disease resistance of longan fruit - Zhongqi Fan; Ling Fang; Qingqing Liu; Hetong Lin; Mengshi Lin; Yifen Lin; Hui Wang; Yen-Con Hung; Yihui Chen (Food Chemistry, 2024)

Acidic electrolyzed-oxidizing water treatment mitigated the disease progression in Phomopsis longanae Chi-infected longans by modulating ROS and membrane lipid metabolism - Meiling Li; Hetong Lin; Chao Wang; Yazhen Chen; Mengshi Lin; Yen-Con Hung; Yifen Lin; Zhongqi Fan; Hui Wang; Yihui Chen (Food Chemistry, 2024)

Selection of vaccine candidates against Pseudomonas koreensis using reverse vaccinology and a preliminary efficacy trial in Empurau (Tor tambroides) - Cindy Jia yung Kho; Melinda Mei Lin Lau; Hung Hui Chung; Koji Fukui (Fish & Shellfish Immunology, 2024)

3D Effect and countermeasure of 2D geoelectrical imaging of a subsurface linear structure - Yin-Chun Hung; Haoran Wang; Po-Lin Wu; Hsin-Chang Liu; Chih-Ping Lin (Engineering Geology, 2024)

The role of galectins in the regulation of autophagy and inflammasome in host immunity - Tzu-Han Lo; I-Chun Weng; Hung-Lin Chen; Fu-Tong Liu (Seminars in Immunopathology, 2024)

Novel GaN-Based Substrates with Gold Nanostructures for Ultra-Sensitive SERS Analysis: Micro-Nano Pit Morphology for Enhanced Molecular Detection - Tsung-Shine Ko; Chen-An Deng; Jiann Shieh; Hung Ji Huang; Yung-Sheng Lin; Yang-Wei Lin; Yi-Chun Du (Journal of Medical and Biological Engineering, 2024)

Underwater Image Enhancement Based on Light Field-Guided Rendering Network - Chia-Hung Yeh; Yu-Wei Lai; Yu-Yang Lin; Mei-Juan Chen; Chua-Chin Wang (Journal of Marine Science and Engineering, 2024)
Underwater images often encounter challenges such as attenuation, color distortion, and noise caused by artificial lighting sources. These imperfections not only degrade image quality but also impose constraints on related application tasks. Improving underwater image quality is crucial for underwater activities. However, obtaining clear underwater images has been a challenge, because scattering and blur hinder the rendering of true underwater colors, affecting the accuracy of underwater exploration. Therefore, this paper proposes a new deep network model for single underwater image enhancement. More specifically, our framework includes a light field module (LFM) and sketch module, aiming at the generation of a light field map of the target image for improving the color representation and preserving the details of the original image by providing contour information. The restored underwater image is gradually enhanced, guided by the light field map. The experimental results show the better image restoration effectiveness, both quantitatively and qualitatively, of the proposed method with a lower (or comparable) computing cost, compared with the state-of-the-art approaches.

Kaguacidine A: a novel spirohydantoin-containing cucurbitane glycoside from vines of Momordica charantia L. - Hung-Tse Huang; I-Wen Lo; Yu-Chi Lin; Liao Geng-You; Yun-Sheng Lin; Li-Jie Zhang; Tsung-Lin Li; Chia-Ching Liaw; Yao-Haur Kuo (Natural Product Research, 2024)

Association among polydisperse aerodynamic size of bioaerosols, biodiversity and urbanization in kindergartens - Tzu-Hsien Lin; Ying-Hsiang Chou; Tzu-Yu Hsu; Chun-Hui Hung; Chane-Yu Lai (Chemosphere, 2024)

The removal and transformation of fipronil using a photoelectrochemical device combined with a carbonized TiO2 nanocomposite electrode - Jheng-Sian Yang; Jhen-Cih Wu; Chia-Hung Hou; Angela Yu-Chen Lin (Journal of Water Process Engineering, 2024)

Optimizing bimetallic-insect exuviate melanin composite cathodes using response surface methodology to enhance the H2O2 yield and selectivity of the electro-Fenton process - Chi-Wen Lin; Ting-Hung Wang; Shu-Hui Liu (Journal of Water Process Engineering, 2024)

Savanna Nightjars (Caprimulgus affinis stictomus) adjust calling height to gain amplitude advantage in urban environments - Shih-Hsiung Liang; Chia-Hung Jen; Lin-Lee Lee; Chao-Chieh Chen; Bao-Sen Shieh (Journal of Ornithology, 2024)

Mitochondrial genome analysis reveals phylogenetic insights and gene rearrangements in Parupeneus (Syngnathiformes: Mullidae) - Zhisen Luo; Murong Yi; Xiaodong Yang; Hui Wen; Changping Jiang; Xiongbo He; Hung-Du Lin; Yunrong Yan (Frontiers in Marine Science, 2024)
Despite the critical role of mitochondrial genomes (mitogenomes) in species identification and evolutionary studies in the genus Parupeneus , current resources are inadequate, given the species richness. Although previous studies have suggested a complex evolutionary history, the detailed mitogenomic variations and their implications remain largely unexplored. Therefore, we sequenced and assembled the mitogenomes of P . barberinoides , P . barberinus , P . biaculeatus , P . crassilabris , P . cyclostomus , P . heptacanthus , P . multifasciatus , and P . chrysopleuron , to enrich the molecular data and provide novel insights into the genetic diversity, evolutionary dynamics and phylogenetics of the family Mullidae. Our analysis revealed a novel gene rearrangement in P . chrysopleuron , Cytb - T - P -CR- Q - I - F -12S- V -16S- ND1-M - ND2 , which differed from the conventional sequence of Cytb - T - P -CR- F -12S- V -16S- ND1 - I - Q - M - ND2 observed in other species. In the novel rearrangement, four non-coding regions are inserted between ND1 and M , Q and I , I and ψ M (tRNA- Met pseudogene), ψ M and F . We assume that two tandem duplication/random loss events occur in the CR and IQM , making the entire sequence longer than that in other Parupeneus species. The phylogenetic results indicated that Mullidae formed a sister group relationship with the family Dactylopteridae, contradicting previous studies that identified a sister group relationship between Mullidae and Callionymoidei. The genera Parupeneus and Mullus formed a sister group, and discrepancies were found in the topological structure of the interspecies relationships within the genus Parupeneus compared with those reported by previous studies. Through combined phylogenetic and mitochondrial structural analysis, we found that phylogenetic topology is closely related to mitochondrial structural abnormalities. This study not only expands the mitogenomic dataset available for Mullidae but also underscores the importance of mitochondrial DNA studies in resolving taxonomic ambiguities and understanding the evolutionary history of marine fishes. Our study contributes to the ongoing research on marine fish taxonomy, mitogenomics, and evolutionary biology by providing new insights into the genetic diversity of marine ecosystems.

Species selection as a key factor in the afforestation of coastal salt-affected lands: Insights from pot and field experiments - Tzu-Hao Su; Yang Shen; Yao-Yu Chiang; Yu-Ting Liu; Han-Ming You; Hung-Chih Lin; Kuan-Ning Kung; Yao-Moan Huang; Chih-Ming Lai (Journal of Environmental Management, 2024)

Effects of adding Bacillus subtilis natto NTU-18 in paste feed on growth, intestinal morphology, gastrointestinal microbiota diversity, immunity, and disease resistance of Anguilla japonica glass eels - Yen-Ting Lin; Yu-Chen Hung; Li-Han Chen; Kung-Ta Lee; Yu-San Han (Fish & Shellfish Immunology, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

An Automatic Approach of Video-Based Landmark Detection and Movement Analysis for Assessing Symptoms of Bradykinesia in Parkinson’s Disease - Ching-Fang Chien; Chen-Sen Ouyang; Yi-Hung Chiu; Lung-Chang Lin; Rei-Cheng Yang; Yang-Pei Chang; San-Yuan Wang; Li-Min Liou (Journal of Medical and Biological Engineering, 2024)

Marine macro-litter sources and ecological impact: a review - Van-Giang Le; Hoang-Lam Nguyen; Minh-Ky Nguyen; Chitsan Lin; Nguyen T. Quang Hung; Akhil P. Khedulkar; Nguyen K. Hue; Phung T. Thu Trang; Arvind Kumar Mungray; D. Duc Nguyen (Environmental Chemistry Letters, 2024)

Correction to: Anti-cancer strategies targeting the autotaxin-lysophosphatidic acid receptor axis: is there a path forward? - Gábor Tigyi; Mélanie A. Dacheux; Kuan-Hung Lin; Junming Yue; Derek Norman; Zoltán Benyó; Sue Chin Lee (Cancer and Metastasis Reviews, 2024)

Characterizing dissolved inorganic and organic nutrients in the oligotrophic Kuroshio Current off eastern Taiwan during warm seasons - Jia-Jang Hung; Sheng-Hsian Tsai; Yen-Hui Lin; Zhi-Ying Hsiang (Frontiers in Marine Science, 2024)
This study conducted sensitive and precise analyses of dissolved organic nitrogen (DON) and dissolved organic phosphorus (DOP) concentrations and trace concentrations of nitrate and nitrite (N+N) and soluble reactive phosphorus (SRP) in seawater. The methods were applied to investigate the distributions and controls of N+N, SRP, DON, and DOP in the oligotrophic Kuroshio Current (KC) area off eastern Taiwan during warm seasons. The water in the studied area was classified into four major types: typical Kuroshio water (KW), KW influenced by the East China Sea water, KC influenced by the South China Sea (SCS) water, and KW influenced by the SCS water and river plumes, which is confined to the coastal zone. Nutrient distributions in KC revealed very low N+N (0.002−0.40 μM) and SRP (0.015−0.125 μM) concentrations but high DON (<8 μM) and DOP (<0.3 μM) concentrations above the nutricline depth, which accounted for >80% of TDN and TDP, respectively; theses concentrations can primarily be attributed to strong, permanent surface stratification. Among the water types, KW had the lowest N+N, SRP, DON, and DOP concentrations but greatest chlorophyll maximum depth and nutricline depth, except for in locations influenced by island-induced upwelling. The concentrations of all nutrients increased by various degrees in the other water types, which was attributed to the exchange and mixing of different water masses and coastal uplift of subsurface waters. KW was not only highly oligotrophic but also N+N-limited reflected from very low [N+N]/[SRP] ratio (0.02−0.15) in the mixed layer (ML). Overall, the N+N limitation and high nitrate anomaly value (N*: 2.47 ± 0.16 μM) above the nutricline depth strongly indicate prevailing N 2 fixation at the surface of KW. Very high DON/DOP ratio in KW (16.9−69.1) probably resulted from the release of N-rich organic nutrients from phytoplankton including N 2 fixers at the surface and faster recycling of DOP than DON in deep waters. Persistent coastal uplift of subsurface water occurs everywhere over the shore-side region of the KC, resulting in increasing surface concentrations of nutrients and chlorophyll a . Overall, the aforementioned physical and biogeochemical processes determined the upper-ocean distributions of nutrient species in warm seasons.

Protective Effects of Roselle Aqueous Extracts against UV-Induced Damage in Zebrafish Fins - I-Ting Lee; Ching-Yuan Huang; Wei-Lin Su; Tran M. Truong; Chi-Chung Wen; Bo-Chang Wang; Yau-Hung Chen (Fishes, 2024)
(1) Background: Roselle (Hibiscus sabdariffa) is a flowering plant reported to have anti-obesity, antioxidant, antibacterial, and anti-inflammatory effects. This study aims to evaluate the UV-absorbing and antioxidant activities of roselle aqueous extracts (RAE) and test the protective effects of RAE against UV radiation in zebrafish embryos. (2) Methods: DPPH assay and UV-spectrum methods were applied to evaluate the antioxidant and UV-absorbing activities, respectively. The protective effects of RAE were evaluated using fin morphology recording, Kaplan–Meier analysis, and Cox proportional hazards regression. Real-time PCR experiments were also applied to detect both the UV- and RAE-induced gene expressions. (3) Results: Our results show that (i) RAE had UV-absorbing abilities and significantly reduced ROS production in vitro; (ii) the mean times of malformed fins in the UV + RAE (36 and 48 ppm) groups were 3.56 and 4.44 days, respectively, and were prolonged compared to those in the UV-only group (3.36 days); (iii) zebrafish in the UV + RAE (36 and 48 ppm) groups were 0.963 and 0.496 (p

RETRACTED: Applications of engineered biochar in remediation of heavy metal(loid)s pollution from wastewater: Current perspectives toward sustainable development goals - Thien-Khanh Tran; Loan Huynh; Hoang-Lam Nguyen; Minh-Ky Nguyen; Chitsan Lin; Tuan-Dung Hoang; Nguyen Tri Q. Hung; X. Hoan Nguyen; S. Woong Chang; D. Duc Nguyen (Science of The Total Environment, 2024)

Exploring the food-energy-water nexus in coupled natural-human systems under climate change with a fully integrated agent-based modeling framework - Jiaorui Zhang; Y.C. Ethan Yang; Guta W. Abeshu; Hongyi Li; Fengwei Hung; Chung-Yi Lin; L. Ruby Leung (Journal of Hydrology, 2024)

Isolation, identification and characterisation of Pseudomonas koreensis CM-01 isolated from diseased Malaysian mahseer (Tor tambroides) - Melinda Mei Lin Lau; Cindy Jia Yung Kho; Hung Hui Chung; Azham Zulkharnain (Fish & Shellfish Immunology, 2024)

Establishment of a cobia (Rachycentron canadum) gill cell line: A valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2024)

A modified lift-off test for restressing anchors of a rehabilitated landslide slope - Shih-Hao Cheng; Kuo-Hsin Yang; Shih-Yuan Lin; Chen-Kan Liao; Hung-Jiun Liao (Landslides, 2024)

Quantifying payloads of antibody‒drug conjugates using a postcolumn infused-internal standard strategy with LC‒MS - Chih-Ning Cheng; Hsiao-Wei Liao; Ching-Hung Lin; Wen-Chi Chang; I-Chun Chen; Yen-Shen Lu; Ching-Hua Kuo (Analytica Chimica Acta, 2024)

Nucleocytoplasmic shuttling of BEFV M protein-modulated by lamin A/C and chromosome maintenance region 1 through a transcription-, carrier- and energy-dependent pathway - Yu-Kang Chang; Yi-Jyum Lin; Ching-Yuan Cheng; Pei-Chien Tsai; Chi-Young Wang; Brent L. Nielsen; Hung-Jen Liu (Veterinary Microbiology, 2024)

Force-activated ratiometric fluorescence switching of tensile mechano-fluorophoric polyurethane elastomers with enhanced toughnesses improved by mechanically interlocked [c2] daisy chain rotaxanes - Tu Thi Kim Cuc; Chen-Hao Hung; Ting-Chi Wu; Pham Quoc Nhien; Trang Manh Khang; Bui Thi Buu Hue; Wei-Tsung Chuang; Hong-Cheu Lin (Chemical Engineering Journal, 2024)

Melatonin Enhanced Microglia M2 Polarization in Rat Model of Neuro-inflammation Via Regulating ER Stress/PPARδ/SIRT1 Signaling Axis - Hung-Chuan Pan; Cheng-Ning Yang; Wen-Jane Lee; Jason Sheehan; Sheng-Mao Wu; Hong-Shiu Chen; Mao-Hsun Lin; Li-Wei Shen; Shu-Hua Lee; Chin-Chang Shen; Liang-Yi Pan; Shing‑Hwa Liu; et al. (Journal of Neuroimmune Pharmacology, 2024)

Lack of effects of eight-week left dorsolateral prefrontal theta burst stimulation on white matter macro/microstructure and connection in autism - Chun-Hung Yeh; Po-Chun Lin; Rung-Yu Tseng; Yi-Ping Chao; Chen-Te Wu; Tai-Li Chou; Rou-Shayn Chen; Susan Shur-Fen Gau; Hsing-Chang Ni; Hsiang-Yuan Lin (Brain Imaging and Behavior, 2024)

Ecological and human health hazards of soil heavy metals after wildfire: A case study of Liangshan Yi autonomous prefecture, China - Lin Rao; Chao Zheng; Jian-Bin Chen; Jun-Zhuo Cai; Zhan-Biao Yang; Xiao-Xun Xu; Guo-Chun Lv; Chang-Lian Xu; Gui-Yin Wang; Yu-Bon Man; Ming-Hung Wong; Zhang Cheng (Chemosphere, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Photo-protection and photo-inhibition during light induction in Barbula indica and Conocephalum conicum under different light gradients - Chung-I. Chen; Kuan-Hung Lin; Meng-Yuan Huang; Kuei-Yu Yao; Chau-Ching Huang; Tzu-Chao Lin; En-Liang Chu; Jia-Dong Yang; Ching-Wen Wang (Photosynthesis Research, 2024)

Heteronemin promotes iron-dependent cell death in pancreatic cancer - Gizem Kaftan; Mümin Alper Erdoğan; Mohamed El-Shazly; Mei-Chin Lu; Shou-Ping Shih; Hung-Yu Lin; Luciano Saso; Güliz Armagan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Probing the hair detectability of prohibited substances in sports: an in vivo-in silico-clinical approach and analytical implications compared with plasma, urine, and faeces - Shao-Hsin Hung; Hung-Lin Kan; Chun-Wei Tung; Yi-Ching Lin; Ting-Ting Chen; Ciao Tian; William Chih-Wei Chang (Archives of Toxicology, 2024)
Hair analysis is a crucial method in forensic toxicology with potential applications in revealing doping histories in sports. Despite its widespread use, knowledge about detectable substances in hair is limited. This study systematically assessed the detectability of prohibited substances in sports using a multifaceted approach. Initially, an animal model received a subset of 17 model drugs to compare dose dependencies and detection windows across different matrices. Subsequently, hair incorporation data from the animal experiment were extrapolated to all substances on the World Anti-Doping Agency’s List through in-silico prediction. The detectability of substances in hair was further validated in a proof-of-concept human study involving the consumption of diuretics and masking agents. Semi-quantitative analysis of substances in specimens was performed using ultra-performance liquid chromatography–tandem mass spectrometry. Results showed plasma had optimal dose dependencies with limited detection windows, while urine, faeces, and hair exhibited a reasonable relationship with the administered dose. Notably, hair displayed the highest detection probability (14 out of 17) for compounds, including anabolic agents, hormones, and diuretics, with beta-2 agonists undetected. Diuretics such as furosemide, canrenone, and hydrochlorothiazide showed the highest hair incorporation. Authentic human hair confirmed diuretic detectability, and their use duration was determined via segmental analysis. Noteworthy is the first-time reporting of canrenone in human hair. Anabolic agents were expected in hair, whereas undetectable compounds, such as peptide hormones and beta-2 agonists, were likely due to large molecular mass or high polarity. This study enhances understanding of hair analysis in doping investigations, providing insights into substance detectability.

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Overdose with the anesthetic propofol causes hematological cytotoxicity and immune cell alteration in an experimental ex vivo whole blood culture model - Chung-Hsi Hsing; Yu-Ping Hung; Ming-Chung Lin; Chia-Ling Chen; Yung-Ting Wang; Po-Chun Tseng; Rahmat Dani Satria; Chiou-Feng Lin (Toxicology in Vitro, 2024)

Significant changes in cloud radiative effects over Southwestern United States during the COVID-19 flight reduction period - Jingyu Wang; Yun Lin; Xianfeng Wang; Yu Gu; Steve Hung-Lam Yim (Science of The Total Environment, 2024)

Evaluate the effect of β-cyclodextrin on the sensory and physicochemical properties of bitter gourd extract during thermal processing - Cam Thi Hong Tran; Hui-Min David Wang; Le Thi Hong Anh; Chitsan Lin; Chun-Yung Huang; Chia-Hung Kuo (Food Chemistry, 2024)

Shrimp SIRT4 promotes white spot syndrome virus replication - Yu Kent Tan; Brandon Rafael de Jesús Castillo-Corea; Ramya Kumar; Ping-Hung Lai; Shih-Shun Lin; Han-Ching Wang (Fish & Shellfish Immunology, 2024)

Waterlogging influences the physiology index and antioxidant enzyme activity in Cucurbita maxima and Cucurbita moschata - Kuan-Hung Lin; Shi-Peng Chen; Yi-Ru Su; Yi-Heng Tsai; Hsin-Hung Lin (Horticulture, Environment, and Biotechnology, 2024)

Breaking prolonged sitting increases 24-h physical activity and self-perceived energy levels but does not acutely affect cognition in healthy adults - Feng-Chih Kuo; Yun-Ting Lin; Ting-Yu Chueh; Yu-Kai Chang; Tsung-Min Hung; Yung-Chih Chen (European Journal of Applied Physiology, 2024)

A numerical investigation of an indoor dry storage facility on heat transfer - Chia-Wei Lin; Yung-Shin Tseng; Kai-Qi Lin; Yu-Hsuan Chang; Tzu-Chen Hung; Hua-Yi Hsu (Annals of Nuclear Energy, 2024)

Exploring the potential of the nano-based sunscreens and antioxidants for preventing and treating skin photoaging - Chih-Hung Lin; Ming-Hsien Lin; Yu-Kuo Chung; Ahmed Alalaiwe; Chi-Feng Hung; Jia-You Fang (Chemosphere, 2024)

Foraging flight-based health indicators for honey bee colonies using automatic monitoring systems - Joe-Air Jiang; Jen-Cheng Wang; Chien-Peng Huang; Mu-Hwa Lee; An-Chi Liu; Hung-Jen Lin; Chien-Hao Wang; Cheng-Ying Chou; En-Cheng Yang (Computers and Electronics in Agriculture, 2024)

Optimization of the manufacturing process and properties of alkali-activated palm oil fuel ash-based cold-bonded aggregates - Jiayi Lin; Tee How Tan; Jerome Song Yeo; Yingxin Goh; Tung-Chai Ling; Kim Hung Mo (Journal of Cleaner Production, 2024)

Micro-scale urbanization-based risk factors for dengue epidemics - Pei-Sheng Lin; Wei-Liang Liu; Chaur-Dong Chen; Tzai-Hung Wen; Chun-Hong Chen; Li-Wei Chen; Yi-Hung Kung (International Journal of Biometeorology, 2024)

Anti-liquefaction mechanisms in buildings with shallow foundations with a focus on lowering the ground water table - Chih-Chieh Lu; Kuan-Yu Chen; Lin-Mao Hu; Wen-Yi Hung (Soil Dynamics and Earthquake Engineering, 2023)

A comprehensive review of micro- and nano-plastics in the atmosphere: Occurrence, fate, toxicity, and strategies for risk reduction - Van-Giang Le; Minh-Ky Nguyen; Hoang-Lam Nguyen; Chitsan Lin; Mohammed Hadi; Nguyen Tri Quang Hung; Hong-Giang Hoang; Khoi Nghia Nguyen; Huu-Tuan Tran; Deyi Hou; Tao Zhang; Nanthi S. Bolan (Science of The Total Environment, 2023)

The joint association of ambient air pollution and different sleep posture with mild obstructive sleep apnea: A study conducted at Taipei Sleep Center - Yansu He; Wen-Te Liu; Shangyang Lin; Zhiyuan Li; Hong Qiu; Steve Hung Lam Yim; Hsiao-Chi Chuang; Kin Fai Ho (Science of The Total Environment, 2023)

A review on sterilization methods of environmental decontamination to prevent the coronavirus SARS-CoV-2 (COVID-19 virus): A new challenge towards eco-friendly solutions - Nguyen Trung Hiep; Minh-Ky Nguyen; Huynh Tan Nhut; Nguyen Tri Quang Hung; Nguyen Cong Manh; Chitsan Lin; S. Woong Chang; Myoung Jin Um; D. Duc Nguyen (Science of The Total Environment, 2023)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Heterostructured YFeO3/CeO2 as efficient photoelectrode for photoelectrochemical degradation of organic pollutants under visible light irradiation - Yen-Shen Kuo; Mu-Jung Lin; Cheng-Liang Hsu; Yi-Hung Liu (Journal of Water Process Engineering, 2023)

Effects of vitamin D and zinc deficiency in acute and long COVID syndrome - Kuang-Yu Chen; Chin-Kuo Lin; Ning-Hung Chen (Journal of Trace Elements in Medicine and Biology, 2023)

Active packaging incorporating chitosan, casein phosphopeptide, and plasmonic modification to maintain quality and regulate the respiration rate of fresh-cut Pyrus serotina Rehder during storage - Chao-Kai Chang; Fang-Yu Lin; Sheng-Yen Tsai; Mohsen Gavahian; Kuan-Chen Cheng; Chih-Yao Hou; Min-Hung Chen; Shella Permatasari Santoso; Chang-Wei Hsieh (Food Packaging and Shelf Life, 2023)

Exploration of the Catalytic Cycle Dynamics of Vigna Radiata H+–Translocating Pyrophosphatases Through Hydrogen–Deuterium Exchange Mass Spectrometry - Li-Kun Huang; Yi-Cyuan Huang; Pin-Chuan Chen; Ching-Hung Lee; Shih-Ming Lin; Yuan-Hao Howard Hsu; Rong-Long Pan (The Journal of Membrane Biology, 2023)

Intercomparison between sentinel-1, sentinel-2, and landsat-8 on reservoir water level estimation - Manikandan Sathianarayanan; Ajay Saraswat; A. S. Mohammed Abdul Athick; Hung-Ming Lin (Sustainable Water Resources Management, 2023)

Practically Feasible Sensor-Embedded Kinetic Assessment Piano System for Quantifying Striking Force of Digits During Piano Playing - Kuan-Yin Lai; Chieh-Hsiang Hsu; Yu-Chen Lin; Chung-Hung Tsai; Cheng-Feng Lin; Li-Chieh Kuo; Fong-Chin Su (Journal of Medical and Biological Engineering, 2023)
Purpose Understanding the pathogenesis of playing-related hand disorders through investigations based on coordination and biomechanical perspectives is indispensable. This study aimed to establish a sensor-embedded kinetic assessment piano system (SeKAPS) and conduct reliability and validity tests for this system. In addition, the differences in digit coordination between professional pianists and non-musicians were investigated. Methods Twelve subminiature load cells were embedded in the middle of the 12 corresponding keys of an upright piano. A customized calibrated system with a load cell was used to establish the criterion-related validity of the SeKAPS. The reliability of the SeKAPS was determined by 22 volunteer pianists. The other ten professional pianists and ten non-musicians were recruited to indicate the feasibility of the SeKAPS to distinguish the performing differences between groups. Results The R 2 values of regression analyses for the load cells were 0.993–0.999 ( p < 0.001), indicating high validity. The ICC values of the modified keys were 0.82–0.93, indicating high reliability. The results indicate that SeKAPS is accurate in detecting the striking force of digits during piano playing. Significant differences existed in the mean peak force and mean CVs of the peak force of the specific digits between the two groups. The results showed differences in finger control strategies between the pianists and non-musicians. Conclusion The SeKAPS may provide a valuable assessment for assisting pianists in understanding digit force control and movement strategies to achieve efficient digit coordination.

Investigation of the Artificial Saliva and Saline Droplet Size Measurement Accuracy for COVID-19 Infection Control - Thomas Y. Wu; Yi-Hung Liu; Fang-hsin Lin; Yue Liu; Junjie Liu; Jinsang Jung; Wesley Zongrong Yu; Qinde Liu; Richard Y. C. Shin; Tang Lin Teo (Aerosol Science and Engineering, 2023)

Occurrence, fate, and potential risk of pharmaceutical pollutants in agriculture: Challenges and environmentally friendly solutions - Minh-Ky Nguyen; Chitsan Lin; Hoang-Lam Nguyen; Nguyen Tri Quang Hung; D. Duong La; X. Hoan Nguyen; S. Woong Chang; W. Jin Chung; D. Duc Nguyen (Science of The Total Environment, 2023)

Acidic electrolyzed oxidizing water delayed the breakdown occurrence in pulp of fresh longan by regulating the metabolisms of respiratory and energy - Qingqing Liu; Huilin Xie; Yihui Chen; Mengshi Lin; Yen-Con Hung; Hui Wang; Zhongqi Fan; Yifen Lin; Hetong Lin (Postharvest Biology and Technology, 2023)

Plasma-engineered graphene quantum dot-based nanocomposites as smart CO2-philic membranes with extremely high separation performance - Yi-Jui Yeh; Wei Lin; Wei-Hung Chiang; Kuo-Lun Tung (Chemical Engineering Journal, 2023)

Graphene-based biomimetic array film for simultaneous fog water harvesting and wind power generation - Tsung Han Huang; Mu-Jie Shih; Yi-Yun Chen; Hannah Faye M. Austria; Owen Setiawan; Chunrui Wu; Xiaolong Lu; Lin Zhang; Wei-Song Hung (Chemical Engineering Journal, 2023)

Pinostrobin modulates FOXO3 expression, nuclear localization, and exerts antileukemic effects in AML cells and zebrafish xenografts - Pei-Yi Chen; Ching-Yen Lin; Chia-Ling Wu; Pei Ying Keak; Je-Wen Liou; Wan-Yun Gao; Liang-In Lin; Jui-Hung Yen (Chemico-Biological Interactions, 2023)

Monitoring and management of abandoned, lost and discarded fishing gear (ALDFG) in Penghu Islands, Taiwan - Wen-Hong Liu; Hung-An Chang; Hao-Tang Jhan; Chih-Cheng Lin; Li-Shu Chen; Chung-Lun Liu; Kuo-Huan Ting (Marine Pollution Bulletin, 2023)

Solar farm policy and farmland price – A land zoning perspective - Hung-Hao Chang; Tzu-Chin Lin (Journal of Environmental Management, 2023)

Photoelectrochemical degradation of TMAH by green synthesized silver modified titanate nanotube arrays - Wu-Xing Chen; Ku-Fan Chen; Ken-Ling Chang; Wei-Hsiang Chen; Chia-Hua Lin; Chia-Hung Chen; Ci-Yi Shih; Yi-Chun Chen; Yen-Ping Peng (Journal of Environmental Chemical Engineering, 2023)

Effects of ammonia on combustion of coal in stoichiometric premixed methane–air flames - Yueh-Heng Li; Bo-Cheng Chuang; Po-Hung Lin; Janusz Lasek (Fuel, 2023)

Long-term field calibration of low-cost metal oxide VOC sensor: Meteorological and interference gas effects - Gung-Hwa Hong; Thi-Cuc Le; Guan-Yu Lin; Hung-Wen Cheng; Jhih-Yuan Yu; Racha Dejchanchaiwong; Perapong Tekasakul; Chuen-Jinn Tsai (Atmospheric Environment, 2023)

Magnusiomyces Capitatus Lung Nodule in a Patient with Nasopharyngeal and Hepatocellular Carcinoma - Shih-Hao Lo; Hsin-Hui Wang; Ya-Ting Chang; Chih-Hung Lin; Po-Liang Lu; Shang-Yi Lin (Mycopathologia, 2023)

High-performance peptide and disulfide mapping by direct injection of intact proteins using on-line coupled UV-liquid chromatography microdroplet mass spectrometry (UVLC-MMS) - Chin-Ming Kuo; Hung-Hsiang Jen; Fung-Yu Chen; Mohsen Akbarian; Tai-Hong Ou; Kang-Yu Liu; Jung-Lee Lin; Shu-Hui Chen (Analytica Chimica Acta, 2023)

Enhanced biomethane production with a low carbon footprint via anaerobic co-digestion of swine wastewater with rice husk - Hung-Cheng Lin; Shu-Yuan Pan; Yu-I Lin; Dan-Thanh Ngoc Cao (Science of The Total Environment, 2023)

Application of water-saving irrigation and biostimulants on the agronomic performance of maize (Zea mays) - Cheng-Hsuan Chen; Kuan-Hung Lin; Yu-Sen Chang; Yu-Jie Chang (Process Safety and Environmental Protection, 2023)

Estimating the daily average concentration variations of PCDD/Fs in Taiwan using a novel Geo-AI based ensemble mixed spatial model - Chin-Yu Hsu; Tien-Wei Lin; Jennieveive B. Babaan; Aji Kusumaning Asri; Pei-Yi Wong; Kai-Hsien Chi; Tuan Hung Ngo; Yu-Hsuan Yang; Wen-Chi Pan; Chih-Da Wu (Journal of Hazardous Materials, 2023)

Maternal di-(2-ethylhexyl) phthalate exposure elicits offspring IFN-λ upregulation: Insights from birth cohort, murine model, and in vitro mechanistic analysis - Fu-Chen Kuo; Mei-Lan Tsai; Shin-Ting Wu; Sih-Syuan Li; Chia-Fang Wu; Shu-Lin Wang; Michael W.Y. Chan; Jau-Ling Suen; Ming-Tsang Wu; Chih-Hsing Hung (Food and Chemical Toxicology, 2023)

Temporal transition trends of cord blood lead levels in various human development index countries and in the Taipei metropolitan area - Yaw-Huei Hwang; Hui-Chu Wu; Ming-Kwang Shyu; Chien-Nan Lee; Shin-Yu Lin; Pau-Chung Chen; Hung-Yi Chuang; Pei-Wen Lin; Tso-Hsien Wu; Yen-Tzu Chen (Environmental Pollution, 2023)

Sublethal effects of methylmercury on lateral line sensory and ion-regulatory functions in zebrafish embryos - Giun-Yi Hung; Yu-Chin Pan; Jiun-Lin Horng; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Highly-specific aptamer targeting SARS-CoV-2 S1 protein screened on an automatic integrated microfluidic system for COVID-19 diagnosis - Hung-Bin Wu; Chih-Hung Wang; Yi-Da Chung; Yan-Shen Shan; Ying-Jun Lin; Huey-Pin Tsai; Gwo-Bin Lee (Analytica Chimica Acta, 2023)

Applying an air curtain to reduce surgical smoke concentration - Xuan-Huy Ninh; Hung-Yu Tzeng; Tak-Wah Wong; Yu-Ting Wu; Yao-Lung Kuo; Ming-Yeng Lin (Air Quality, Atmosphere & Health, 2023)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

Air pollution exacerbates mild obstructive sleep apnea by disrupting nocturnal changes in lower-limb body composition: a cross-sectional study conducted in urban northern Taiwan - Yansu He; Wen-Te Liu; Shang-Yang Lin; Zhiyuan Li; Hong Qiu; Steve Hung-Lam Yim; Hsiao-Chi Chuang; Kin Fai Ho (Science of The Total Environment, 2023)

A novel framework for spatiotemporal groundwater pumping process estimation based on data-driven approaches - Hwa-Lung Yu; Hua-Ting Tseng; Ying-Fan Lin; Chun-Hung Chen; Ying-Chang Kuo; Yun-Ta Cheng (Journal of Hydrology, 2023)

Dietary administration of a postbiotic, heat-killed Pediococcus pentosaceus PP4012 enhances growth performance, immune response and modulates intestinal microbiota of white shrimp, Penaeus vannamei - Rolissa Ballantyne; Jai-Wei Lee; Sz-Tsan Wang; Jin-Seng Lin; Deng-Yu Tseng; Yi-Chu Liao; Hsiao-Tung Chang; Ting-Yu Lee; Chun-Hung Liu (Fish & Shellfish Immunology, 2023)

Air quality health index (AQHI) based on multiple air pollutants and mortality risks in Taiwan: Construction and validation - Mu-Jean Chen; Yue Leon Guo; Pinpin Lin; Hung-Che Chiang; Pau-Chung Chen; Yu-Cheng Chen (Environmental Research, 2023)

Arsenic exposure associated with lung interstitial changes in non-smoking individuals living near a petrochemical complex: A repeated cross-sectional study - Chih-Wen Wang; Szu-Chia Chen; Da-Wei Wu; Hung-Hsun Lin; Huang‐Chi Chen; Chih-Hsing Hung; Chao-Hung Kuo (Environmental Pollution, 2023)

Livistona chinensis Water Extract has the Potential to Repair Thioacetamide-Induced Liver Fibrosis in Mice - San-Ho Hung; Tzu-Hsuan Hsu; Chun-Shien Wu; Yi-Ping Lin; Ching-Ting Wei; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2023)

Correction: Common Subtype of Small Renal Mass MR Imaging Characterisation: A Medical Center Experience in Taiwan - Ming-Cheng Liu; Yi-Jui Liu; Yen-Ting Lin; Siu-Wan Hung; Jyh-Wen Chai; Si-Wa Chan; Kun-Yuan Chiu; Ya-Ling Tsou (Journal of Medical and Biological Engineering, 2023)

Measuring the effects of typhoon trajectories on dengue outbreaks in tropical regions of Taiwan: 1998–2019 - Brian Kao; Chia-Hsien Lin; Tzai-Hung Wen (International Journal of Biometeorology, 2023)

Whole-Genome Sequencing of Pseudomonas koreensis Isolated from Diseased Tor tambroides - Cindy Jia Yung Kho; Melinda Mei Lin Lau; Hung Hui Chung; Ivy Yee Yen Chew; Han Ming Gan (Current Microbiology, 2023)

Body composition modify the association between ambient particulate matter and lung function among asthma patients - Fang-Chi Lin; Pei-Shih Chen; Yuan-Chung Lin; Meng-Chih Lin; Chao-Chien Wu; Kang-Shin Chen; Chien-Hung Lee; Tsu-Nai Wang (Environmental Science and Pollution Research, 2023)

Captive Reproductive Behavior, Spawning, and Early Development of White-Barred Goby Amblygobius phalaena (Valenciennes, 1837) and Examined Larval Survival and Viability at Different Water Temperatures and Salinities - Pei-Sheng Chiu; Shine-Wei Ho; Cheng-Hsuan Huang; Yen-Chun Lee; Yu-Hung Lin (Fishes, 2023)
White-barred goby Amblygobius phalaena is a highly valued marine ornamental fish, but its captive reproduction and early life history are poorly understood. In this study, the captive reproductive behavior, early development, and optimal temperature and salinity for the larval survival and viability of A. phalaena were investigated for the first time. Spawning occurred between 11:00 and 13:00, with the breeding pairs naturally spawning 24 times from 1 June 2021 to 30 June 2022. The fecundity ranged from 11,022 to 95,858 eggs per spawning event. Hatching occurred approximately 81 h and 26 min after fertilization at a temperature of 27.0 ± 0.9 °C. Newly hatched larvae had a total length (TL) of 1.91–2.03 mm with 24–26 somites. The larvae transformed into juveniles at 30 days post-hatch. Experiments were conducted at different temperatures (21, 24, 27, 30, and 33 °C) and salinities (18, 24, 30, and 36 ppt) to determine the optimal conditions for larval survival and viability. The results indicate that the most suitable conditions in terms of temperature were in the range of 21–27 °C and 30 ppt for salinity. These findings provide valuable insights for the future development of captive-breeding techniques and the commercial production of other marine ornamental gobies.

New ent -kaurene and germacrene derivatives from Mesona procumbens Hemseley and their biological activity - Jerome G. Ganzon; Chia-Ching Liaw; Yu-Chi Lin; Zhi-Hu Lin; Chang-Hung Wang; Che-Yi Chen; Kuo-Hsiang Chuang; Yao-Haur Kuo (Natural Product Research, 2023)

Estimating arsenic biotransfer factors from feed to chicken: a viable approach to animal feed risk assessment - Ching-Chi Hung; Hsin-Tang Lin; Ching-Yi Chen; Kuan-Yi Chen; Tsung-Yu Lee; Chow-Feng Chiang (Food Additives & Contaminants: Part A, 2023)

Estimating the effect of increasing ambient temperature on antimicrobial resistance in China: A nationwide ecological study with the difference-in-differences approach - Weibin Li; Chaojie Liu; Hung Chak Ho; Lin Shi; Yingchao Zeng; Xinyi Yang; Haohai Xia; Wangjian Zhang; Cunrui Huang; Lianping Yang (Science of The Total Environment, 2023)

Applicability of carbonate clumped isotope thermometry in the Tuchang-Jentse geothermal field - Yi-Chia Lu; Sheng-Rong Song; Ling-Wen Liu; Tsung-Ren Peng; Bill Bing-Cheng Chen; Remy Kai-Cheng Tu; Li-Hung Lin; Pei-Ling Wang (Geothermics, 2023)

Heavy metals in fish, rice, and human hair and health risk assessment in Wuhan city, central China - Muhammad Ubaid Ali; Chuan Wang; Yuan Li; Ruolan Li; Shaochen Yang; Li Ding; Lin Feng; Bo Wang; Ping Li; Ming Hung Wong (Environmental Pollution, 2023)

Ganglioside-focused Glycan Array Reveals Abnormal Anti-GD1b Auto-antibody in Plasma of Preclinical Huntington’s Disease - Tien-Wei Lin; Jung-Kai Chang; Yih-Ru Wu; Tsung-Hsien Sun; Yang-Yu Cheng; Chien-Tai Ren; Mei-Hung Pan; Jin-Lin Wu; Kuo-Hsuan Chang; Hwai-I Yang; Chiung-Mei Chen; Chung-Yi Wu; et al. (Molecular Neurobiology, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Influence of microclimate control on the growth of asparagus under greenhouse in tropical climates - Kuo-An Hung; Yi-Wei Hsu; Yu-Cheng Chen; Tzu-Ping Lin (International Journal of Biometeorology, 2023)

Dietary α-tocopherol acetate improved growth performance, lipid oxidative status, and disease resistance of hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) - Isabella Ebi; Annita Seok Kian Yong; Leong-Seng Lim; Yu Hung Lin; Rossita Shapawi (Fisheries Science, 2023)

Effect of functionalized nanodiamonds and surfactants mediation on the nanofiltration performance of polyamide thin-film nanocomposite membranes - T.M. Subrahmanya; Jing-Yang Lin; Januar Widakdo; Hannah Faye M. Austria; Owen-Setiawan; Yu-Hsuan Chiao; Tsung-Han Huang; Wei-Song Hung; Hideto Matsuyama; Kueir-Rarn Lee; Juin-Yih Lai (Desalination, 2023)

Improved bioremediation of PCDD/Fs contaminated soil by mycelium-free liquids induced by agro-industrial residues - Chih-Yu Cheng; Zhi-Feng Zhang; Acharee Kaewlaoyoong; Jing-Ting Huang; Nicholas Kiprotich Cheruiyot; Chitsan Lin; Hung-Chou Huang (Bioresource Technology Reports, 2023)

Application of vetiver grass (Vetiveria Zizanioides L.) for organic matter removal from contaminated surface water - Minh Ky Nguyen; Nguyen Tri Quang Hung; Cong Manh Nguyen; Chitsan Lin; Tuan Anh Nguyen; Hoang-Lam Nguyen (Bioresource Technology Reports, 2023)

Far-field Coupling and Interactions in Multiple Geospheres After the Tonga Volcano Eruptions - Chieh-Hung Chen; Yang-Yi Sun; Xuemin Zhang; Fei Wang; Kai Lin; Yongxin Gao; Chi-Chia Tang; Jun Lyu; Rong Huang; Qian Huang (Surveys in Geophysics, 2023)

Sialylation of cell surface glycoconjugates modulates cytosolic galectin-mediated responses upon organelle damage - I-Chun Weng; Hung-Lin Chen; Wei-Han Lin; Fu-Tong Liu (Glycoconjugate Journal, 2023)

Improving Aquaculture Water Quality Using Dual-Input Fuzzy Logic Control for Ammonia Nitrogen Management - Hung-Chih Li; Ker-Wei Yu; Chang-Hua Lien; Chitsan Lin; Cheng-Ruei Yu; Sundarapandian Vaidyanathan (Journal of Marine Science and Engineering, 2023)
In this paper, a closed-loop control system using dual-input fuzzy logic theory is proposed to improve the water quality of aquaculture. The new closed-loop control system is implemented on a Raspberry-Pi-embedded platform using Python programming. The proposed closed-loop control system integrates an RS485 function, a database transfer module, a simulating variable group function, and a trigger function import to achieve savings in human resources, power, and water consumption. The proposed closed-loop control system is equipped with an ammonia nitrogen sensor and solenoid valves for the water exchange. The experimental results demonstrate that the intelligent controller can rapidly eliminate ammonia nitrogen within the range of 2.0 ppm and maintain robust control in response to changes in ammonia nitrogen excretion from a school of fish. The experimental results provide insights into the relationship between tank capacity, water exchange solenoid valves, and ammonia nitrogen degradation time, which can be used to optimize aquaculture density and improve industrialization. The experimental results demonstrate that the savings for power and water can be achieved above 95%.

Blood lead (Pb) is associated with lung fibrotic changes in non-smokers living in the vicinity of petrochemical complex: a population-based study - Wei-Hoong Yau; Szu-Chia Chen; Da-Wei Wu; Huang-Chi Chen; Hung-Hsun Lin; Chih-Wen Wang; Chih-Hsing Hung; Chao-Hung Kuo (Environmental Science and Pollution Research, 2023)

Bisphenol C induces developmental defects in liver and intestine through mTOR signaling in zebrafish (Danio rerio) - Jinfeng Liu; Jiebo Lin; Jiafeng Chen; Yasen Maimaitiyiming; Kunhui Su; Siqi Sun; Guankai Zhan; Chih-Hung Hsu (Chemosphere, 2023)

Cadmium exposure induces histological damage and cytotoxicity in the cardiovascular system of mice - Shing-Hsien Chou; Hung-Chen Lin; Shao-Wei Chen; Yu-Ting Tai; Shih-Ming Jung; Fu-Hsiang Ko; Jong-Hwei Su Pang; Pao-Hsien Chu (Food and Chemical Toxicology, 2023)

Tidally-modulated stratification in a channel-shoal estuary - Chung-Hung Pao; Andhy Romdani; Jia-Lin Chen (Estuarine, Coastal and Shelf Science, 2023)

Response characteristics of an insertion tensiometer investigated via the vacuum saturation method - Yi Guo; Hung-Chou Lin; Jian-Bing Peng (CATENA, 2023)

A critical analysis of sources, pollution, and remediation of selenium, an emerging contaminant - Habib Ullah; Lu Lun; Audil Rashid; Noor Zada; Baoliang Chen; Asfandyar Shahab; Ping Li; Muhammad Ubaid Ali; Siyi Lin; Ming Hung Wong (Environmental Geochemistry and Health, 2023)

Genomic architecture underlying morphological and physiological adaptation to high elevation in a songbird - Chia‐Wei Lu; Shih‐Ting Huang; Shun‐Jen Cheng; Chen‐Tau Lin; Yu‐Cheng Hsu; Cheng‐Te Yao; Feng Dong; Chih‐Ming Hung; Hao‐Chih Kuo (Molecular Ecology, 2023)
Organisms often acquire physiological and morphological modifications to conquer ecological challenges when colonizing new environments which lead to their adaptive evolution. However, deciphering the genomic mechanism of ecological adaptation is difficult because ecological environments are often too complex for straightforward interpretation. Thus, we examined the adaptation of a widespread songbird—the rufous‐capped babbler ( Cyanoderma ruficeps )—to a relatively simple system: distinct environments across elevational gradients on the mountainous island of Taiwan. We focused on the genomic sequences of 43 birds from five populations to show that the Taiwan group split from its sister group in mainland China around 1–2 million years ago (Ma) and colonized the montane habitats of Taiwan at least twice around 0.03–0.22 Ma. The montane and lowland Taiwan populations diverged with gene flow between them, suggesting strong selection associated with different elevations. We found that the montane babblers had smaller beaks than the lowland ones, consistent with Allen's rule, and identified candidate genes— COL9A1 and SOX11 —underlying the beak size changes. We also found that altitudinally divergent mutations were mostly located in noncoding regions and tended to accumulate in chromosomal inversions and autosomes. The altitudinally divergent mutations might regulate genes related to haematopoietic, metabolic, immune, auditory and vision functions, as well as cerebrum morphology and plumage development. The results reveal the genomic bases of morphological and physiological adaptation in this species to the low temperature, hypoxia and high UV light environment at high elevation. These findings improve our understanding of how ecological adaptation drives population divergence from the perspective of genomic architecture.

Street-view and traditional greenness metrics with adults' sitting time in high-density living in Hong Kong: Comparing associations, air pollution and noise roles, and population heterogeneity - Ting Zhang; Bo Huang; Yizhen Yan; Yinyi Lin; Hung Wong; Samuel Yeung-shan Wong; Roger Yat-Nork Chung (Science of The Total Environment, 2023)

Toward sustainable inland aquaculture: Coastal subsidence monitoring in Taiwan - Wei-Chia Hung; Cheinway Hwang; Luigi Tosi; Shao-Hung Lin; Pei-Ching Tsai; Yi-An Chen; Wei-Ji Wang; En-Cheng Li; Sihao Ge (Remote Sensing Applications: Society and Environment, 2023)

Associations of residential greenness with unhealthy consumption behaviors: Evidence from high-density Hong Kong using street-view and conventional exposure metrics - Ting Zhang; Bo Huang; Yizhen Yan; Yinyi Lin; Hung Wong; Samuel Yeung-shan Wong; Roger Yat-Nork Chung (International Journal of Hygiene and Environmental Health, 2023)

Two-phase transition induced cation-disordered Li-reactive bi-metallic phosphides enabling high-performance Li-storage - Yanhong Li; Lei Zhang; Jianbin Deng; Hung-Yu Yen; Songliu Yuan; Jeng-Han Wang; Chunfu Lin; Meilin Liu; Wenwu Li (Chemical Engineering Journal, 2023)

The influence of seawater temperature on the timing of coral spawning - Che-Hung Lin; Yoko Nozawa (Coral Reefs, 2023)

Application of a Deep Neural Network for Acoustic Source Localization Inside a Cavitation Tunnel - Bo-Jie Lin; Pai-Chen Guan; Hung-Tang Chang; Hong-Wun Hsiao; Jung-Hsiang Lin (Journal of Marine Science and Engineering, 2023)
Navigating with low noise is the key capability in the submarine design considerations, and noise reduction is also one of the most critical issues in the related fields. Therefore, it is necessary to identify the source of noise during design stage to improve the survivability of the submarines. The main objective of this research is using the supervised neural network to construct the system of noise localization to identify noise source in the large acoustic tunnel. Firstly, we started our proposed method by improving the Yangzhou’s method and Shunsuke’s method. In the test results, we find that the errors of the both can be reduced by using the min-max normalization to highlight the data characteristics of the low amplitude in some frequency. And Yangzhou’s method has higher accuracy than Shunsuke’s method. Then, we reset the diagonal numbers of the cross spectral matrix in Yangzhou’s method to zero and replace mean absolute error to be the loss function for improving the stability of training, and get the most suitable neural network construction for our research. After our optimization, the error decreases from 0.315 m to 0.008 m in cuboid model test. Finally, we apply our method to the cavitation tunnel model. A total of 100 data sets were used for training, 10 sets for verification, and 5 for testing. The average error of the test result is 0.13 m. For the model test in cavitation tunnel in National Taiwan Ocean University, the length of ship model is around 7 m. And the average error is sufficient to determine the noise source position.

The effect of dietary lecithin and lipid levels on the growth performance, body composition, hemolymph parameters, immune responses, body texture, and gene expression of juvenile white shrimp (Litopenaeus vannamei) - Chyng-Hwa Liou; Vu-An To; Zhong-Fu Zhang; Yu-Hung Lin (Aquaculture, 2023)

Automated and continuous BIM-based life cycle carbon assessment for infrastructure design projects - Mudasir Hussain; Bowen Zheng; Hung-Lin Chi; Shu-Chien Hsu; Jieh-Haur Chen (Resources, Conservation and Recycling, 2023)

Acidic electrolyzed water treatment suppresses Phomopsis longanae Chi-induced the decreased storability and quality properties of fresh longans through modulating energy metabolism - Meiling Li; Qin Lin; Yazhen Chen; Yihui Chen; Mengshi Lin; Yen-Con Hung; Hetong Lin (Food Chemistry, 2023)

Investigation of ecological risk of microplastics in peatland areas: A case study in Vietnam - Minh Ky Nguyen; Chitsan Lin; Nguyen Tri Quang Hung; Hong-Giang Hoang; Dai-Viet N. Vo; Huu-Tuan Tran (Environmental Research, 2023)

Chemical investigations and cytotoxic effects of metabolites from Antrodia camphorata against human hepatocellular carcinoma cells - Yih-Fung Chen; Ho-Cheng Wu; Jia-Min Chang; Horng-Huey Ko; Chu-Hung Lin; Hsun-Shuo Chang (Natural Product Research, 2023)

Vitamin D regulates ion regulation by affecting the ionocyte differentiation in zebrafish (Danio rerio) larvae - Chia-Hao Lin; Hung-Chi Chang; Sian-Tai Liu; Huei-Jyun Hu (Frontiers in Marine Science, 2023)
Freshwater teleosts frequently face the stress of varied ion and pH levels; therefore, they have developed related defense mechanisms to maintain the homeostasis of body-fluid ion and acid-base balance. The different subtypes of ionocytes expressed in the branchial epithelium of adult fish or the skin of larvae are the major sites for fish ion regulation. 1α,25-dihydroxyvitamin D3 (1α,25(OH) 2 D 3 ), the bioactive form of vitamin D, is a steroid hormone that is involved in the regulation of Ca 2+ uptake and acid secretion in teleosts. Our results revealed that 1α,25(OH) 2 D 3 levels were not changed in zebrafish larvae upon exposure to low Na + freshwater compared to normal freshwater. In contrast, 1α,25(OH) 2 D 3 levels were substantially higher in fish exposed to acidic and low Ca 2+ freshwater than in those exposed to normal freshwater. Some hormones regulate ion regulation and acid secretion by modulating ionocyte differentiation and/or proliferation in teleosts; however, the role of vitamin D in this process is unclear. Zebrafish larvae were used as a model in the present study to explore the effect of vitamin D on ionocyte proliferation and/or differentiation. The present study indicated that 1α,25(OH) 2 D 3 treatment increased the number of foxi3a -positive cells, ionocyte progenitors, and mature ionocytes. However, the number of P63-positive epidermal stem cells did not change in the zebrafish larvae treated with 1α,25(OH) 2 D 3 . These results revealed that vitamin D exerts a positive effect on the number of ionocytes by increasing the differentiation of ionocytes. Increased ionocyte differentiation by vitamin D is suggested to elevate the capacity of ion regulation and acid secretion in zebrafish to cope with external stress. The present findings indicate the role of vitamin D in the regulation of ionocyte differentiation and provide new insights into the mechanisms of stress adaptation of fish.

A framework for the sustainable risk assessment of in-river hydraulic structures: A case study of Taiwan’s Daan River - Dong-Sin Shih; Shang-Shu Shih; Shaohua Marko Hsu; Shih-Yuan Lin; Yiching Lin; Chi-Tung Hung; Kai Wang (Journal of Hydrology, 2023)

In situ derived sulfated/sulfonated carbon nanogels with multi-protective effects against influenza a virus - Hung-Yun Lin; Ka-Long Luo; Ju-Yi Mao; Chin-Jung Lin; Chen-Yow Wang; Lauren Panny; Shiow-Yi Chen; Shih-Chao Lin; Chih-Ching Huang; Scott G. Harroun; Robert Y.L. Wang; Chang-Jer Wu (Chemical Engineering Journal, 2023)

Facile synthesis of spiro-core-based hole-transporting material for high-performance and stable perovskite solar cells - Kun-Mu Lee; Seid Yimer Abate; June Hung Yang; Wei-Hao Chiu; Seoungjun Ahn; Sie-Rong Li; Kang-Ling Liau; Yu-Tai Tao; Yan-Duo Lin (Chemical Engineering Journal, 2023)

Adopting abundant seawater as green chemical activators for preparing high surface area biochar - TsingHai Wang; Yu-Ching Lin; Ci-Jing Hung; Yasi Liao; Ruo-Xin Xu (Bioresource Technology Reports, 2023)

Editorial: Oceanographic processes linking nearshore, continental shelf, and shelf break - Feng-Hsun Chang; Yun-Chi Lin; Kuo-Ping Chiang; Ya-Han Nien; Chih-hao Hsieh; Wei-Jen Chen; Chin-Chang Hung; Toru Kobari; Hiroaki Saito; William Savidge (Frontiers in Marine Science, 2023)

Dynamic Co-Simulation Analysis and Control of an IEA 15 MW Offshore Floating Semi-Submersible Wind Turbine under Taiwan Offshore-Wind-Farm Conditions of Wind and Wave - Cherng-Jer Chueh; Chun-Hung Chien; Ching Lin; Ting-Yan Lin; Mao-Hsiung Chiang (Journal of Marine Science and Engineering, 2023)
This study aims to develop dynamic co-simulation and control for analyzing the IEA 15 MW semi-submersible floating wind turbine under Taiwan offshore-wind-farm conditions of wind and wave. The IEA 15 MW wind turbine is mounted on a UMaine VolturnUS-S reference platform with a mooring system designed for a water depth of 70 m, in this study. The dynamic co-simulation combines software of SIMPACK, MATLAB/SIMULINK, AeroDyn, HydroDyn, WAMIT, and MAP++ to achieve the complex dynamic simulation of aerodynamics, hydrodynamics, mechanism dynamics and control system dynamics. In addition, this study proposes a novel power-control strategy combining fuzzy sliding-mode control with additional pitching-rate feedback. Since the motion of the floating platform, especially the pitching motion, contributes to power oscillation, the proposed novel power-control strategy with additional pitching-rate feedback can reduce the influence of the floating-platform oscillation motion, and is verified under different conditions.

Assessing consumer perceptions of chemical leasing business models and possibilities for adoption by Taiwanese manufacturers - Chen-Fu Lu; Chia-Yi Cheng; Ying-Lin Hung (Sustainable Production and Consumption, 2023)

Comparative pulmonary toxicity assessment of tungsten trioxide and tungsten trioxide hydrate nanoparticles - Hsin Her Yu; Yi-Chun Chen; Han-Pang Su; Liliang Chen; Hung-Hsiang Chen; Kun-Yi Andrew Lin; Chia-Hua Lin (Science of The Total Environment, 2023)

Pod fossils of Albizia (Fabaceae: Caesalpinioideae) from the late Miocene of northern Vietnam and their phytogeographic history - Hung Ba Nguyen; Jian Huang; Truong Van Do; Gaurav Srivastava; Hoa Mai Thi Nguyen; Shu-Feng Li; Lin-Lin Chen; Minh Trung Nguyen; Hung Dinh Doan; Zhe-Kun Zhou; Tao Su (Review of Palaeobotany and Palynology, 2023)

Novel fast pesticides extraction (FaPEx) strategy coupled with UHPLC-MS/MS for rapid monitoring of emerging pollutant fipronil and its metabolite in food and environmental samples - Raghavendra Rao Pasupuleti; Yi-Jia Ku; Tseng-Yu Tsai; Hung-Ta Hua; Yu-Chia Lin; Jentaie Shiea; Po-Chin Huang; Gangadhar Andaluri; Vinoth Kumar Ponnusamy (Environmental Research, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Intimate interaction of TFSI− anions with MoO3−x oxygen vacancies boost ionic conductivity of cathode-supported solid polymer electrolyte - Rohan Paste; Chintam Hanmandlu; Po-Yu Su; Cheng-Hung Hou; Hsin-An Chen; Chun-Wei Pao; Jing-Jong Shyue; Kuei-Hsien Chen; Heng-Liang Wu; Hong-Cheu Lin; Chih Wei Chu (Chemical Engineering Journal, 2023)

Conducting an adaptive evaluation framework of importance and performance for community-based earthquake disaster management - Bih-Chuan Lin; Chun-Hung Lee (Natural Hazards, 2023)
The frequency and intensity of natural disasters have been increasing in recent decades; especially earthquakes are one of the causes of major natural disasters. Improving community adaptive response to disasters based on community capacity has gradually become an effective means of coping with disaster risks, as well as improving residents' well-being and community participation in disaster planning and management. We integrate community resilience and disaster management to establish an evaluation framework for community-based earthquake disaster management (CEDM) based on community perspectives under importance performance analysis method, and identify the factors affecting community adaptive behavior. Features that affect the differentiation of community residents' adaptive behavior in CEDM program are classified into risk perception, learning earthquake knowledge, the ability on earthquake prevention, and creating a platform on CEDM. The results identify that the CEDM has to integrate the higher community education plan, the stronger flexible to disaster preparedness, the higher the residents' awareness of disaster prevention, the stronger the ability to adapt to disasters; the higher the ability of the government and non-profit organizations to cooperate with the community to deal with disasters, and the stronger the community's ability to manage disasters. These findings provide valuable insights into the construction of CEDM systems and related policymaking.

Coexistence of the social semantic effect and non-semantic effect in the default mode network - Guangyao Zhang; Jinyi Hung; Nan Lin (Brain Structure and Function, 2023)

Defect inspection of indoor components in buildings using deep learning object detection and augmented reality - Shun-Hsiang Hsu; Ho-Tin Hung; Yu-Qi Lin; Chia-Ming Chang (Earthquake Engineering and Engineering Vibration, 2023)

Promoting human rights for Taiwan’s fishermen: Collaboration with the primary source countries of Taiwan’s DWF migrant fishermen - Po-Chih Hung; Hsiao-Chien Lee; Chih-Cheng Lin; Wen-Hong Liu (Frontiers in Marine Science, 2022)
Taiwan is one of the largest distant water fishing (DWF) nations worldwide, and relies largely on the migrant labor to keep costs low. However, this industry has caused Taiwan to be listed in the 2020 “List of Goods Produced by Child Labor or Forced Labor” of the U.S. Department of Labor. In view of this, the Taiwanese government is actively adopting further management measures to supervise the domestic and foreign fishermen agencies. It is because the latter has been involved in many disputes, especially in recruitment, payroll, and labor contracts, which directly or indirectly affect the rights of migrant fishermen. On the other hand, although the C188 Work in Fishing Convention has stregthend the protection of the fishermen’s human rights, it still stays ambiguous in terms of private agency management. That is also why so many disputes have been caused in recent years.This study conducts a comparative analysis of the agency management systems in the primary source countries of Taiwan’s distant water fishing migrant fishermen (that is, Indonesia, the Philippines, and Vietnam), as well as interviews with distant water fishing stakeholders to provide insights on the improvement of agency management and migrant fishermen’s rights in Taiwan. The findings imply that the positive interaction, mutual trust, and understanding of laws and regulations between fishermen’s exporting and importing countries lead to future cross-national collaboration. This study suggests that the Taiwanese government should follow the spirit of the C188 but not be restricted to the Convention texts to amend or formulate regulations and policies of agencies for fully protecting the rights of migrant fishermen.

Indigodole E from Strobilanthes cusia exhibits anti-IL-17A effect - Chia-Lin Lee; Chien-Ming Wang; Hung-Rong Yen; Ying-Chyi Song; Chao-Jung Chen (Natural Product Research, 2022)

Mesenchymal Stem Cell Secreted-Extracellular Vesicles are Involved in Chondrocyte Production and Reduce Adipogenesis during Stem Cell Differentiation - Yu-Chen Tsai; Tai-Shan Cheng; Hsiu-Jung Liao; Ming-Hsi Chuang; Hui-Ting Chen; Chun-Hung Chen; Kai-Ling Zhang; Chih-Hung Chang; Po-Cheng Lin; Chi-Ying F. Huang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Extracellular vesicles (EVs) are derived from internal cellular compartments, and have potential as a diagnostic and therapeutic tool in degenerative disease associated with aging. Mesenchymal stem cells (MSCs) have become a promising tool for functional EVs production. This study investigated the efficacy of EVs and its effect on differentiation capacity. Methods: The characteristics of MSCs were evaluated by flow cytometry and stem cell differentiation analysis, and a production mode of functional EVs was scaled from MSCs. The concentration and size of EVs were quantitated by Nanoparticle Tracking Analysis (NTA). Western blot analysis was used to assess the protein expression of exosome-specific markers. The effects of MSC-derived EVs were assessed by chondrogenic and adipogenic differentiation analyses and histological observation. Results: The range of the particle size of adipose-derived stem cells (ADSCs)- and Wharton’s jelly -MSCs-derived EVs were from 130 to 150 nm as measured by NTA, which showed positive expression of exosomal markers. The chondrogenic induction ability was weakened in the absence of EVs in vitro . Interestingly, after EV administration, type II collagen, a major component in the cartilage extracellular matrix, was upregulated compared to the EV-free condition. Moreover, EVs decreased the lipid accumulation rate during adipogenic induction. Conclusion: The results indicated that the production model could facilitate production of effective EVs and further demonstrated the role of MSC-derived EVs in cell differentiation. MSC-derived EVs could be successfully used in cell-free therapy to guide chondrogenic differentiation of ADSC for future clinical applications in cartilage regeneration.

In silico prediction of parkinsonian motor deficits-related neurotoxicants based on the adverse outcome pathway concept - Hung-Lin Kan; Chun-Wei Tung; Shao-En Chang; Ying-Chi Lin (Archives of Toxicology, 2022)

Biophysical controls on spatial and summer/winter distributions of total and chromophoric dissolved organic matter in the Taiwan Strait - Jia-Jang Hung; Wan-Tzu Lu; Hsin-Mei Yang; Yen-Hui Lin; Laodong Guo (Frontiers in Marine Science, 2022)
This study examined the physical and biogeochemical processes that determine the spatial and summer/winter distributions of dissolved organic matter (DOM) and chromophoric dissolved organic matter (CDOM) in the Taiwan Strait (TS). The hydrological conditions in the TS varied between early summer and winter because of differences in terrestrial input as well as input from the poleward South China Sea Water (SCSW) during the warm summer and the strong, nutrient-rich, equatorward China Coastal Water (CCW) in winter. Concentrations of dissolved organic carbon (DOC) ranged from 60 to 100 μM-C in early summer and from 70 to 144 μM-C in winter. The average stoichiometric ratio of DOC : DON:DOP was high (353:49:1) in the land-source impacted zones and low (168:21:1) in the SCSW-laden areas, both of which are higher than the Redfield ratio. The concentrations of DOC and nutrients were higher in the western TS (on the coast of China) than in the eastern TS (on the coast of Taiwan), and the highest concentrations were mostly found in the Minjiang River plume, reflecting the profound effects of freshwater input in early summer and CCW inflow in winter. The absorption and emission characteristics of the CDOM varied to a large extent with locations because of the mixing of the shelf water with different source waters. Although the absorption coefficient (a CDOM (325)) and fluorescence intensity of the terrestrial humic-like CDOM (Ft: Ex/Em= 260/400-460) were both strongly inversely correlated with salinity, as an optical tracer, Ft may be more effective than a CDOM (325) in examining the mixing among source waters, given that a CDOM (325) may be subject to various photobleaching effects in the TS. Ft was also significantly correlated with the concentrations of terrestrially derived nitrate and nitrite (N+N) and silicate. The results of factor analysis elucidated the complexity of the hydrological and biological processes that affect the distributions of DOM and CDOM in the TS.

Volatile organic compounds in ambient air of a major Asian port: spatiotemporal variation and source apportionment - Thi-Hieu Le; Chitsan Lin; Duy-Hieu Nguyen; Nicholas Kiprotich Cheruiyot; Chung-Shin Yuan; Chung-Hsuang Hung (Environmental Science and Pollution Research, 2022)

Evaluating the Effect of Anisotropy on Hydraulic Stimulation in a Slate Geothermal Reservoir - Meng-Chia Weng; Po-Lin Wu; Chih-Hung Fang; Yu-Yao Fu; Yen-Che Liao; Chih-Hsi Liu (Rock Mechanics and Rock Engineering, 2022)

Physical Mechanism for Seabed Scouring around a Breakwater—A Case Study in Mailiao Port - I-Fan Tseng; Chih-Hung Hsu; Po-Hung Yeh; Ting-Chieh Lin (Journal of Marine Science and Engineering, 2022)
According to a field survey in 2012, the bathymetry near Mailiao Port, located in central Taiwan’s west coast, has a scouring hole that extends approximately 500 m × 100 m with a maximum scour depth of 26 m (eroded from its design depth −22 m to −48 m). To investigate the scour mechanism near the breakwater head and prevent the breakwater from collapsing, this study conducts comprehensive analysis by analyzing field observed data, performing hydraulic model tests, and conducting numerical modeling for the area near the Mailiao Port. The results show that the current plays an important role in the scour process. The physical model tests and numerical simulations both can reproduce the scour phenomenon of the study site. By analyzing field observed data we validated through physical and numerical models. This study concludes that the current caused by the ebb and flood tide, as well as the steep and shallow seabed topography, together comprise the seabed scour mechanism near the Mailiao Port breakwater head.

Biomechanical Analysis of Mandibular Implant-Assisted Removable Partial Denture with Distal Extension - Yung-Chung Chen; Chi-Lun Lin; Chen-Han Yu; Hung-Chih Chang; Yang-Ming Lin; Jia-Wei Lin (Journal of Medical and Biological Engineering, 2022)

Nanoencapsulation of Tea Catechins for Enhancing Skin Absorption and Therapeutic Efficacy - Ibrahim A. Aljuffali; Chih-Hung Lin; Shih-Chun Yang; Ahmed Alalaiwe; Jia-You Fang (AAPS PharmSciTech, 2022)

Correction to: Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Preliminary establishment of a mass movement warning system for Taiwan using the soil water index - Chi-Wen Chen; Ching Hung; Guan-Wei Lin; Jun-Jih Liou; Shih-Yao Lin; Hsin-Chi Li; Yung-Ming Chen; Hongey Chen (Landslides, 2022)

High Levels of 25-OH-Vitamin D and Copper in Pregnant Women with Abnormal Glucose Challenge Test - Chien-Hua Chiang; Wan-Ju Kung; Chien-Hung Lee; Yeong-Hwa Zen; Cheng-Fa Lee; Hui-Ru Yang; Ching-Chiang Lin; Yeou-Lih Huang (Biological Trace Element Research, 2022)

Integrated small RNA profiling and degradome analysis of Anthurium andraeanum cultivars with different-colored spathes - Fazhuang Lin; Shi-Peng Chen; Kuan-Hung Lin; Changming Chen; Fengqin Yao; Linshan Zhong; Weiting Chen; Yun-Wei Kuo (Journal of Plant Research, 2022)

Estrogenic and anti-neutrophilic inflammatory phenanthrenes from Juncus effusus L. - Hao-Chun Hu; Yi-Hong Tsai; Yu-Che Chuang; Kuei-Hung Lai; Yu-Ming Hsu; Tsong-Long Hwang; Chih-Chan Lin; Ferenc Fülöp; Yang-Chang Wu; Szu-Yin Yu; Yu-Ting Kuo; Fang-Rong Chang (Natural Product Research, 2022)

Characterization of chemical constituents with their antioxidant and anti-melanogenesis activities from the roots of Ampelopsis japonica - Chia-Lin Lee; Yun-Lian Jhan; Hsiu-Mei Chiang; Yi-Hung Chen; Chao-Jung Chen; Yuan-Shiun Chang (Natural Product Research, 2022)

Activation of Neuropeptide Y2 Receptor Can Inhibit Global Cerebral Ischemia-Induced Brain Injury - Reggie Hui-Chao Lee; Celeste Yin-Chieh Wu; Cristiane T. Citadin; Alexandre Couto e Silva; Harlee E. Possoit; Garrett A. Clemons; Christina H. Acosta; Victoria A. de la Llama; Jake T. Neumann; Hung Wen Lin (NeuroMolecular Medicine, 2022)

Evaluation of PET List Data-Driven Gated Motion Correction Technique Applied in Lung Tumors - Yi-Lun Chen; Bang-Hung Yang; I.-Ling Shih; Ko-Han Lin (Journal of Medical and Biological Engineering, 2022)

Long-term exercise pre-training attenuates Alzheimer’s disease–related pathology in a transgenic rat model of Alzheimer’s disease - Luodan Yang; Chongyun Wu; Yong Li; Yan Dong; Celeste Yin-Chieh Wu; Reggie Hui-Chao Lee; Darrell W. Brann; Hung Wen Lin; Quanguang Zhang (GeroScience, 2022)

The optimal combination of Nile red identification, colony polymerase chain reaction, and gas chromatography detection methods in screening for polyhydroxyalkanoicate-producing bacteria - Hung-Che Chou; Chia-Hsin Chen; Hsiao-Kai Chu; Chun-Mei Huang; Hui-Jun Wang; Wei-Lin Tu; Gia-Luen Guo (Archives of Microbiology, 2022)

Functional connections between bird eggshell stiffness and nest characteristics through risk of egg collision in nests - Chih‐Ming Hung; Shu‐Han Tsao; Pei‐Lin Chiang; Shang‐Ping Wu; Mao‐Ning Tuanmu; Jia‐Yang Juang (Ecology Letters, 2022)
Eggs and nests are two critical traits for the ecological success of birds. Their functional interactions, however, remain unclear. Here, we examined the functional connections between egg stiffness and nest attachment, site and structure for 1350 avian species. We revealed high eggshell stiffness for eggs in nests with a pensile attachment, located on non‐tree vegetation or having a domed shape, suggesting that birds produce stiffer eggs in response to higher egg‐collision risk in unstable or enclosed nests. Interdependence models suggested that the evolution of eggshell stiffness was more likely to be driven by than drive that of nest characters. Our results implied a trade‐off between investment in competing for established nesting niches and producing stiff eggs to explore novel niches with high collision risk, possibly mediated by predation or thermoregulation. This study highlights an overlooked connection between nests and eggshells that may have broadened the ecological niches of birds.

Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Growth Promotion and Salt-Tolerance Improvement of Gerbera jamesonii by Root Colonization of Piriformospora indica - Weiting Chen; Fazhuang Lin; Kuan-Hung Lin; Changming Chen; Chaoshui Xia; Qiaoling Liao; Shi-Peng Chen; Yun-Wei Kuo (Journal of Plant Growth Regulation, 2022)

Composition, Demographic History, and Population Structures of Trichiurus - Kui-Ching Hsu; Mu-Rong Yi; Sui Gu; Xiong-Bo He; Zhi-Sen Luo; Bin Kang; Hung-Du Lin; Yun-Rong Yan (Frontiers in Marine Science, 2022)
Sequences of the complete mitochondrial cytochrome oxidase subunit I gene were used to identify Trichiurus species and examine their population genetic structure and demographic history along the coast of China. Three Trichiurus species were found. Trichiurus japonicus lives in colder waters along the continental shelves in the China Seas, while Trichiurus nanhaiensis lives warmer waters along continental slopes in the South China Sea, and Trichiurus brevis lives in shallow and warmer waters in the South China Sea. The migrations of these species were mainly associated with feeding and spawning preferences. Two major wintering and spawning grounds in the East China Sea and South China Sea were found. All species showed a lack of population genetic structure resulting from their oceanodromous life cycle (the degree of population substructure index N ST = 0.000–0.149), but the results of approximate Bayesian computational approaches suggested population declines or stabilization and differentiation. The results of the T MRCA (time to the most recent common ancestor) showed that during glaciations, the Yellow Sea and the East China Sea were completely exposed, and the South China Sea acted as a refugium. Thus, the populations of these three species experienced differentiation during glaciations. This study also examined the limitations of Bayesian skyline plot analysis.

Biomechanical superiority of locking plate designed with cluster of head screws compared to conventional buttress plate for fixation of posteromedial tibial plateau fractures: A computational assessment - Kai-Cheng Lin; Yih-Wen Tarng; Kun-Jhih Lin; Hung-Wen Wei (Journal of Medical and Biological Engineering, 2022)

Probiotics and their Metabolites Reduce Oxidative Stress in Middle-Aged Mice - Wen-Yang Lin; Jia-Hung Lin; Yi-Wei Kuo; Pei-Fang Rose Chiang; Hsieh-Hsun Ho (Current Microbiology, 2022)
Aging is an irreversible physiological degradation of living organisms. Accumulated oxidative stress and dysbiosis accelerate aging. Probiotics such as Lactobacillus and Bifidobacterium and their fermented metabolites (postbiotics) have been discovered to exhibit antioxidative activities that regulate oxidative stress and protect cells from oxidative damage. We screened selected Lactobacillus and Bifidobacterium strains and their postbiotics for potential antioxidative activity by using DPPH (2,2-Diphenyl-1-picrylhydrazyl) assay. Strains with their metabolites were selected for mixed formula in experiments involving aging mice. The aged groups presented higher oxidative stress in the brain, liver, heart, and kidney than did young mice. However, treatment with probiotic strains and their postbiotics elevated antioxidative levels, especially in the high-dose probiotics plus postbiotics group. Next-generation sequencing data revealed positive microbiota alterations of Lactobacillus and Bifidobacterium and Akkermansia in the gut. Lactobacillus johnsonii and Akkermansia muciniphila exhibited effective enlargement of relative abundance. Besides, high-dose probiotics and high-dose probiotics plus postbiotics showed significant elevation in serum SCFAs, especially in butyrate. In conclusion, the formula containing Bifidobacterium animalis subsp. infantis BLI-02, Bifidobacterium breve Bv889, Bifidobacterium bifidum VDD088, B. animalis subsp. lactis CP-9, and Lactobacillus plantarum PL-02 and their metabolites may benefit aged people’s health.

Potential Plasticity of Artificial Feed Preference in Juvenile Pharaoh Cuttlefish (Sepia pharaonis) Through Progressive Training Programs - Chia-Huan Ma; Chih-Hung Lin; Yung-Cheng Chang; Hung-Tai Lee; Chyng-Hwa Liou; Te-Hua Hsu (Frontiers in Marine Science, 2022)
The cuttlefish is a commercially important marine species across the world; however, due to the lack of appropriate artificial feed, there is limited future aquaculture development of the cuttlefish. We proposed a novel process comprising (1) feed preference tests and (2) progressive training programs. Through this process, artificial diets can become more suitable for pharaoh cuttlefish ( Sepia pharaonis ). Feed preference tests (based on vision, touch, and smell) revealed that pharaoh cuttlefish preferred rod-shaped feed to flat rod-shaped or ball-shaped feed, moist feed over dry feed (DF), and DF with agar coating to DF without agar coating. Without olfactory training, some cuttlefish refused to eat artificial feed and eventually died. Through progressive training programs (3- and 6-week programs), a survival rate of >80% was achieved. Although the artificial diets examined in this study resulted in a lower conversion ratio for S. pharaonis than for fresh shrimp, available artificial feed can potentially be adopted for cuttlefish aquaculture through the use of our progressive training program.

Spatiotemporal distribution and the passive dispersal of fungal spores through HVAC systems - Wan-Rou Lin; Yung-Hung Ho; Wai Kwan Lee; Hsuan-Min Cheng; Pi-Han Wang (Aerobiologia, 2022)

Review and Future Perspective of Geophysical Methods Applied in Nearshore Site Characterization - Chia-Cheng Tsai; Chun-Hung Lin (Journal of Marine Science and Engineering, 2022)
Seabed surveying is the basis of engineering development in shallow waters. At present, geophysical survey methods mainly utilize sonars for qualitative surveying, which requires the calibration of the results found through in situ drilling and sampling. Among them, the parameters required for engineering designs are obtained from either in situ tests or laboratory experiments of soil samples retrieved from drilling. However, the experience from onshore applications shows that the physical quantities obtained through quantitative geophysical survey methods for shallow waters can be indirectly used to estimate engineering parameters or directly as parameters for engineering evaluation, which has high application potential. This review analyzes various geophysical survey methods for nearshore site characterization (i.e., side-scan sonar, single/multi- beam sonar, sub-bottom profiler, seismic reflection method, and underwater magnetometer) and challenges in their application, and introduces quantitative geophysical survey methods (including the underwater seismic refraction method, seismic surface wave method and underwater electrical resistivity tomography) that are worth focusing on for future development. Three application difficulties have been identified, namely, the lack of operational efficiency, appropriate operational equipment and systems, and sufficient guidance for experimental shallow sea applications. It is hoped that comprehensive discussion of these challenges will increase awareness leading to engineering improvements in the surveying and measuring capabilities in shallow waters, further reducing the risk of geotechnical hazards.

Bacterial Communities in Coral Offspring Vary Between in situ and ex situ Spawning Environments - Jia-Ho Shiu; Che-Hung Lin; Aziz Jabir Mulla; Viet Do Hung Dang; Chia-Ling Fong; Yoko Nozawa (Frontiers in Marine Science, 2022)
Examining the bacterial communities of offspring is key to understanding the establishment of coral-bacteria associations. Although high sensitivity to the environment is expected, previous studies have only examined bacterial communities of coral offspring in ex situ (laboratory) environments, not in in situ (field) environments. Here, we examined and compared the effect of ex situ and in situ environments on bacterial communities of newly released offspring (eggs and larvae) and their maternal colonies in two phylogenetically distant coral species with different reproductive modes: Dipsastraea speciosa (Scleractinia; spawner) and Heliopora coerulea (Octocorallia; brooder). Our results demonstrated that the spawning environments do not affect the bacterial composition in maternal colonies, but influence that of the offspring (eggs of D. speciosa and larvae of H. coerulea ). Dominant bacterial operational taxonomic units (OTUs) varied between in situ and ex situ environments in the eggs of D. speciosa . The composition of bacterial communities among larvae of H. coerulea samples was more diverse in in situ environments than in ex situ environments. This study provides the first information on in situ bacterial communities in coral eggs and larvae and highlights their sensitivities to the local environment. Future studies must take into consideration the influence of ex situ environments on bacterial communities in coral offspring.

Pollution characteristics, mechanism of toxicity and health effects of the ultrafine particles in the indoor environment: Current status and future perspectives - Muhammad Ubaid Ali; Siyi Lin; Balal Yousaf; Qumber Abbas; Mehr Ahmed Mujtaba Munir; Audil Rashid; Chunmiao Zheng; Xingxing Kuang; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2022)

L-Theanine Ameliorated Rotenone-Induced Parkinsonism-like Symptoms in Rats - Cheng-Neng Chen; Mao-Hsien Wang; Hung-Sheng Soung; Shu-Mei Chen; Chih-Hsiang Fang; Yi-Wen Lin; Hsiang-Chien Tseng (Neurotoxicity Research, 2022)

Common Subtype of Small Renal Mass MR Imaging Characterisation: A Medical Center Experience in Taiwan - Ming-Cheng Liu; Yi-Jui Liu; Yen-Ting Lin; Siu-Wan Hung; Jyh-Wen Chai; Si-Wa Chan; Kun-Yuan Chiu; Ya-Ling Tsou (Journal of Medical and Biological Engineering, 2022)
Purpose Many studies have shown that multiparametric magnetic resonance imaging (MRI) may be helpful for differentiating malignant renal cell carcinomas (RCCs) from benign lesions. However, the key imaging characteristics that differ between malignant and benign tumors still require further discussion. Methods We analyzed 60 adult patients diagnosed with 72 small renal masses (SRMs) who received preoperative MRI from 2014 to 2019 at a hospital in Taiwan. The MRI features included conventional MRI parameters, diffusion-weighted imaging (DWI) data, and dynamic contrast-enhanced (DCE) patterns, which were documented and compared among the four common subtypes: clear cell RCC (ccRCC), papillary RCC (pRCC), angiomyolipoma (AML) and other types of RCC. The apparent diffusion coefficient (ADC) values of high- and low-grade RCCs were also analyzed. Results The results show that ccRCC had higher T2-weighted signal intensity than the other three subgroups, a higher arterial wash-in index (AWI) and ADC value than AML and pRCC, and manifested a plateau ( n = 9, 25%) or washout (n = 27, 75%) enhancement pattern. AMLs exhibited more intravoxel fat than the other three subtype groups, and half of the AMLs (6 in 12) contained bulk fat. pRCC demonstrated a more progressive (n = 3, 60%) enhancement pattern than the other three subgroups. The ADC value of high-grade RCCs was significantly lower than that of low-grade RCCs. Conclusion These findings may indicate that multiparametric MRI is useful in differentiating among four common pathological types of SRMs, and the ADC value may be helpful in evaluating the histological grade of malignancy.

Intramyocardial injection of human adipose-derived stem cells ameliorates cognitive deficit by regulating oxidative stress–mediated hippocampal damage after myocardial infarction - Tsung-Ming LEE; Cheng-Che LEE; Horng-Jyh HARN; Tzyy-Wen Chiou; Ming-Hsi CHUANG; Chun-Hung CHEN; Chi-Hsuan CHUANG; Po-Cheng LIN; Shinn-Zong LIN (Journal of Molecular Medicine, 2021)
Cognitive impairment is a serious side effect of post-myocardial infarction (MI) course. We have recently demonstrated that human adipose-derived stem cells (hADSCs) ameliorated myocardial injury after MI by attenuating reactive oxygen species (ROS) levels. Here, we studied whether the beneficial effects of intramyocardial hADSC transplantation can extend to the brain and how they may attenuate cognitive dysfunction via modulating ROS after MI. After coronary ligation, male Wistar rats were randomized via an intramyocardial route to receive either vehicle, hADSC transplantation (1 × 10 6 cells), or the combination of hADSCs and 3-Morpholinosydnonimine (SIN-1, a peroxynitrite donor). Whether hADSCs migrated into the hippocampus was assessed by using human-specific primers in qPCR reactions. Passive avoidance test was used to assess cognitive performance. Postinfarction was associated with increased oxidative stress in the myocardium, circulation, and hippocampus. This was coupled with decreased numbers of dendritic spines as well as a significant downregulation of synaptic plasticity consisting of synaptophysin and PSD95. Step-through latency during passive avoidance test was impaired in vehicle-treated rats after MI. Intramyocardial hADSC injection exerted therapeutic benefits in improving cardiac function and cognitive impairment. None of hADSCs was detected in rat’s hippocampus at the 3rd day after intramyocardial injection. The beneficial effects of hADSCs on MI-induced histological and cognitive changes were abolished after adding SIN-1. MI-induced ROS attacked the hippocampus to induce neurodegeneration, resulting in cognitive deficit. The remotely intramyocardial administration of hADSCs has the capacity of improved synaptic neuroplasticity in the hippocampus mediated by ROS, not the cell engraftment, after MI. Key messages Human adipose-derived stem cells (hADSCs) ameliorated injury after myocardial infarction by attenuating reactive oxygen species (ROS) levels. Intramyocardial administration of hADSCs remotely exerted therapeutic benefits in improving cognitive impairment after myocardial infarction. The improved synaptic neuroplasticity in the hippocampus was mediated by hADSC-inhibiting ROS, not by the stem cell engraftment.

Measuring Heterogeneity in 18F-Fluorodeoxyglucose Positron Emission Tomography Images for Classifying Metastatic and Benign Bone Lesions in Patients with Cervical Cancer - Feng-Yuan Liu; Gigin Lin; Jing-Ren Tseng; Angel Chao; Huei-Jean Huang; Hung-Hsueh Chou; Yu-Chen Chang; Tzu-Chen Yen; Chyong-Huey Lai (Journal of Medical and Biological Engineering, 2021)
Purpose Heterogeneity assessment can be applied for medical imaging analysis. Here, we evaluated first-order and texture analysis (TA) metrics in 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET) imaging for classification of metastatic and benign bone lesions in patients with cervical cancer. Methods The data of 18 F-FDG PET studies performed on a specific PET/CT system from 2016 to 2018 in patients with cervical cancer were retrieved. The data of bone lesions extracted from studies over 2016–2017 and 2018 were used as training and validation datasets, respectively. Metastatic bone lesions were identified in each dataset, with an equal number of benign bone lesions selected. Cuboid volume of interest (VOI) consisting of 3 × 3 × 5 reconstructed voxels was applied for first-order metrics, and cubic VOI consisting of smaller voxels with trilinear interpolation of standardized uptake value (SUV) was adopted for TA metrics. First-order metrics included the maximum SUV (SUVmax) of lesions and the mean voxel SUV and its standard deviation (SUVsd), skewness, and kurtosis in VOI. In total, 4464 TA metrics based on 62 texture features were evaluated. Logistic regression was used for classification with area under the receiver operating characteristic curve (AUC) as the performance measure. Results From the training and validation datasets, 98 and 42 metastatic bone lesions were identified, respectively. SUVsd demonstrated higher performance than did SUVmax in both the training (AUC .798 vs .732, P = .001) and validation (AUC .786 vs .684, P < .001) datasets. Top-performing TA metrics demonstrated significantly higher performance in the training dataset, but not in the validation dataset. Conclusion A simple first-order measure of heterogeneity, SUVsd, was found to be superior to SUVmax for the classification of metastatic and benign bone lesions. Multiple hypothesis testing can result in false-positive findings in TA with multiple features and parameters; careful validation is required.

Association between exposure to road traffic noise and hearing impairment: a case-control study - Tang-Chuan Wang; Ta-Yuan Chang; Richard S. Tyler; Bing-Fang Hwang; Yi-Hung Chen; Che-Ming Wu; Chiu-Shong Liu; Kuang-Chao Chen; Chia-Der Lin; Ming-Hsui Tsai (Journal of Environmental Health Science and Engineering, 2021)

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Vagus nerve stimulation in pediatric patients with failed epilepsy surgery - Jeng-Dau Tsai; Pi-Chuan Fan; Wang-Tso Lee; Pi-Lien Hung; Kun-Long Hung; Huei-Shyong Wang; Kuang-Lin Lin (Acta Neurologica Belgica, 2021)

Image Segmentation in 3D Brachytherapy Using Convolutional LSTM - Jui-Hung Chang; Kai-Hsiang Lin; Ti-Hao Wang; Yu-Kai Zhou; Pau-Choo Chung (Journal of Medical and Biological Engineering, 2021)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

Anti-Inflammatory and anti-proliferative oleanane-type triterpene glycosides from the vine of Momordica cochinchinensis - Hung-Tse Huang; Yu-Chi Lin; Li-Jie Zhang; Chia-Ching Liaw; Hsin-Yen Chen; Ming-Tung Hsueh; Yao-Haur Kuo (Natural Product Research, 2021)

Association Between Estuary Characteristics and Activities of the Critically Endangered Indo-Pacific Humpback Dolphin (Sousa chinensis) - Chi-hung Lin; Hsing-Juh Lin; Jian-Ping Suen; Lien-Siang Chou (Frontiers in Marine Science, 2021)
The Indo-Pacific humpback dolphin ( Sousa chinensis ) has been reported to prefer estuary habitats. This study explored the environmental factors affecting a critically endangered population off the coast of Yunlin, Taiwan. We measured dolphin sighting rates and estuary characteristics affected by the watershed, including seven physical factors (watershed rainfall, watershed runoff, estuarine turbidity, pH, salinity, temperature, and dissolved oxygen) and two biological factors (estuarine net primary production and chlorophyll a concentration), at the Hsinhuwei River estuary in Taiwan. Dolphin activity was measured by sighting rate and behavioral indices for feeding and traveling between 2017 and 2018. We observed that when the maximum net production increased alongside rising temperatures in spring, both the dolphin sighting rate and foraging activity increased. This trend was maintained until heavy rainfall or increased river runoff occurred during late summer, which resulted in high turbidity in autumn and winter. Turbidity was significantly negatively correlated with dolphin activity (sighting rate and foraging). Furthermore, we found that dolphin traveling positively correlated with the chlorophyll a concentration and maximum net production factors, which could attract dolphins expecting more abundant prey fish in the estuary supported by the high primary production. This study provides empirical evidence on how estuary characteristics affected by the watershed can affect the sighting rate and behavioral activities of Indo-Pacific humpback dolphins.

Overexpression of Cell-Surface Marker SLC16A1 Shortened Survival in Human High-Grade Gliomas - Hong-Han Lin; Wen-Chiuan Tsai; Chia-Kuang Tsai; Ssu-Han Chen; Li-Chun Huang; Dueng-Yuan Hueng; Kuang-Chen Hung (Journal of Molecular Neuroscience, 2021)

Advantage of Multi-Directional Stability of Spiral Clavicle Plate in Treatment of Middle One-Third Clavicle Fracture: A Finite Element Study - Dan-Kai Wu; Wen-Chuan Chen; Kun-Jhih Lin; Cheng-Lun Tsai; Kang-Ping Lin; Hung-Wen Wei (Journal of Medical and Biological Engineering, 2021)

Photo-movement of coral larvae influences vertical positioning in the ocean - Aziz J. Mulla; Che-Hung Lin; Shunichi Takahashi; Yoko Nozawa (Coral Reefs, 2021)

Spontaneous thought-related network connectivity predicts sertraline effect on major depressive disorder - Li-Ming Hsu; Timothy Joseph Lane; Changwei W. Wu; Chien-Yuan Lin; Chi-Bin Yeh; Hung-Wen Kao; Ching-Po Lin (Brain Imaging and Behavior, 2021)

A Review on the Emerging Asian Aquaculture Fish, the Malaysian Mahseer (Tor tambroides): Current Status and the Way Forward - Melinda Mei Lin Lau; Leonard Whye Kit Lim; Sairatul Dahlianis Ishak; Ambok Bolong Abol-Munafi; Hung Hui Chung (Proceedings of the Zoological Society, 2021)

Naringin Ameliorates Haloperidol-Induced Neurotoxicity and Orofacial Dyskinesia in a Rat Model of Human Tardive Dyskinesia - Mao-Hsien Wang; Chih-Chuan Yang; Hsiang-Chien Tseng; Chih-Hsiang Fang; Yi-Wen Lin; Hung-Sheng Soung (Neurotoxicity Research, 2021)

Differences in immunity between pathogen-resistant and -susceptible yam cultivars reveal insights into disease prevention underlying ethylene supplementation - Shumei Hua; Zhihua Chen; Lihong Li; Kuan-Hung Lin; Yangwen Zhang; Jieyu Yang; Shi-Peng Chen (Journal of Plant Biochemistry and Biotechnology, 2021)

Effect of dermal phthalate levels on lung function tests in residential area near a petrochemical complex - Chih-Wen Wang; Szu-Chia Chen; Da-Wei Wu; Huang-Chi Chen; Hung-Hsun Lin; Hung Su; Jen-taie Shiea; Wen-Yi Lin; Chih-Hsing Hung; Chao-Hung Kuo (Environmental Science and Pollution Research, 2021)

Emission sources and full spectrum of health impacts of black carbon associated polycyclic aromatic hydrocarbons (PAHs) in urban environment: A review - Muhammad Ubaid Ali; Lin Siyi; Balal Yousaf; Qumber Abbas; Rashida Hameed; Chunmiao Zheng; Xingxing Kuang; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2021)

Influence of different fluidization and gasification parameters on syngas composition and heavy metal retention in a two-stage fluidized bed gasification process - Jia-Hong Kuo; Chiou-Liang Lin; Chang-Yu Ho; Jia-Chi Hung (Environmental Science and Pollution Research, 2021)

EndoPil: A Magnetically Actuated Swallowable Capsule for Weight Management: Development and Trials - Phuoc Thien Phan; Anthony Meng Huat Tiong; Muneaki Miyasaka; Lin Cao; Hung Leng Kaan; Khek Yu Ho; Soo Jay Phee (Annals of Biomedical Engineering, 2021)

Effects of plant growth regulators and polyamines on bract longevity in Bougainvillea buttiana - Kuan-Hung Lin; Jui-Mei Li; Chun-Wei Wu; Yu-Sen Chang (Horticulture, Environment, and Biotechnology, 2021)

Improving long-baseline rapid GPS time transfers by a modified common-view method - Wen-Hung Tseng; Shinn-Yan Lin (GPS Solutions, 2021)

The Effect of Wave-Induced Current and Coastal Structure on Sediment Transport at the Zengwen River Mouth - Chun-Hung Pao; Jia-Lin Chen; Shih-Feng Su; Yu-Ching Huang; Wen-Hsin Huang; Chien-Hung Kuo (Journal of Marine Science and Engineering, 2021)
The mechanisms that control estuarine sediment transport are complicated due to the interaction between riverine flows, tidal currents, waves, and wave-driven currents. In the past decade, severe seabed erosion and shoreline retreat along the sandy coast of western Taiwan have raised concerns regarding the sustainability of coastal structures. In this study, ADCPs (Acoustic Doppler Current Profiler) and turbidity meters were deployed at the mouth of the Zengwen river to obtain the time series and the spatial distribution of flow velocities and turbidity during the base flow and flood conditions. A nearshore circulation model, SHORECIRC, has been adapted into a hybrid finite-difference/finite-volume, TVD (Total Variation Diminishing)-type scheme and coupled with the wave-spectrum model Simulating Waves Nearshore (SWAN). Conventional finite-difference schemes often produce unphysical oscillations when modeling coastal processes with abrupt bathymetric changes at river mouths. In contrast, the TVD-type finite volume scheme allows for robust treatment of discontinuities through the shock-capturing mechanism. The model reproduces water levels, waves, currents observed at the mouth of the Zengwen River reasonably well. The simulated residual sediment transport patterns demonstrate that the transport process at the river mouth is dominated by the interaction of the bathymetry and wave-induced currents when the riverine discharge was kept in reservoirs. The offshore residual transport causes erosion at the northern part of the river mouth, and the onshore residual transport causes accretion in the ebb tidal shoals around the center of the river mouth. The simulated morphological evolution displays significant changes on shallower deltas. The location with significant sea bed changes is consistent with the spot in which severe erosion occurred in recent years. Further analysis of morphological evolution is also discussed to identify the role of coastal structures, for example, the extension of the newly constructed groins near the river mouth.

Object Detection and Tracking with UAV Data Using Deep Learning - A. Ancy Micheal; K. Vani; S. Sanjeevi; Chao-Hung Lin (Journal of the Indian Society of Remote Sensing, 2021)

Anti-cancer strategies targeting the autotaxin-lysophosphatidic acid receptor axis: is there a path forward? - Gábor Tigyi; Mélanie A. Dacheux; Kuan-Hung Lin; Junming Yue; Derek Norman; Zoltán Benyó; Sue Chin Lee (Cancer and Metastasis Reviews, 2021)

Piriformospora indica colonization increases the growth, development, and herbivory resistance of sweet potato (Ipomoea batatas L.) - Qing Li; Yun-Wei Kuo; Kuan-Hung Lin; Weiqun Huang; Caisheng Deng; Kai-Wun Yeh; Shi-Peng Chen (Plant Cell Reports, 2021)

Risk of mental illness after the diagnosis of occupational injury or disease: a retrospective cohort study - Ming-Hung Lin; Ya-Lun Yang; Fung-Chung Sung; Chiu-Shong Liu; Chi-Hsuan Lung; Jong-Yi Wang (International Archives of Occupational and Environmental Health, 2021)

Sea Urchins Play an Increasingly Important Role for Coral Resilience Across Reefs in Taiwan - Viet D. H. Dang; Pak-Yin Cheung; Chia-Ling Fong; Aziz J. Mulla; Jia-Ho Shiu; Che-Hung Lin; Yoko Nozawa (Frontiers in Marine Science, 2020)
Herbivores are an important functional group that control algae, create new space, and promote recruitment for coral recovery. However, on many coral reefs, overfishing has greatly decreased the density of herbivores, especially fishes and gastropods, impairing coral resilience. On such overfished reefs, remnant herbivores that are not target species of local fisheries, e.g., sea urchins, are expected to play an increasingly important role, yet few studies, except for those in the Caribbean and Kenya have examined non-fish herbivores in relation to coral resilience. Here, we conducted field surveys at 30 sites along three coral reefs in Taiwan between 2016 and 2017, to examine the relative importance of six key factors for coral resilience: herbivore abundance (fishes, gastropods, sea urchins), coral cover, macroalgal cover, habitat complexity, water depth, and wave exposure. The density of juvenile coral was used as a proxy of coral resilience. Diadematid sea urchins ( Echinothrix spp. and Diadema spp.) dominated most sites (19 of 30 sites) and multivariable regression models showed sea urchin density as the best positive predictor of coral juvenile density. The results elucidated the increasing role diadematid sea urchins play as remnant herbivores on overfished coral reefs in Taiwan. Given that overfishing is a widespread issue, this phenomenon may be occurring globally. More studies are needed to examine the role of remnant, but often ignored, sea urchin herbivory on coral resilience. Reef managers should consider monitoring locally remnant herbivores and incorporating them into management strategies.

Structural insights into Arabidopsis ethylene response factor 96 with an extended N-terminal binding to GCC box - Chun-Yen Chen; Pei-Hsuan Lin; Kun-Hung Chen; Yi-Sheng Cheng (Plant Molecular Biology, 2020)
The phytohormone ethylene is widely involved in many developmental processes and is a crucial regulator of defense responses against biotic and abiotic stresses in plants. Ethylene-responsive element binding protein, a member of the APETALA2/ethylene response factor (AP2/ERF) superfamily, is a transcription factor that regulates stress-responsive genes by recognizing a specific cis -acting element of target DNA. A previous study showed only the NMR structure of the AP2/ERF domain of AtERF100 in complex with a GCC box DNA motif. In this report, we determined the crystal structure of AtERF96 in complex with a GCC box at atomic resolution. We analyzed the binding residues of the conserved AP2/ERF domain in the DNA recognition sequence. In addition to the AP2/ERF domain, an N-terminal α-helix of AtERF96 participates in DNA interaction in the flanking region. We also demonstrated the structure of AtERF96 EDLL motif, a unique conserved motif in the group IX of AP2/ERF family, might involve in the transactivation of defense-related genes. Our study establishes the structural basis of the AtERF96 transcription factor in complex with the GCC box, as well as the DNA binding mechanisms of the N-terminal α-helix and AP2/ERF domain.

Complete mitochondrial genome of the freshwater fish Acrossocheilus longipinnis (Teleostei: Cyprinidae): genome characterization and phylogenetic analysis - Xiao-Jing Hou; Hung-Du Lin; Wen-Qiao Tang; Dong Liu; Chiao-Chuan Han; Jin-Quan Yang (Biologia, 2020)

Correction to: Complete genome sequences of two novel dicistroviruses detected in yellow crazy ants (Anoplolepis gracilipes) - Chih-Chi Lee; Chun-Yi Lin; Hung-Wei Hsu; Chin-Cheng Scotty Yang (Archives of Virology, 2020)

Complete genome sequences of two novel dicistroviruses detected in yellow crazy ants (Anoplolepis gracilipes) - Chih-Chi Lee; Chun-Yi Lin; Hung-Wei Hsu; Chin-Cheng Scotty Yang (Archives of Virology, 2020)

Correction to: Feasibility of Smartphone-Based Gait Assessment for Parkinson’s Disease - Shih‑Tsang Tang; Chun‑Hwei Tai; Chia‑Yen Yang; Jiun‑Hung Lin (Journal of Medical and Biological Engineering, 2020)

Mild acidity likely accelerates the physiological matriptase autoactivation process: a comparative study between spontaneous and acid-induced matriptase zymogen activation - Bailing Jia; Hamishi A. Thompson; Robert B. Barndt; Yi-Lin Chiu; Mon-Juan Lee; See-Chi Lee; Jehng-Kang Wang; Hung-Jen Tang; Chen-Yong Lin; Michael D. Johnson (Human Cell, 2020)

Matriptase and prostasin proteolytic activities are differentially regulated in normal and wounded skin - Shun-Cheng Chang; Chien-Ping Chiang; Chih-Hsin Lai; Po-Wen A. Du; Yu-Sin Hung; Yu-Hsuan Chen; Hui-Yu Yang; Hao-Yu Fang; Shiao-Pieng Lee; Hung-Jen Tang; Jehng-Kang Wang; Michael D. Johnson; et al. (Human Cell, 2020)

Dynamic Stability of an Ocean Current Turbine System - Shueei-Muh Lin; Yang-Yih Chen; Hung-Chu Hsu; Meng-Syue Li (Journal of Marine Science and Engineering, 2020)
This paper presents a theoretical solution for the dynamic stability of the ocean current turbine system developed in Taiwan. This system is tethered to the sea floor and uses the Kuroshio Current to produce electricity. To maintain the performance of the turbine system in the presence of the Kuroshio Current, the stability of the surfaced turbine needs to be considered. The proposed system is composed of a turbine, a buoyance platform, a traction rope, and a mooring foundation. The two-dimensional theoretical solutions treat the turbine as a rigid body with a movable structure that is moored with two cables. In this model, the gravity, buoyancy, and drag force generated by the wave on the turbine structure are considered. In addition, an analytical solution is proposed for the general system. Finally, the effects of the wave on the pitch motion and dynamical stability of the ocean current turbine system are investigated.

Putative Probiotic Strains Isolated from Kefir Improve Gastrointestinal Health Parameters in Adults: a Randomized, Single-Blind, Placebo-Controlled Study - Ming-Cheng Wang; Ahmad Imran Zaydi; Wei-Hung Lin; Jin-Seng Lin; Min-Tze Liong; Jiunn-Jong Wu (Probiotics and Antimicrobial Proteins, 2020)

Upregulation of miR-133a-3p in the Sciatic Nerve Contributes to Neuropathic Pain Development - Lin-Li Chang; Hung-Chen Wang; Kuang-Yi Tseng; Miao-Pei Su; Jaw-Yuan Wang; Yi-Ta Chuang; Yi-Hsuan Wang; Kuang-I Cheng (Molecular Neurobiology, 2020)

Feasibility of Smartphone-Based Gait Assessment for Parkinson’s Disease - Shih-Tsang Tang; Chun-Hwei Tai; Chia-Yen Yang; Jiun-Hung Lin (Journal of Medical and Biological Engineering, 2020)

Sea urchins (diadematids) promote coral recovery via recruitment on Taiwanese reefs - Yoko Nozawa; Che-Hung Lin; Pei-Jie Meng (Coral Reefs, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Methane Seeps and Independent Methane Plumes in the South China Sea Offshore Taiwan - Susan Mau; Tzu-Hsuan Tu; Marius Becker; Christian dos Santos Ferreira; Jhen-Nien Chen; Li-Hung Lin; Pei-Ling Wang; Saulwood Lin; Gerhard Bohrmann (Frontiers in Marine Science, 2020)

Comprehensive Natural Environment and Landscape Signs in Coastal Settlement Hazard Assessment: Case of East Taiwan between the Coastal Mountain and the Pacific Ocean - Shyang-Woei Lin; Chia-Feng Yen; Chih-Hsin Chang; Li-Jin Wang; Hung-Ju Shih (Journal of Marine Science and Engineering, 2020)
In East Taiwan, coastal settlements are scattered and narrowly confined between the Coastal Mountain and the Pacific Ocean. These settlements are currently at risk as there is no room for retreat. Therefore, it is essential to conduct a comprehensive and continuous hazard assessment in these coastal residential areas. In order to avoid biased towards the natural environment, the factors that cannot easily be built within the geographic information system (GIS) database are distinguished by Unmanned Aerial Vehicle (UAV) to conduct a vulnerability assessment of threats to coastal zones. The method: we used the east coast of Taiwan as an example, through GIS and statistical analysis in land-use status, vulnerable population groups and UAV landscape signs of indicators of erosion and accumulation. Through the main output of an intuition scatter map, the erosion landscape susceptibility, economical land-use exposure, and special population groups’ ratio allowed for the easy comparison of the vulnerability, risk level and resilience between different coastal settlements. These diverse observation aspects of risk assessment results can provide prevention and control strategies that meet the different needs of coastal risk management in restricting and strengthening the land-use development of communities.

Population Genetic Analysis for Stock Enhancement of Silver Sea Bream (Rhabdosargus sarba) in Taiwan - Te-Hua Hsu; Chang-Wen Huang; Hung-Tai Lee; Yi-Hsuan Kuo; Kwang-Ming Liu; Cheng-Hui Lin; Hong-Yi Gong (Fishes, 2020)
Stock enhancement is a method for replenishing depleted wild finfish populations by supplementing them with hatchery-raised fish. In Taiwan, silver sea bream (Rhabdosargus sarba) is a predominant commercial species involved in stock enhancement projects. Although management agencies conduct stock enhancement projects, there are a lot of private releases without records. Stock enhancement is performed by the private aquaculture sector without accurate genetic records, potentially leading to unintended consequences for wild populations. We analyzed the genetics of 459 wild and 701 hatchery-reared specimens from nine batches produced by various hatcheries. Wild and hatchery-reared samples could be considered two separate clades by using a set of stable and informative microsatellite markers including type I (from gene introns and 3′UTR) and type II markers (randomly picked up from genome). Type I microsatellite markers could more sensitively reflect the loss of genetic diversity more than type II markers in the domestication process. All specimens were considered native by using mtDNA COI and microsatellites. The genetic composition of the wild population is relatively simple, and the estimated low contribution rate of the hatchery stock (1.3–10.9%; 6–50/459) indicated a weak but significant genetic effect of stock enhancement. Therefore, establishing standards for the stock enhancement of silver sea bream for more effective supplementation of wild populations is imperative.

Calycosin Preserves BDNF/TrkB Signaling and Reduces Post-Stroke Neurological Injury after Cerebral Ischemia by Reducing Accumulation of Hypertrophic and TNF-α-Containing Microglia in Rats - Chien-Chin Hsu; Ting-Wei Kuo; Wen-Pin Liu; Ching-Ping Chang; Hung-Jung Lin (Journal of Neuroimmune Pharmacology, 2020)

Automatic Striatal ROI Delineation for Semi-quantitative Analysis of 99mTc-TRODAT-1 Brain SPECT Imaging - Bang-Hung Yang; Kang-Ping Lin; Mei-Fen Chen; Jui-Hung Weng; Pan-Fu Kao; Wen-Chen Lin; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2020)

Cognitive Load of Exercise Influences Cognition and Neuroplasticity of Healthy Elderly: An Exploratory Investigation - Yi-Ping Chao; Changwei W. Wu; Li-Jung Lin; Cheng-Hung Lai; Hong-Yi Wu; Ai-Ling Hsu; Chiao-Nan Chen (Journal of Medical and Biological Engineering, 2020)
This study explored the effects of exercise with either high cognitive load or low cognitive load on cognitive performance and neuroplasticity in healthy elderly. Twenty-eight sedentary community-dwelling seniors participated in this study. Participants were assigned to one of three groups: the control group (C), low-cognitive load exercise group (LE), or high-cognitive load exercise group (HE). Individuals in both exercise groups engaged in moderate-intensity aerobic exercise for 4 months. Resting-state functional MRI and diffusion MRI were used to investigate the effects of intervention on functional and structural connectivity, respectively. Analysis of covariance with baseline, age and the education year as covariates was used to determine the effects of intervention. We found 4 months of exercise with high-cognitive load, but not exercise with low-cognitive load, improved the overall cognitive function of healthy elderly. Additionally, the HE group showed increased resting-state functional connectivity of superior frontal gyrus and anterior cingulate cortex and decreased functional connectivity of middle occipital gyrus and postcentral gyrus. The age-related alterations in local efficiency and betweenness were protected by exercise. Our findings might suggest that exercise with greater cognitive load likely results in greater training effects on cognition and brain connectivity than exercise requiring lower cognitive loads for healthy elderly.

Effects of Hyperbaric Oxygen Therapy on Acute Myocardial Infarction Following Carbon Monoxide Poisoning - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Chien-Chin Hsu; Hung-Jung Lin; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2020)

Biological Protective Effects Against Vibrio Infections in Grouper Larvae Using the Strombidium sp. NTOU1, a Marine Ciliate Amenable for Scaled-Up Culture and With an Excellent Bacteriovorous Ability - Hung-Yun Lin; Wei-Yu Yeh; Sheng-Fang Tsai; Kuo-Ping Chiang; John Han-You Lin; Che-Chia Tsao; Han-Jia Lin (Frontiers in Marine Science, 2020)

Spectral and spatial kernel water quality mapping - Hone-Jay Chu; Lalu Muhamad Jaelani; Manh Van Nguyen; Chao-Hung Lin; Ariel C. Blanco (Environmental Monitoring and Assessment, 2020)

Prior Antiplatelet Therapy, Excluding Phosphodiesterase Inhibitor Is Associated with Poor Outcome in Patients with Spontaneous Intracerebral Haemorrhage - Zhuo-Hao Liu; Chi-Hung Liu; Po-Hsun Tu; Ping K. Yip; Ching-Chang Chen; Yu-Chi Wang; Nan-Yu Chen; Yu-Sheng Lin (Translational Stroke Research, 2020)

Assessment of transmission risk in WSSV‐infected shrimp Litopenaeus vannamei upon cooking - Luis Fernando Aranguren Caro; Hung N. Mai; Linda Nunan; Joshua Lin; Brenda Noble; Arun K. Dhar (Journal of Fish Diseases, 2020)
White spot syndrome virus has been a threat to the global shrimp industry since it was discovered in Taiwan in 1992. Thus, shrimp‐producing countries have launched regulations to prevent import of WSSV‐infected commodity shrimp from endemic areas. Recently, cooked shrimp that is infected with WSSV tested positive by PCR. However, there is no study to determine the infectivity of WSSV in cooked shrimp that tested positive by PCR. In the present study, WSSV‐infected shrimp were cooked at boiling temperature for different times including 0, 1, 3, 5, 10 and 30 min. Upon exposure to boiling temperature, WSSV‐infected shrimp were fed to SPF shrimp ( Litopenaeus vannamei ). The result showed experimentally challenged shrimp from 0‐min treatment (positive control) indeed got infected with WSSV. However, experimentally challenged shrimp that were fed tissues boiled at 1, 3, 5, 10 and 30 min were not infected with WSSV. Mortality data showed that only the positive control (0‐min) treatment displayed high mortality, whereas no mortality was observed in any other treatment category. These findings suggest that cooking shrimp at boiling temperature for at least 1 min might prevent any potential spread of WSSV from endemic countries to other geographical areas where WSSV has not yet been reported.

Protective Effect of (−)Epigallocatechin-3-gallate on Rotenone-Induced Parkinsonism-like Symptoms in Rats - Hsiang-Chien Tseng; Mao-Hsien Wang; Kuo-Chi Chang; Hung-Sheng Soung; Chih-Hsiang Fang; Yi-Wen Lin; Keng-Yuan Li; Chih-Chuan Yang; Cheng-Chia Tsai (Neurotoxicity Research, 2020)

Protein Arginine Methyltransferases in Cardiovascular and Neuronal Function - Alexandre Couto e Silva; Celeste Yin-Chieh Wu; Cristiane T. Citadin; Garrett A. Clemons; HarLee E. Possoit; Mychal S. Grames; Chih-Feng Lien; Alireza Minagar; Reggie Hui-Chao Lee; Adam Frankel; Hung Wen Lin (Molecular Neurobiology, 2020)

Chemical fingerprint and source apportionment of PM2.5 in highly polluted events of southern Taiwan - Huazhen Shen; Tsung-mou Yang; Chun-chung Lu; Chung-shin Yuan; Chung-Hsuang Hung; Chi-tsan Lin; Chia-wei Lee; Guohua Jing; Gongren Hu; Kuo-cheng Lo (Environmental Science and Pollution Research, 2020)

Comparative Study of Regulations of Devices for Aesthetic Purposes: US, European Union, China, and Taiwan - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2020)

Pulse Oximetry Monitor Feasible for Early Screening of Obstructive Sleep Apnea (OSA) - Huei-Chen Lin; Chien-Ling Su; Jun-Hui Ong; kun-ling Tsai; Yu-Wen Chen; Cheng-Yu Lin; Ling-Ling Chiang; Ching-Hsia Hung (Journal of Medical and Biological Engineering, 2020)

Impacts of the influx of e-waste into Hong Kong after China has tightened up entry regulations - Siyi Lin; Yu Bon Man; Ka Lai Chow; Chunmiao Zheng; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2020)

Altered Mineral Metabolism and Disequilibrium Between Calcification Promoters and Inhibitors in Chronic Hemodialysis Patients - Chia-Liang Wang; Kuan-Pin Lin; Guoo-Shyng W. Hsu; Kai-Li Liu; Chih-Hung Guo (Biological Trace Element Research, 2020)

Correction to: Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Mutational signatures and mutagenic impacts associated with betel quid chewing in oral squamous cell carcinoma - Shih-Chi Su; Lun-Ching Chang; Chiao-Wen Lin; Mu-Kuan Chen; Chun-Ping Yu; Wen-Hung Chung; Shun-Fa Yang (Human Genetics, 2019)

Application of Cas12a and nCas9-activation-induced cytidine deaminase for genome editing and as a non-sexual strategy to generate homozygous/multiplex edited plants in the allotetraploid genome of tobacco - Chen-Tran Hsu; Yu-Jung Cheng; Yu-Hsua Yuan; Wei-Fon Hung; Qiao-Wei Cheng; Fu-Hui Wu; Lan-Ying Lee; Stanton B. Gelvin; Choun-Sea Lin (Plant Molecular Biology, 2019)

Failure mechanism of a mudstone slope embedded with steep anti-dip layered sandstones: case of the 2016 Yanchao catastrophic landslide in Taiwan - Cheng-Han Lin; Ching Hung; Meng-Chia Weng; Ming-Lang Lin; Ryosuke Uzuoka (Landslides, 2019)

Using in situ modification to enhance organic fouling resistance and rejection of pharmaceutical and personal care products in a thin-film composite nanofiltration membrane - Yi-Li Lin; Jia-Zheng Tsai; Chung-Hsuang Hung (Environmental Science and Pollution Research, 2019)

Cloning and overexpression of the ascorbate peroxidase gene from the yam (Dioscorea alata) enhances chilling and flood tolerance in transgenic Arabidopsis - Zhihua Chen; Hsueh-Han Lu; Shumei Hua; Kuan-Hung Lin; Ningdan Chen; Yangwen Zhang; Ziyi You; Yun-Wei Kuo; Shi-Peng Chen (Journal of Plant Research, 2019)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

Simplified Tai Chi 6-Form Apparatus for Balance in Elderly People with Alzheimer’s Disease - Yin-Chou Lin; Wen-Chuin Hsu; Chien-Hung Chen; Chai-Wei Wang; Katie Pei-Hsuan Wu; Alice M. K. Wong (Journal of Medical and Biological Engineering, 2019)

Extracting region-specific runout behavior and rainfall thresholds for massive landslides using seismic records: a case study in southern Taiwan - Ching Hung; Guan-Wei Lin; Ben Leshchinsky; Hsien-Li Kuo (Bulletin of Engineering Geology and the Environment, 2019)

Potassium Stimulation of IAA Transport Mediated by the Arabidopsis Importer AUX1 Investigated in a Heterologous Yeast System - Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Shih-Ming Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Acoustic Emission-Feedback Planar Ultrasound System for Localized Blood–Brain Barrier Opening Monitoring - Chih-Hung Tsai; Ko-Ting Chen; Yu-Xian Lin; Yu-Chien Lin; Wen-Shiang Chen; Claude Inserra; Hao-Li Liu (Journal of Medical and Biological Engineering, 2019)

The Aso-Bridge coseismic landslide: a numerical investigation of failure and runout behavior using finite and discrete element methods - Ching Hung; Chih-Hsuan Liu; Guan-Wei Lin; Ben Leshchinsky (Bulletin of Engineering Geology and the Environment, 2019)

Development of an Image Processing Module for Autonomous Underwater Vehicles through Integration of Visual Recognition with Stereoscopic Image Reconstruction - Yu-Hsien Lin; Shao-Yu Chen; Chia-Hung Tsou (Journal of Marine Science and Engineering, 2019)
This study investigated the development of visual recognition and stereoscopic imaging technology, applying them to the construction of an image processing system for autonomous underwater vehicles (AUVs). For the proposed visual recognition technology, a Hough transform was combined with an optical flow algorithm to detect the linear features and movement speeds of dynamic images; the proposed stereoscopic imaging technique employed a Harris corner detector to estimate the distance of the target. A physical AUV was constructed with a wide-angle lens camera and a binocular vision device mounted on the bow to provide image input. Subsequently, a simulation environment was established in Simscape Multibody and used to control the post-driver system of the stern, which contained horizontal and vertical rudder planes as well as the propeller. In static testing at National Cheng Kung University, physical targets were placed in a stability water tank; the study compared the analysis results obtained from various brightness and turbidity conditions in out-of-water and underwater environments. Finally, the dynamic testing results were combined with a fuzzy controller to output the real-time responses of the vehicle regarding the angles, rates of the rudder planes, and the propeller revolution speeds at various distances.

Risk of Myocardial Infarction After Carbon Monoxide Poisoning: A Nationwide Population-Based Cohort Study - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Hung-Jung Lin; Chien-Chin Hsu; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2019)

Mitochondrial Genetic Diversity of the Freshwater Snail Melanoides tuberculata - Yuh-Wen Chiu; Ye-Chen Gan; Po-Hsun Kuo; Kui-Ching Hsu; Mian-Shin Tan; Yu-Min Ju; Hung-Du Lin (Biochemical Genetics, 2019)

Prediction of annual dengue incidence by hydro-climatic extremes for southern Taiwan - Hsiang-Yu Yuan; Tzai-Hung Wen; Yi-Hung Kung; Hsiao-Hui Tsou; Chun-Hong Chen; Li-Wei Chen; Pei-Sheng Lin (International Journal of Biometeorology, 2019)

Far-infrared Radiation Improves Motor Dysfunction and Neuropathology in Spinocerebellar Ataxia Type 3 Mice - Shin-Wu Liu; Jui-Chih Chang; Sheng-Fei Chuang; Ko-Hung Liu; Wen-Ling Cheng; Hui-Ju Chang; Huei-Shin Chang; Ta-Tsung Lin; Ching-Liang Hsieh; Wei-Yong Lin; Mingli Hsieh; Shou-Jen Kuo; et al. (The Cerebellum, 2019)

Analysis of Electroencephalography Event-Related Desynchronisation and Synchronisation Induced by Lower-Limb Stepping Motor Imagery - Yi-Hung Liu; Li-Fong Lin; Chun-Wei Chou; Yun Chang; Yu-Tsung Hsiao; Wei-Chun Hsu (Journal of Medical and Biological Engineering, 2019)

Herpes zoster and the risks of osteoporosis and fracture: a nationwide cohort study - Shu-Man Lin; Chih-Yung Wang; Ying-Yu Chen; Jen-Hung Wang; Chung-Chao Liang; Huei-Kai Huang (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Evaluation of an enhanced FS method for finding the initiation time of earthquake-induced landslides - Guan-Wei Lin; Ching Hung; Huei-Sian Syu (Bulletin of Engineering Geology and the Environment, 2019)

Historical demography of four gecko species specializing in boulder cave habitat: Implications in the evolutionary dead end hypothesis and conservation - Hung N. Nguyen; Chia‐Wei Lu; Jui‐Hua Chu; Larry Lee Grismer; Chih‐Ming Hung; Si‐Min Lin (Molecular Ecology, 2019)
Specialization in narrow ecological niches may not only help species to survive in competitive or unique environments but also contribute to their extermination over evolutionary time. Although the “evolutionary dead end” hypothesis has long been debated, empirical evidence from species with detailed information on niche specialization and evolutionary history remains rare. Here we use a group of four closely related Cnemaspis gecko species that depend highly on granite boulder caves in the Mekong Delta to investigate the potential impact of ecological specialization on their evolution and population dynamics. Isolated by unsuitable floodplain habitats, these boulder‐dwelling geckos are among the most narrowly distributed Squamata in the world. We applied several coalescence‐based approaches combined with the RAD‐seq technique to estimate their divergence times, gene flow and demographic fluctuations during the speciation and population differentiation processes. Our results reveal long‐term population shrinkage in the four geckos and limited gene flow during their divergence. The results suggest that the erosion and fragmentation of the granite boulder hills have greatly impacted population divergence and declines. The habitat specialization of these geckos has led to fine‐scaled speciation in these granite rocky hills; in contrast, specialization might also have pushed these species toward the edge of extinction. Our study also emphasizes the conservation urgency of these vulnerable, cave‐dependent geckos.

Effect of different ethanolic concentrations on antioxidant properties and cytoprotective activities of Platostoma palustre Blume - Kuan-Hung Lin; Ming-Chih Shih; Po Wang; Yi-Ping Yu; Chun-Ping Lu (Natural Product Research, 2018)

Nonparametric dynamical model of cardiorespiratory responses at the onset and offset of treadmill exercises - Hairong Yu; Lin Ye; Ganesh R. Naik; Rong Song; Hung T. Nguyen; Steven W. Su (Medical & Biological Engineering & Computing, 2018)

Pre-treatment with angiotensin-(1–7) inhibits tumor growth via autophagy by downregulating PI3K/Akt/mTOR signaling in human nasopharyngeal carcinoma xenografts - Yu-Tsai Lin; Hung-Chen Wang; Hui-Ching Chuang; Yi-Chiang Hsu; Ming-Yu Yang; Chih-Yen Chien (Journal of Molecular Medicine, 2018)

Tissue Section Image-Based Liver Scar Detection - Yung-Kuan Chan; Ming-Jen Chang; Yi-Wen Hung; Ching-Lin Wang; Chun-Fu Hong; Kwong-Chung Tung; Shyr Shen Yu (Journal of Medical and Biological Engineering, 2018)

Illustrating the Impact of Uneven Saline Distribution on Thermal Lesion During Radiofrequency Ablation Using Computer Simulation for Smarter Healthcare Treatment Planning - Huang-Wen Huang; Lin Hui; Jason C. Hung; Kuei Min Wang (Journal of Medical and Biological Engineering, 2018)

Changes in Trace Elements During Early Stages of Chronic Kidney Disease in Type 2 Diabetic Patients - Ching-Chiang Lin; Ching-Tang Shih; Chien-Hung Lee; Yeou-Lih Huang (Biological Trace Element Research, 2018)

NTF3 Is a Novel Target Gene of the Transcription Factor POU3F2 and Is Required for Neuronal Differentiation - Yi-Mei J. Lin; I-Lun Hsin; H. Sunny Sun; Shankung Lin; Yen-Ling Lai; Hsuan-Ying Chen; Ting-Yu Chen; Ya-Ping Chen; Yi-Ting Shen; Hung-Ming Wu (Molecular Neurobiology, 2018)

Response to “Letter to the editor re: Cheng YH, Chou WC, Yang YF, et al. Environ Sci Pollut Res (2018). https://doi.org/10.107/s11356-017-0875-4” - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Analysis of the Aso-Bridge landslide during the 2016 Kumamoto earthquakes in Japan - Ching Hung; Guan-Wei Lin; Huei-Sian Syu; Chi-Wen Chen; Hsin-Yi Yen (Bulletin of Engineering Geology and the Environment, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

The effects of El Niño‐Southern Oscillation events on intertidal seagrass beds over a long‐term timescale - Hsing‐Juh Lin; Chen‐Lu Lee; Shang‐En Peng; Meng‐Chi Hung; Pi‐Jen Liu; Anderson B. Mayfield (Global Change Biology, 2018)
El Niño‐Southern Oscillation (ENSO) events can cause dramatic changes in marine communities. However, we know little as to how ENSO events affect tropical seagrass beds over decadal timescales. Therefore, a diverse array of seagrass ( Thalassia hemprichii ) habitat types were surveyed once every 3 months for 16 years (January 2001 to February 2017) in a tropical intertidal zone that is regularly affected by both ENSO events and anthropogenic nutrient enrichment. La Niña and El Niño events had distinct effects on the biomass and growth of T. hemprichii . During La Niña years, higher (a) precipitation levels and (b) seawater nitrogen concentrations led to increases in seagrass leaf productivity, canopy height, and biomass. However, the latter simultaneously stimulated the growth of periphyton on seagrass leaves; this led to decreases in seagrass cover and shoot density. More frequent La Niña events could, then, eventually lead to either a decline in intertidal seagrass beds or a shift to another, less drought‐resistant seagrass species in those regions already characterized by eutrophication due to local anthropogenic activity.

Dynamic response of a dip slope with multi-slip planes revealed by shaking table tests - Hung-Hui Li; Cheng-Han Lin; Wei Zu; Chi-Chieh Chen; Meng-Chia Weng (Landslides, 2018)

Clinical and microbiological characteristics of peritoneal dialysis-related peritonitis caused by Escherichia coli in southern Taiwan - Wei-Hung Lin; Chin-Chung Tseng; An-Bang Wu; Yu-Tzu Chang; Te-Hui Kuo; Jo-Yen Chao; Ming-Cheng Wang; Jiunn-Jong Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

The Divalent Elements Changes in Early Stages of Chronic Kidney Disease - Wan-Ju Kung; Ching-Tang Shih; Chien-Hung Lee; Ching-Chiang Lin (Biological Trace Element Research, 2018)

The complete mitogenome of the winged argonaut Argonauta hians and its phylogenetic relationships in Octopoda - Yu-Wen Chiu; Chih-Wei Chang; Hung-Du Lin; Kang-Ning Shen (Conservation Genetics Resources, 2018)

Factors regulating carbon sinks in mangrove ecosystems - Shi‐Bo Li; Po‐Hung Chen; Jih‐Sheng Huang; Mei‐Li Hsueh; Li‐Yung Hsieh; Chen‐Lu Lee; Hsing‐Juh Lin (Global Change Biology, 2018)
Mangroves are recognized as one of the richest carbon storage systems. However, the factors regulating carbon sinks in mangrove ecosystems are still unclear, particularly in the subtropical mangroves. The biomass, production, litterfall, detrital export and decomposition of the dominant mangrove vegetation in subtropical ( Kandelia obovata ) and tropical ( Avicennia marina ) Taiwan were quantified from October 2011 to July 2014 to construct the carbon budgets. Despite the different tree species, a principal component analysis revealed the site or environmental conditions had a greater influence than the tree species on the carbon processes. For both species, the net production (NP) rates ranged from 10.86 to 27.64 Mg C ha −1 year −1 and were higher than the global average rate due to the high tree density. While most of the litterfall remained on the ground, a high percentage (72%–91%) of the ground litter decomposed within 1 year and fluxed out of the mangroves. However, human activities might cause a carbon flux into the mangroves and a lower NP rate. The rates of the organic carbon export and soil heterotrophic respiration were greater than the global mean values and those at other locations. Only a small percentage (3%–12%) of the NP was stored in the sediment. The carbon burial rates were much lower than the global average rate due to their faster decomposition, indicating that decomposition played a critical role in determining the burial rate in the sediment. The summation of the organic and inorganic carbon fluxes and soil heterotrophic respiration well exceeded the amount of litter decomposition, indicating an additional source of organic carbon that was unaccounted for by decomposition in the sediment. Sediment‐stable isotope analyses further suggest that the trapping of organic matter from upstream rivers or adjacent waters contributed more to the mangrove carbon sinks than the actual production of the mangrove trees.

Tacrine(10)-hupyridone, a dual-binding acetylcholinesterase inhibitor, potently attenuates scopolamine-induced impairments of cognition in mice - Huixin Chen; Siying Xiang; Ling Huang; Jiajia Lin; Shengquan Hu; Shing-Hung Mak; Chuang Wang; Qinwen Wang; Wei Cui; Yifan Han (Metabolic Brain Disease, 2018)

Sodium Metabisulfite: Effects on Ionic Currents and Excitotoxicity - Ming-Chi Lai; Te-Yu Hung; Kao-Min Lin; Pi-Shan Sung; Shyh-Jong Wu; Chih-Sheng Yang; Yi-Jen Wu; Jing-Jane Tsai; Sheng-Nan Wu; Chin-Wei Huang (Neurotoxicity Research, 2018)

Occurrence, identification, and bactericide sensitivity of Pantoea ananatis causing leaf blight on welsh onion in Taiwan - Yi-Jen Wang; Chih-Hung Lin; Chien-Jui Huang (Journal of Plant Pathology, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Phthalate esters distribution in coastal mariculture of Hong Kong, China - Zhang Cheng; Han-Han Li; Lin Yu; Zhan-Biao Yang; Xiao-Xun Xu; Hong-Sheng Wang; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

Recent Research Progress on the Antidepressant-like Effect and Neuropharmacological Potential of Gastrodia elata Blume - Yu-En Lin; Kuan-Hung Lu; Lee-Yan Sheen (Current Pharmacology Reports, 2018)

Mitochondrial and nuclear genetic structure in Rhodeus ocellatus (Teleostei: Cyprinidae) with approximate Bayesian computation - Jin-Quan Yang; Kui-Ching Hsu; Po-Hsun Kuo; Lin-Lin Li; Wen-Qiao Tang; Dong Liu; Hung-Du Lin (Environmental Biology of Fishes, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Insights into the roles of anammox bacteria in post-treatment of anaerobically-treated sewage - Qian Wang; Giin-Yu Amy Tan; Mohammad Azari; Xiaowu Huang; Martin Denecke; Yujie Men; Jin-Young Jung; Satoshi Okabe; Muhammad Ali; Yu-Tzu Huang; Zhuoying Wu; Wai-hung Lo; et al. (Critical Reviews in Environmental Science and Technology, 2018)

Residue characteristics of sludge from a chemical industrial plant by microwave heating pyrolysis - Kuo-Hsiung Lin; Nina Lai; Jun-Yan Zeng; Hung-Lung Chiang (Environmental Science and Pollution Research, 2018)

PBPK/PD assessment for Parkinson’s disease risk posed by airborne pesticide paraquat exposure - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

IGF1R+ Dental Pulp Stem Cells Enhanced Neuroplasticity in Hypoxia-Ischemia Model - Hsiao-Yu Chiu; Chen-Huan Lin; Chung Y. Hsu; John Yu; Chia-Hung Hsieh; Woei-Cherng Shyu (Molecular Neurobiology, 2017)

Variability of spawning time (lunar day) in Acropora versus merulinid corals: a 7-yr record of in situ coral spawning in Taiwan - Che-Hung Lin; Yoko Nozawa (Coral Reefs, 2017)

Enhancing Immiscible Fluid Displacement in Porous Media by Capillary Pressure Discontinuities - C. A. Chung; Hung-Yu Lin (Transport in Porous Media, 2017)

Identification of morin as an agonist of imidazoline I-3 receptor for insulin secretion in diabetic rats - Mang Hung Lin; Chia-Chen Hsu; Jenshinn Lin; Juei-Tang Cheng; Ming Chang Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

17β-Estradiol and/or estrogen receptor alpha blocks isoproterenol-induced calcium accumulation and hypertrophy via GSK3β/PP2A/NFAT3/ANP pathway - Peiying Pai; Bharath Kumar Velmurugan; Chia-Hua Kuo; Chung-Yi Yen; Tsung-Jung Ho; Yueh-Min Lin; Yu-Feng Chen; Chao-Hung Lai; Cecilia Hsuan Day; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2017)

Ultrasonic Soil Washing with Fish Oil Extract to Remove Polychlorinated Dibenzo-p-dioxins (PCDDs), Dibenzofurans (PCDFs) from Highly Contaminated Field Soils - Chi Thanh Vu; Chitsan Lin; Weiteng Hung; Wen-Yen Huang; Acharee Kaewlaoyoong; Siwalee Yotapukdee; Jenq-Renn Chen; Yun-Hwei Shen (Water, Air, & Soil Pollution, 2017)

Detection of exercise periodic breathing using thermal flowmeter in patients with heart failure - Tieh-Cheng Fu; Wen-Chen Lin; Jong-Shyan Wang; Chao-Hung Wang; Chun-Tien Chang; Cheng-Lun Tsai; Yun-Shien Lee; Kang-Ping Lin (Medical & Biological Engineering & Computing, 2017)

The use of ultrasound-assisted anaerobic compost tea washing to remove poly-chlorinated dibenzo-p-dioxins (PCDDs), dibenzo-furans (PCDFs) from highly contaminated field soils - Weiteng Hung; Wen-Yen Huang; Chitsan Lin; Chi Thanh Vu; Siwalee Yotapukdee; Acharee Kaewlaoyoong; Jenq-Renn Chen; Yun-Hwei Shen (Environmental Science and Pollution Research, 2017)

Current pathogenic Escherichia coli foodborne outbreak cases and therapy development - Shih-Chun Yang; Chih-Hung Lin; Ibrahim A. Aljuffali; Jia-You Fang (Archives of Microbiology, 2017)

IL-28 and IL-29 as protective markers in subject with dengue fever - Chih-Hsing Hung; Chung-Hao Huang; Lin Wang; Chun-Chi Huang; Meng-Chieh Wu; Yi-Ying Chin; Chun-Yu Lin; Ko Chang; Deng-Chyang Wu; Yen-Hsu Chen (Medical Microbiology and Immunology, 2017)

Different responses of influenza epidemic to weather factors among Shanghai, Hong Kong, and British Columbia - Xi-Ling Wang; Lin Yang; Dai-Hai He; Alice PY Chiu; Kwok-Hung Chan; King-Pan Chan; Maigeng Zhou; Chit-Ming Wong; Qing Guo; Wenbiao Hu (International Journal of Biometeorology, 2017)

Mixture risk assessment due to ingestion of arsenic, copper, and zinc from milkfish farmed in contaminated coastal areas - Yi-Jun Lin; Min-Pei Ling; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Hsien Cheng; Shu-Han You; Wei-Chun Chou; Ming-Chao Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2017)

Prior Visual Experience Modulates Learning of Sound Localization Among Blind Individuals - Qian Tao; Chetwyn C. H. Chan; Yue-jia Luo; Jian-jun Li; Kin-hung Ting; Zhong-lin Lu; Susan Whitfield-Gabrieli; Jun Wang; Tatia M. C. Lee (Brain Topography, 2017)

Increased risk of chronic osteomyelitis after hip replacement: a retrospective population-based cohort study in an Asian population - D.-Z. Hung; N. Tien; C.-L. Lin; Y.-R. Lee; C. C. N. Wang; J.-J. Chen; Y.-P. Lim (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Therapeutic potential of pro-angiogenic BPC157 is associated with VEGFR2 activation and up-regulation - Ming-Jer Hsieh; Hsien-Ta Liu; Chao-Nin Wang; Hsiu-Yun Huang; Yuling Lin; Yu-Shien Ko; Jong-Shyan Wang; Vincent Hung-Shu Chang; Jong-Hwei S. Pang (Journal of Molecular Medicine, 2017)

Overexpression of the ascorbate peroxidase gene from eggplant and sponge gourd enhances flood tolerance in transgenic Arabidopsis - Chih-Ming Chiang; Chiu-Chen Chen; Shi-Peng Chen; Kuan-Hung Lin; Li-Ru Chen; Yu-Huei Su; His-Cheng Yen (Journal of Plant Research, 2017)

Bilateral photoplethysmography for arterial steal detection in arteriovenous fistula using a fractional-order decision-making quantizer - Jian-Xing Wu; Guan-Chun Chen; Ming-Jui Wu; Chia-Hung Lin; Tainsong Chen (Medical & Biological Engineering & Computing, 2017)

miRNA Expression Change in Dorsal Root Ganglia After Peripheral Nerve Injury - Hsueh-Ling Chang; Hung-Chen Wang; Yi-Ta Chunag; Chao-Wen Chou; I-Ling Lin; Chung-Sheng Lai; Lin-Li Chang; Kuang-I Cheng (Journal of Molecular Neuroscience, 2017)

An integrated earthquake early warning system and its performance at schools in Taiwan - Bing-Ru Wu; Nai-Chi Hsiao; Pei-Yang Lin; Ting-Yu Hsu; Chiou-Yun Chen; Shieh-Kung Huang; Hung-Wei Chiang (Journal of Seismology, 2017)

The spatio-temporal characteristics of potential dengue risk assessed by Aedes aegypti and Aedes albopictus in high-epidemic areas - Chia-Hsien Lin; Tzai-Hung Wen; Hwa-Jen Teng; Niann-Tai Chang (Stochastic Environmental Research and Risk Assessment, 2016)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

Erratum to: Evaluation of Anti-Inflammatory Effects of Helminthostachys zeylanica Extracts via Inhibiting Bradykinin-Induced MMP-9 Expression in Brain Astrocytes - Chuen-Mao Yang; Sien-Hung Yang; Tsong-Hai Lee; Jia-You Fang; Chwan-Fwu Lin; Mei-Jie Jou; Hsi-Lung Hsieh (Molecular Neurobiology, 2016)

Evaluation of Anti-Inflammatory Effects of Helminthostachys zeylanica Extracts via Inhibiting Bradykinin-Induced MMP-9 Expression in Brain Astrocytes - Hsi-Lung Hsieh; Sien-Hung Yang; Tsong-Hai Lee; Jia-You Fang; Chwan-Fwu Lin (Molecular Neurobiology, 2016)

Identification of susceptibility gene associated with female primary Sjögren’s syndrome in Han Chinese by genome-wide association study - I-Wen Song; Hsiang-Cheng Chen; Yuh-Feng Lin; Jenn-Hwai Yang; Chi-Ching Chang; Chung-Tei Chou; Ming-Ta Michael Lee; Yi-Chun Chou; Chien-Hsiun Chen; Yuan-Tsong Chen; Chen-Hung Chen; Jer-Yuarn Wu (Human Genetics, 2016)

Green and sustainable remediation (GSR) evaluation: framework, standards, and tool. A case study in Taiwan - Wen-Yen Huang; Weiteng Hung; Chi Thanh Vu; Wei-Ting Chen; Jhih-Wei Lai; Chitsan Lin (Environmental Science and Pollution Research, 2016)

Catastrophic outburst and tsunami flooding of Lake Baikal: U–Pb detrital zircon provenance study of the Palaeo-Manzurka megaflood sediments - Alexei V. Ivanov; Elena I. Demonterova; Leonid Z. Reznitskii; Igor G. Barash; Sergey G. Arzhannikov; Anastasia V. Arzhannikova; Chan-Hui Hung; Sun-Lin Chung; Yoshiyuki Iizuka (International Geology Review, 2016)

Methylation and Esterification of Magnolol for Ameliorating Cutaneous Targeting and Therapeutic Index by Topical Application - Chwan-Fwu Lin; Chi-Feng Hung; Ibrahim A. Aljuffali; Yu-Ling Huang; Wei-Chun Liao; Jia-You Fang (Pharmaceutical Research, 2016)

Arbuscular mycorrhizal fungi optimize the acquisition and translocation of Cd and P by cucumber (Cucumis sativus L.) plant cultivated on a Cd-contaminated soil - Junli Hu; Wing Tsang; Fuyong Wu; Shengchun Wu; Junhua Wang; Xiangui Lin; Ming Hung Wong (Journal of Soils and Sediments, 2016)

Disentangling the effects of isolation-by-distance and isolation-by-environment on genetic differentiation among Rhododendron lineages in the subgenus Tsutsusi - Chun-Lin Huang; Jui-Hung Chen; Chung-Te Chang; Jeng-Der Chung; Pei-Chun Liao; Jenn-Che Wang; Shih-Ying Hwang (Tree Genetics & Genomes, 2016)

Influence of Soluplus on Solid-State Properties and Physical Stability of Indomethacin-Saccharin Co-crystal Formation Prepared by Air-Drying Process - Shan-Yang Lin; Hong-Liang Lin; Ying-Ting Chi; Ru-Ying Hung; Yu-Ting Huang; Wei-Hsien Hsieh; Chi-Yu Kao (Journal of Pharmaceutical Innovation, 2016)

Nitrogen balances and nitrogen-use efficiency of different organic and conventional farming systems - Hung-Chun Lin; Julia A. Huber; Georg Gerl; Kurt-Jürgen Hülsbergen (Nutrient Cycling in Agroecosystems, 2016)

Prevalence of potential nitrogen‐fixing, green sulfur bacteria in the skeleton of reef‐building coral I sopora palifera - Shan‐Hua Yang; Sonny T. M. Lee; Chang‐Rung Huang; Ching‐Hung Tseng; Pei‐Wen Chiang; Chung‐Pin Chen; Hsing‐Ju Chen; Sen‐Lin Tang (Limnology and Oceanography, 2016)
Microbial endoliths, which inhabit interior pores of rocks, skeletons and coral, are ubiquitous in terrestrial and marine environments. In this study, various colored layers stratified the endolithic environment within the skeleton of Isopora palifera ; however, there was a distinct green‐pigmented layer in the skeleton (beneath the living coral tissue). To characterize diversity of endolithic microorganisms, 16S ribosomal RNA gene amplicon pyrosequencing was used to investigate bacterial communities in the green layer of eight I. palifera coral colonies retrieved from two locations on Green Island, Taiwan. The dominant bacterial group in the green layer belonged to the bacterial phylum Chlorobi, green sulfur bacteria capable of anoxygenic photosynthesis and nitrogen fixation. Specifically, bacteria of the genus Prosthecochloris were dominant in this green layer. To our knowledge, this is the first study to provide a detailed profile of endolithic bacteria in coral and to determine the prevalence of Prosthecochloris in the green layer. Based on our findings, we infer that these bacteria may have an important functional role in the coral holobiont in the nutrient‐limited coral reef ecosystem.

Increased night duty loading of physicians caused elevated blood pressure and sympathetic tones in a dose-dependent manner - Hsiu-Hao Lee; Shih-Hsiang Lo; Bing-Yu Chen; Yen-Hung Lin; Dachen Chu; Tsun-Jen Cheng; Pau-Chung Chen; Yue-Liang Guo (International Archives of Occupational and Environmental Health, 2016)

Transcriptional and posttranscriptional regulation of CXCL8/IL-8 gene expression induced by connective tissue growth factor - Chien-Huang Lin; Yuan-Hung Wang; Yu-Wen Chen; Yu-Liang Lin; Bing-Chang Chen; Mei-Chieh Chen (Immunologic Research, 2016)

Humic acids enhance the microbially mediated release of sedimentary ferrous iron - Chun-Han Chang; Chia-Cheng Wei; Li-Hung Lin; Tzu-Hsuan Tu; Vivian Hsiu-Chuan Liao (Environmental Science and Pollution Research, 2016)

One-step RT-LAMP analysis for efficient detection of Odontoglossum ringspot virus from Oncidiinae hybrids (Orchidaceae) - Chi-Chu Tsai; Chun-Yen Huang; I-Szu Weng; Wen-Lin Liu; Chang-Hung Chou (Journal of General Plant Pathology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Six new metabolites produced by Colletotrichum aotearoa 09F0161, an endophytic fungus isolated from Bredia oldhamii - Yi Hsiao; Ming-Jen Cheng; Hsun-Shuo Chang; Ming-Der Wu; Sung-Yuan Hsieh; Ta-Wei Liu; Chu-Hung Lin; Gwo-Fang Yuan; Ih-Sheng Chen (Natural Product Research, 2016)

A Clinical and Kinematical Evaluation of Trajectory Planning Software for Posterior Atlantoaxial Transarticular Screw Fixation Surgery - Andy Chien; Yao-Hung Wang; Dar-Ming Lai; Ying-Sian Chen; Wen-Kai Chou; Been-Der Yang; Jaw-Lin Wang (Journal of Medical and Biological Engineering, 2016)

Sleep medicine in Taiwan - Ning-Hung Chen; Liang-Wen Hang; Chia-Mo Lin (Sleep and Biological Rhythms, 2016)

A set of GFP-based organelle marker lines combined with DsRed-based gateway vectors for subcellular localization study in rice (Oryza sativa L.) - Tsung-Meng Wu; Ke-Chun Lin; Wei-Shiang Liau; Yun-Yang Chao; Ling-Hung Yang; Szu-Yun Chen; Chung-An Lu; Chwan-Yang Hong (Plant Molecular Biology, 2016)

Physiological and proteomic analysis in two wild tomato lines under waterlogging and high temperature stress - Hsin-Hung Lin; Kuan-Hung Lin; Jia-Yu Syu; Shun-Yuan Tang; Hsiao-Feng Lo (Journal of Plant Biochemistry and Biotechnology, 2016)

Parasite and Infected-Erythrocyte Image Segmentation in Stained Blood Smears - Yi-Wen Hung; Ching-Lin Wang; Chuin-Mu Wang; Yung-Kuan Chan; Lin-Yu Tseng; Chiu-Wen Lee; Kwong-Chung Tung (Journal of Medical and Biological Engineering, 2015)

High-Performance Multiclass Classification Framework Using Cloud Computing Architecture - Feng-Sheng Lin; Chia-Ping Shen; Chia-Hung Liu; Han Lin; Chi-Ying F. Huang; Cheng-Yan Kao; Feipei Lai; Jeng-Wei Lin (Journal of Medical and Biological Engineering, 2015)

Data Perturbation Method Based on Contrast Mapping for Reversible Privacy-preserving Data Mining - Yuan-Hung Kao; Wei-Bin Lee; Tien-Yu Hsu; Chen-Yi Lin; Hui-Fang Tsai; Tung-Shou Chen (Journal of Medical and Biological Engineering, 2015)

Dysfunction Screening in Experimental Arteriovenous Grafts for Hemodialysis Using Fractional-Order Extractor and Color Relation Analysis - Ming-Jui Wu; Wei-Ling Chen; Chung-Dann Kan; Fan-Ming Yu; Su-Chin Wang; Hsiu-Hui Lin; Chia-Hung Lin (Cardiovascular Engineering and Technology, 2015)

An improved modeling of TDR signal propagation for measuring complex dielectric permittivity - Chih-Ping Lin; Shr-Hong Tang; Chun-Hung Lin; Chih-Chung Chung (Journal of Earth Science, 2015)

Ceramics manufacturing contributes to ambient silica air pollution and burden of lung disease - Chung-Min Liao; Bo-Chun Wu; Yi-Hsien Cheng; Shu-Han You; Yi-Jun Lin; Nan-Hung Hsieh (Environmental Science and Pollution Research, 2015)

Pretreatment with Evans blue, a stimulator of BKCa channels, inhibits compound 48/80-induced shock, systemic inflammation, and mast cell degranulation in the rat - Yaw-Syan Fu; Su-Yu Kuo; Hsuan-Yea Lin; Chun-Lin Chen; Shi-Ying Huang; Zhi-Hong Wen; Kun-Zer Lee; Hung-Tu Huang (Histochemistry and Cell Biology, 2015)

The associations between metals/metalloids concentrations in blood plasma of Hong Kong residents and their seafood diet, smoking habit, body mass index and age - Yan Yan Qin; Clement Kai Man Leung; Che Kit Lin; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Genetic variants of retinol-binding protein 4 in adolescents are associated with liver function and inflammatory markers but not with obesity and insulin resistance - CHIN-JUNG LIN; NAIN-FENG CHU; YI-JEN HUNG; DEE PEI; CHIEN-HSING LEE; FONE-CHING HSIAO; CHIEH-HUA LU; CHANG-HSUN HSIEH (Journal of Genetics, 2015)

Calreticulin Regulates VEGF-A in Neuroblastoma Cells - Wen-Chin Weng; Kuan-Hung Lin; Pei-Yi Wu; Yi-Chien Lu; Yi-Cheng Weng; Bo-Jeng Wang; Yung-Feng Liao; Wen-Ming Hsu; Wang-Tso Lee; Hsinyu Lee (Molecular Neurobiology, 2015)

Effects of Polypropylene Carbonate/Poly(d,l-lactic) Acid/Tricalcium Phosphate Elastic Composites on Improving Osteoblast Maturation - Hsu-Wei Fang; Wei-Yu Kao; Pei-I Lin; Guang-Wei Chang; Ya-Jung Hung; Ruei-Ming Chen (Annals of Biomedical Engineering, 2015)

Expression of eggplant ascorbate peroxidase increases the tolerance of transgenic rice plants to flooding stress - Chih Ming Chiang; Long Fang O. Chen; Shang Wen Shih; Kuan Hung Lin (Journal of Plant Biochemistry and Biotechnology, 2015)

Genetic relationships and ecological divergence in Salix species and populations in Taiwan - Chun-Lin Huang; Chung-Te Chang; Bing-Hong Huang; Jeng-Der Chung; Jui-Hung Chen; Yu-Chung Chiang; Shih-Ying Hwang (Tree Genetics & Genomes, 2015)

Arsenic tolerance, uptake, and accumulation by nonmetallicolous and metallicolous populations of Pteris vittata L - Fuyong Wu; Dan Deng; Shengchun Wu; Xiangui Lin; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Sassarandainol: a new neolignan and anti-inflammatory constituents from the stem of Sassafras randaiense - Ya-Ling Hou; Hsun-Shuo Chang; Hui-Chun Wang; Sheng-Yang Wang; Tze-Ying Chen; Chu-Hung Lin; Ih-Sheng Chen (Natural Product Research, 2015)

Transcriptional regulation of the iac locus from Acinetobacter baumannii by the phytohormone indole-3-acetic acid - Hung-Yu Shu; Ling-Chun Lin; Tze-Kang Lin; Hao-Ping Chen; Hsueh-Hui Yang; Kou-Cheng Peng; Guang-Huey Lin (Antonie van Leeuwenhoek, 2015)

Production of Arachidonic and Eicosapentaenoic Acids by the Marine Oomycete Halophytophthora - Ka-Lai Pang; Han-Jia Lin; Hung-Yun Lin; Yu-Fen Huang; Yi-Min Chen (Marine Biotechnology, 2015)

Classification of Benign and Malignant Breast Tumors in Ultrasound Images with Posterior Acoustic Shadowing Using Half-Contour Features - Zhuhuang Zhou; Shuicai Wu; King-Jen Chang; Wei-Ren Chen; Yung-Sheng Chen; Wen-Hung Kuo; Chung-Chih Lin; Po-Hsiang Tsui (Journal of Medical and Biological Engineering, 2015)

Human health risk assessment of soil dioxin/furans contamination and dioxin-like activity determined by ethoxyresorufin-O-deethylase bioassay - Yu Bon Man; Ka Lai Chow; Hong Sheng Wang; Xiao Lin Sun; Sheng Chun Wu; Zong Wei Cai; Yuan Kang; Hui Li; Jin Shu Zheng; John P. Giesy; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Avian reovirus S1133-induced apoptosis is associated with Bip/GRP79-mediated Bim translocation to the endoplasmic reticulum - Ping-Yuan Lin; Hung-Jen Liu; Ching-Dong Chang; Yo-Chia Chen; Chi-I Chang; Wen-Ling Shih (Apoptosis, 2015)

Regional response of dengue fever epidemics to interannual variation and related climate variability - Chung-Min Liao; Tang-Luen Huang; Yi-Jun Lin; Shu-Han You; Yi-Hsien Cheng; Nan-Hung Hsieh; Wei-Yu Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Analysis of space–time patterns of rainfall events during 1996–2008 in Yilan County (Taiwan) - Hwa-Lung Yu; Bo-Lin Chen; Chuan-Hung Chiu; Mong-Ming Lu; Ching-pin Tung (Stochastic Environmental Research and Risk Assessment, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Anti-tuberculosis treatments and risk of hepatocellular carcinoma in tuberculosis patients with liver cirrhosis: a population-based case–control study - Y.-P. Lim; C.-L. Lin; D.-Z. Hung; Y.-N. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Rhizobium capsici sp. nov., isolated from root tumor of a green bell pepper (Capsicum annuum var. grossum) plant - Shih-Yao Lin; Mei-Hua Hung; Asif Hameed; You-Cheng Liu; Yi-Han Hsu; Cheng-Zhe Wen; A. B. Arun; Hans-Jürgen Busse; Stefanie P. Glaeser; Peter Kämpfer; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Influences of environmental and spatial factors on genetic and epigenetic variations in Rhododendron oldhamii (Ericaceae) - Chun-Lin Huang; Jui-Hung Chen; Ming-Hsuan Tsang; Jeng-Der Chung; Chung-Te Chang; Shih-Ying Hwang (Tree Genetics & Genomes, 2015)

Interaction between Nm23 and the tumor suppressor VHL - Chih-Hung Lin; Vincent Dammai; Boris Adryan; Tien Hsu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

The Akt inhibitor MK-2206 enhances the cytotoxicity of paclitaxel (Taxol) and cisplatin in ovarian cancer cells - Ying-Hsi Lin; Bert Yu-Hung Chen; Wei-Ting Lai; Shao-Fu Wu; Jih-Hwa Guh; Ann-Lii Cheng; Lih-Ching Hsu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity - Yun-Ping Lim; Ching-Hao Cheng; Wei-Cheng Chen; Shih-Yu Chang; Dong-Zong Hung; Jih-Jung Chen; Lei Wan; Wei-Chih Ma; Yu-Hsien Lin; Cing-Yu Chen; Tsuyoshi Yokoi; Miki Nakajima; et al. (Archives of Toxicology, 2015)

Predicting 3D pose in partially overlapped X-ray images of knee prostheses using model-based Roentgen stereophotogrammetric analysis (RSA) - Chi-Pin Hsu; Shang-Chih Lin; Kao-Shang Shih; Chang-Hung Huang; Chian-Her Lee (Medical & Biological Engineering & Computing, 2014)

Effects of colony size and polyp position on polyp fecundity in the scleractinian coral genus Acropora - Yoko Nozawa; Che-Hung Lin (Coral Reefs, 2014)

Development, characterization and cross-species amplification of new microsatellite primers from an endemic species Cinnamomum kanehirae (Lauraceae) in Taiwan - Kuo-Hsiang Hung; Chia-Hung Lin; Huei-Chuan Shih; Yu-Chung Chiang; Li-Ping Ju (Conservation Genetics Resources, 2014)

Outdoor thermal comfort characteristics in the hot and humid region from a gender perspective - Chien-Hung Tung; Chen-Peng Chen; Kang-Ting Tsai; Noémi Kántor; Ruey-Lung Hwang; Andreas Matzarakis; Tzu-Ping Lin (International Journal of Biometeorology, 2014)

Influence of gene flow on divergence dating – implications for the speciation history of Takydromus grass lizards - Shu‐Ping Tseng; Shou‐Hsien Li; Chia‐Hung Hsieh; Hurng‐Yi Wang; Si‐Min Lin (Molecular Ecology, 2014)
Dating the time of divergence and understanding speciation processes are central to the study of the evolutionary history of organisms but are notoriously difficult. The difficulty is largely rooted in variations in the ancestral population size or in the genealogy variation across loci. To depict the speciation processes and divergence histories of three monophyletic Takydromus species endemic to Taiwan, we sequenced 20 nuclear loci and combined with one mitochondrial locus published in GenBank. They were analysed by a multispecies coalescent approach within a Bayesian framework. Divergence dating based on the gene tree approach showed high variation among loci, and the divergence was estimated at an earlier date than when derived by the species‐tree approach. To test whether variations in the ancestral population size accounted for the majority of this variation, we conducted computer inferences using isolation‐with‐migration ( IM ) and approximate Bayesian computation ( ABC ) frameworks. The results revealed that gene flow during the early stage of speciation was strongly favoured over the isolation model, and the initiation of the speciation process was far earlier than the dates estimated by gene‐ and species‐based divergence dating. Due to their limited dispersal ability, it is suggested that geographical isolation may have played a major role in the divergence of these Takydromus species. Nevertheless, this study reveals a more complex situation and demonstrates that gene flow during the speciation process cannot be overlooked and may have a great impact on divergence dating. By using multilocus data and incorporating Bayesian coalescence approaches, we provide a more biologically realistic framework for delineating the divergence history of Takydromus .

A dual tyrosine kinase inhibitor lapatinib suppresses overexpression of matrix metallopeptidase 1 (MMP1) in endometrial cancer - Chiao-Yun Lin; Angel Chao; Tzu-Hao Wang; Swei Hsueh; Yun-Shien Lee; Tzu-I Wu; An-Shine Chao; Huei-Jean Huang; Hung-Hsueh Chou; Ting-Chang Chang; Chyong-Huey Lai (Journal of Molecular Medicine, 2014)

Management of groundwater in farmed pond area using risk-based regulation - Jun-Ying Huang; Chiao-Miao Liao; Kao-Hung Lin; Cheng-Haw Lee (Environmental Monitoring and Assessment, 2014)

Expression of the broccoli catalase gene (BoCAT) enhances heat tolerance in transgenic Arabidopsis - Chih-Ming Chiang; Shi-Peng Chen; Long-Fang O. Chen; Ming-Chang Chiang; Hao-Lun Chien; Kuan-Hung Lin (Journal of Plant Biochemistry and Biotechnology, 2014)

Modulation of angiogenesis by thyroid hormone and hormone analogues: implications for cancer management - Shaker A. Mousa; Hung-Yun Lin; Heng Yuan Tang; Aleck Hercbergs; Mary K. Luidens; Paul J. Davis (Angiogenesis, 2014)

Mitochondrial DNA phylogeography of Semisulcospira libertina (Gastropoda: Cerithioidea: Pleuroceridae): implications the history of landform changes in Taiwan - Kui-Ching Hsu; Hor Bor; Hung-Du Lin; Po-Hsun Kuo; Mian-Shin Tan; Yuh-Wen Chiu (Molecular Biology Reports, 2014)

Characteristics of endogenous γ-aminobutyric acid (GABA) in human platelets: functional studies of a novel collagen glycoprotein VI inhibitor - Kuan-Hung Lin; Wan-Jung Lu; Shwu-Huey Wang; Tsorng-Harn Fong; Duen-Suey Chou; Chao-Chien Chang; Nen-Chung Chang; Yung-Chen Chiang; Shih-Yi Huang; Joen-Rong Sheu (Journal of Molecular Medicine, 2014)

Aryl hydrocarbon receptor (AhR) agonists increase airway epithelial matrix metalloproteinase activity - Ming-Ju Tsai; Ya-Lin Hsu; Tsu-Nai Wang; Ling-Yu Wu; Chi-Tun Lien; Chih-Hsing Hung; Po-Lin Kuo; Ming-Shyan Huang (Journal of Molecular Medicine, 2014)

Fractured-bedrock aquifer studies based on a descriptive statistics of well-logging data: A case study from the Dajia River basin, Taiwan - Po-Yi Chou; Shih-Meng Hsu; Po-Jui Chen; Jung-Jun Lin; Hung-Chieh Lo (Acta Geophysica, 2014)

Biomechanical analysis and design of a dynamic spinal fixator using topology optimization: a finite element analysis - Hung-Ming Lin; Chien-Lin Liu; Yung-Ning Pan; Chang-Hung Huang; Shih-Liang Shih; Shun-Hwa Wei; Chen-Sheng Chen (Medical & Biological Engineering & Computing, 2014)

Anti-apoptotic protein BRE/BRCC45 attenuates apoptosis through maintaining the expression of caspase inhibitor XIAP in mouse Lewis lung carcinoma D122 cells - Yiu-Loon Chui; Chun-Hung Ma; Wei Li; Zhenyu Xu; Yao Yao; Frances Ka-Yin Lin; John Yeuk-Hon Chan; Kenneth Ka-Ho Lee (Apoptosis, 2014)

Molecular, structural, and phylogenetic characterization of two chlorophyllase isoforms in Pachira macrocarpa - Miles Chih-Ming Chen; Jay-How Yang; Chiao-Hui Liu; Kuan-Hung Lin; Chi-Ming Yang (Plant Systematics and Evolution, 2014)

GIS and SBF for estimating groundwater recharge of a mountainous basin in the Wu River watershed, Taiwan - HSIN-FU YEH; HUNG-I LIN; SHING-TSZ LEE; MIN-HSIANG CHANG; KUO-CHIN HSU; CHENG-HAW LEE (Journal of Earth System Science, 2014)

Cloning and gene expression analysis of sponge gourd ascorbate peroxidase gene and winter squash superoxide dismutase gene under respective flooding and chilling stresses - Chih Ming Chiang; Wen Shuo Kuo; Kuan Hung Lin (Horticulture, Environment, and Biotechnology, 2014)

Using ADABOOST and Rough Set Theory for Predicting Debris Flow Disaster - Ping-Feng Pai; Lan-Lin Li; Wei-Zhan Hung; Kuo-Ping Lin (Water Resources Management, 2014)

Fatty Acid Methyl Esters and Solutol HS 15 Confer Neuroprotection after Focal and Global Cerebral Ischemia - Hung Wen Lin; Isabel Saul; Victoria L. Gresia; Jake T. Neumann; Kunjan R. Dave; Miguel A. Perez-Pinzon (Translational Stroke Research, 2014)

Synthesis and anti-cancer activity of a glycosyl library of $$\varvec{N}$$ N -acetylglucosamine-bearing oleanolic acid - Yi-Bing Zeng; Hsin-Min Hsiao; She-Hung Chan; Ying-Hsin Wang; You-Yu Lin; Yu-Hsuan Kuo; Jih-Hwa Guh; Pi-Hui Liang (Molecular Diversity, 2014)

pIMP-PH114 Carrying bla IMP-4 in a Klebsiella pneumoniae Strain is Closely Related to Other Multidrug-Resistant IncA/C2 Plasmids - Pak-Leung Ho; Wai-U Lo; Jane Chan; Yuk-Yam Cheung; Kin-Hung Chow; Wing-Cheong Yam; Chi-Ho Lin; Tak-Lun Que (Current Microbiology, 2014)

The Role of Pentacyclic Triterpenoids in the Allelopathic Effects of Alstonia scholaris - Chao-Min Wang; Hsiao-Ting Chen; Tsai-Chi Li; Jen-Hsien Weng; Yun-Lian Jhan; Shi-Xun Lin; Chang-Hung Chou (Journal of Chemical Ecology, 2014)

An Electromagnetic Thermotherapy System with a Deep Penetration Depth for Percutaneous Thermal Ablation - Sheng-Chieh Huang; Yi-Yuan Chang; Jui-Wen Kang; Hung-Wen Tsai; Yan-Shen Shan; Xi-Zhang Lin; Gwo-Bin Lee (Annals of Biomedical Engineering, 2014)

Functional Investigation of Transmembrane Helix 3 in H+-Translocating Pyrophosphatase - Ching-Hung Lee; Yen-Wei Chen; Yun-Tzu Huang; Yih-Jiuan Pan; Chien-Hsien Lee; Shih-Ming Lin; Lin-Kun Huang; Yueh-Yu Lo; Yu-Fen Huang; Yu-Di Hsu; Shih-Chung Yen; Jenn-Kang Hwang; et al. (The Journal of Membrane Biology, 2013)

Aerosol characteristics of different types of episode - Chung-Yih Kuo; Yan-Ruei Lin; Shih-Yu Chang; Chuan-Yao Lin; Chun-Hung Chou (Environmental Monitoring and Assessment, 2013)

Arbuscular mycorrhizal fungi induced differential Cd and P phytoavailability via intercropping of upland kangkong (Ipomoea aquatica Forsk.) with Alfred stonecrop (Sedum alfredii Hance): post-harvest study - Junli Hu; Jintian Li; Fuyong Wu; Shengchun Wu; Zhihong Ye; Xiangui Lin; Ming Hung Wong (Environmental Science and Pollution Research, 2013)

Altered molecular repertoire of immune system by renal dysfunction in the elderly: is prediction and targeted prevention in the horizon? - Cheng-Lin Lang; Min-Hui Wang; Kuan-Yu Hung; Chih-Kang Chiang; Kuo-Cheng Lu (EPMA Journal, 2013)
Background Patients on chronic hemodialysis (HD) have impaired cellular and humoral immunity. The percentage of elderly people among the total population in Taiwan is increasing dramatically, and HD is the primary alternative for renal replacement therapy when renal function declines. Activated vitamin D is widely used in HD patients with secondary hyperparathyroidism (SHPT) and is a well-known immunomodulatory agent. Personalized medicine and integrative medical approach has been a trend in current clinical practice. Can we improve their immune function using vitamin D in spite of the mineral aspect? Here, we investigated the relationship between serum 25-hydroxyvitamin D (25(OH)D) level and T cell differentiation in chronic HD patients. Methods Forty patients with chronic HD were enrolled. HD patients with SHPT had been treated with activated vitamin D for 3 months. Peripheral blood mononuclear cells obtained from the patients were cultured and stimulated by mitogens, and T cells were analyzed by flow cytometry. Serum 25(OH)D levels were detected by enzyme-linked immunosorbent assay. Results The incidence of T cell differentiation to the T helper cell (Th)2 subtype was more prevalent in the elderly group than in the controls ( p = 0.001). Th2 differentiation was also correlated with age ( p = 0.004) and serum 25(OH)D levels ( p < 0.05). After treated with activated vitamin D, the level of Th1 cytokines decreased while the Th2 cytokine level increased in the sera ( p < 0.05). The T cell differentiation tended toward the Th2 subtype ( p = 0.027) after treatment of activated vitamin D in SHPT patients. Conclusions These results demonstrated that Th2 differentiation is correlated with age and the serum 25(OH)D level of patients. Treatment with activated vitamin D influenced T cell differentiation and cytokine expression in SHPT patients. Taking vitamin D is the possible prediction and targeted treatment in the immune dysfunction in chronic HD patients.

Benzodiazepine therapy in psychiatric outpatients is associated with deliberate self-poisoning events at emergency departments—a population-based nested case–control study - Hsin-I Shih; Ming-Chia Lin; Che-Chen Lin; Hsiang-Chin Hsu; Hsin-Ling Lee; Chih-Hsien Chi; Fung-Chang Sung; Yen-Jung Chang; Chia-Hung Kao (Psychopharmacology, 2013)

Molecular Characterization of an Atypical IncX3 Plasmid pKPC-NY79 Carrying bla KPC-2 in a Klebsiella pneumoniae - Pak-Leung Ho; Yuk-Yam Cheung; Wai-U Lo; Zhen Li; Kin-Hung Chow; Chi-Ho Lin; Jasper Fuk-Woo Chan; Vincent Chi-Chung Cheng (Current Microbiology, 2013)

Phonographic signal with a fractional-order chaotic system: a novel and simple algorithm for analyzing residual arteriovenous access stenosis - Wei-Ling Chen; Tainsong Chen; Chia-Hung Lin; Pei-Jarn Chen; Chung-Dann Kan (Medical & Biological Engineering & Computing, 2013)

An approach to evaluate groundwater recharge from streamflow and groundwater records - Wen-Jui Kung; Hsin-Fu Yeh; Hung-I Lin; Wei-Ping Chen; Cheng-Haw Lee (Geosciences Journal, 2013)

Identification and Characterization of an Extracellular Alkaline Phosphatase in the Marine Diatom Phaeodactylum tricornutum - Hung-Yun Lin; Chi-Yu Shih; Hung-Chun Liu; Jeng Chang; Ying-Lan Chen; Yet-Ran Chen; Han-Tso Lin; Yu-Yung Chang; Chun-Hua Hsu; Han-Jia Lin (Marine Biotechnology, 2013)

Emission factor of exhaust gas constituents during the pyrolysis of zinc chloride immersed biosolid - Hung-Lung Chiang; Kuo-Hsiung Lin; Hua-Hsien Chiu (Environmental Science and Pollution Research, 2013)

Effect of acute DHEA administration on free testosterone in middle-aged and young men following high-intensity interval training - Te-Chih Liu; Che-Hung Lin; Chih-Yang Huang; John L. Ivy; Chia-Hua Kuo (European Journal of Applied Physiology, 2013)

Estimation of phosphorus flux in rivers during flooding - Yen-Chang Chen; Jih-Hung Liu; Jan-Tai Kuo; Cheng-Fang Lin (Environmental Monitoring and Assessment, 2013)

Reduction of connexin43 in human endothelial progenitor cells impairs the angiogenic potential - Hsueh-Hsiao Wang; Cheng-Huang Su; Yih-Jer Wu; Jiun-Yi Li; Ya-Ming Tseng; Yi-Chun Lin; Chin-Ling Hsieh; Cheng-Ho Tsai; Hung-I Yeh (Angiogenesis, 2013)

Inhibition of formyl peptide-stimulated phospholipase D activation by Fal-002-2 via blockade of the Arf6, RhoA and protein kinase C signaling pathways in rat neutrophils - Ya-Ru Tsai; Li-Jiau Huang; Hui-Yi Lin; Yun-Jie Hung; Miau-Rong Lee; Sheng-Chu Kuo; Mei-Feng Hsu; Jih-Pyang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Application of a feature-based approach to debris flow detection by numerical simulation - Chih-Wei Lin; Cheng-Wu Chen; Wen-Ko Hsu; Chia-Yen Chen; Chung-Hung Tsai; Yi-Ping Hung; Wei-Ling Chiang (Natural Hazards, 2013)

MicroRNA-210 targets antiapoptotic Bcl-2 expression and mediates hypoxia-induced apoptosis of neuroblastoma cells - Chung-Ching Chio; Jia-Wei Lin; Heien-An Cheng; Wen-Ta Chiu; Yuan-Hung Wang; Jhi-Joung Wang; Chung-Hsi Hsing; Ruei-Ming Chen (Archives of Toxicology, 2013)

The construction of a high-resolution visual monitoring for hazard analysis - Chi-Wei Lin; Yi-Ping Hung; Wen-Ko Hsu; Wei-Ling Chiang; Cheng-Wu Chen (Natural Hazards, 2013)

Estrogen stimulates the proliferation of human endometrial cancer cells by stabilizing nucleophosmin/B23 (NPM/B23) - Angel Chao; Chiao-Yun Lin; Chia-Lung Tsai; Swei Hsueh; Ying-Yu Lin; Cheng-Tao Lin; Hung-Hsueh Chou; Tzu-Hao Wang; Chyong-Huey Lai; Hsin-Shih Wang (Journal of Molecular Medicine, 2013)

Arbuscular mycorrhizal fungal diversity, external mycelium length, and glomalin-related soil protein content in response to long-term fertilizer management - Jue Dai; Junli Hu; Xiangui Lin; Anna Yang; Rui Wang; Jiabao Zhang; Ming Hung Wong (Journal of Soils and Sediments, 2013)

Dynamics of cadmium concentration in contaminated rice paddy soils with submerging time - Jang-Hung Huang; Shan-Li Wang; Jhin-Hao Lin; Yue-Ming Chen; Ming-Kuang Wang (Paddy and Water Environment, 2013)

Heat acclimation decreased oxidative DNA damage resulting from exposure to high heat in an occupational setting - Yung-Kai Huang; Che-Wei Lin; Chen-Chen Chang; Pai-Fen Chen; Chien-Jen Wang; Yu-Mei Hsueh; Hung-Che Chiang (European Journal of Applied Physiology, 2012)

Atypical work schedules are associated with poor sleep quality and mental health in Taiwan female nurses - Pei-Chen Lin; Chung-Hey Chen; Shung-Mei Pan; Chih-Hong Pan; Chiou-Jong Chen; Yao-Mei Chen; Hsin-Chia Hung; Ming-Tsang Wu (International Archives of Occupational and Environmental Health, 2012)

Photocatalytic degradation of methyl orange by a multi-layer rotating disk reactor - Chia-Nan Lin; Chih-Yi Chang; Hung Ji Huang; Din Ping Tsai; Nae-Lih Wu (Environmental Science and Pollution Research, 2012)

Rapid sex identification of papaya (Carica papaya) using multiplex loop-mediated isothermal amplification (mLAMP) - Te-Hua Hsu; Jin-Chywan Gwo; Kuan-Hung Lin (Planta, 2012)

Prediction of hydraulically transmissive fractures using geological and geophysical attributes: a case history from the mid Jhuoshuei River basin, Taiwan - Po-Yi Chou; Hung-Chieh Lo; Shih-Meng Hsu; Yen-Tsu Lin; Chi-Chao Huang (Hydrogeology Journal, 2012)

Niacin improves ischemia-induced neovascularization in diabetic mice by enhancement of endothelial progenitor cell functions independent of changes in plasma lipids - Po-Hsun Huang; Chih-Pei Lin; Chao-Hung Wang; Chia-Hung Chiang; Hsiao-Ya Tsai; Jia-Shiong Chen; Feng-Yen Lin; Hsin-Bang Leu; Tao-Cheng Wu; Jaw-Wen Chen; Shing-Jong Lin (Angiogenesis, 2012)

Synergistic effects of streptolysin S and streptococcal pyrogenic exotoxin B on the mouse model of group A streptococcal infection - Chih-Hsin Hung; Nina Tsao; Yi-Fang Zeng; Shiou-Ling Lu; Chuan Chiang-Ni; Yee-Shin Lin; Jiunn-Jong Wu; Chih-Feng Kuo (Medical Microbiology and Immunology, 2012)

Biogeochemical cycling of ferric oxyhydroxide affecting As partition in groundwater aquitard - Sheng-Wei Wang; Chen-Wuing Liu; Kuang-Liang Lu; Li-Hung Lin (Environmental Geochemistry and Health, 2012)

Pleistocene speciation with and without gene flow in Euphaea damselflies of subtropical and tropical East Asian islands - YAT‐HUNG LEE; CHUNG‐PING LIN (Molecular Ecology, 2012)
Climatic oscillations during the Pleistocene period could have had a profound impact on the origin of tropical species by the alternation of allopatric isolation and interpopulation gene flow cycles. However, whether tropical speciation involves strictly allopatric isolation, or proceeds in the face of homogenizing gene flow, is relatively unclear. Here, we investigated geographical modes of speciation in four closely related Euphaea damselfly species endemic to the subtropical and tropical East Asian islands using coalescent analyses of a multilocus data set. The reconstructed phylogenies demonstrated distinct species status for each of the four species and the existence of two sister species pairs, Euphaea formosa / E. yayeyamana and E. decorata / E. ornata . The species divergence time of the sibling Euphaea damselflies dates back to within the last one Mya of the Middle to Lower Pleistocene. The speciation between the populous E. formosa of Taiwan and the less numerous E. yayeyamana of the Yaeyama islands occurred despite significant bidirectional, asymmetric gene flow, which is strongly inconsistent with a strictly allopatric model. In contrast, speciation of the approximately equal‐sized populations of E. decorata of the southeast Asian mainland and E. ornata of Hainan is inferred to have involved allopatric divergence without gene flow. Our findings suggest that differential selection of natural or sexual environments is a prominent driver of species divergence in subtropical E. formosa and E. yayeyamana ; whereas for tropical E. decorata and E. ornata at lower latitudes, allopatric isolation may well be a pivotal promoter of species formation.

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Arbuscular mycorrhizal fungal community structure and diversity in response to 3-year conservation tillage management in a sandy loam soil in North China - Anna Yang; Junli Hu; Xiangui Lin; Anning Zhu; Junhua Wang; Jue Dai; Ming Hung Wong (Journal of Soils and Sediments, 2012)

Response to “Letter to editor re: Ling et al. 2011 (Environ Sci Pollut Res Int 18(6): 877–889)” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Response to “Dr. Luca Giannini’s Letter to the Editor” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Response to “Letter to Editor: Inappropriate exposure data and misleading calculations invalidate the estimates of health risk for airborne titanium dioxide and carbon black nanoparticle exposures in the workplace” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Identification and characterization of an indigo-producing oxygenase involved in indole 3-acetic acid utilization by Acinetobacter baumannii - Guang-Huey Lin; Hao-Ping Chen; Jui-Hsin Huang; Tze-Tze Liu; Tze-Kang Lin; Shih-Jon Wang; Cheng-Hsing Tseng; Hung-Yu Shu (Antonie van Leeuwenhoek, 2012)

Preferential involvement of mitochondria in Toll-like receptor 3 agonist-induced neuroblastoma cell apoptosis, but not in inhibition of cell growth - Jiin-Haur Chuang; Tsu-Kung Lin; Ming-Hong Tai; Chia-Wei Liou; Sheng-Teng Huang; Chia-Ling Wu; Hung-Yi Lin; Pei-Wen Wang (Apoptosis, 2012)

Microbial methane cycling in a terrestrial mud volcano in eastern Taiwan - Yung‐Hsin Chang; Ting‐Wen Cheng; Wen‐Jing Lai; Wen‐Yu Tsai; Chih‐Hsien Sun; Li‐Hung Lin; Pei‐Ling Wang (Environmental Microbiology, 2012)
Summary Microbial communities responsible for methane cycling in mud volcanoes onshore are poorly characterized. This study analysed bubbling fluids and cored sediments retrieved from a mud volcano in eastern Taiwan. The pore water profiles revealed that methane concentrations generally increased with depth and changed dramatically at different depth intervals at different sites. The methane concentrations were inversely correlated with Fe 2+ /Mn 2+ concentrations and δ 13 C values of methane, marking iron/manganese‐methane transition zones in the sediment cores. Archaeal communities were dominated by ANME‐2a members and methylotrophic methanogens, whereas bacterial communities consisted primarily of Proteobacteria, Firmicutes and Bacteroidetes . The 16S rRNA gene copy numbers of ANME‐2a and Desulfuromonas / Pelobacter populations varied by two to three orders of magnitude along the profile and exhibited a pattern comparable with those of Fe 2+ and δ 13 C values of methane. These lines of evidence suggest a coupling between anaerobic methanotrophy and metal reduction in the metal‐methane transition zones under sulfate‐deficient conditions, a metabolic scheme contrasting with that observed in marine cold seeps. Anaerobic methanotrophs proliferate by removing methane produced from in situ methanogenesis and originating from the deep source. Methane finally emitted into the atmosphere is quantitatively and isotopically altered by various microbial processes compartmentalized at different depth intervals.

Neuroprotection by marine-derived compound, 11-dehydrosinulariolide, in an in vitro Parkinson’s model: a promising candidate for the treatment of Parkinson’s disease - Wu-Fu Chen; Chiranjib Chakraborty; Chun-Sung Sung; Chien-Wei Feng; Yen-Hsuan Jean; Yen-You Lin; Han-Chun Hung; Tzu-Yi Huang; Shi-Ying Huang; Thung-Ming Su; Ping-Jyun Sung; Jyh-Horng Sheu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

A study of genetic variations, population size, and population dynamics of the catadromous Japanese eel Anguilla japonica (Pisces) in northern Taiwan - Mei-Chen Tseng; Hsiao-Wei Kao; Yin-Huei Hung; Tung-Lin Lee (Hydrobiologia, 2012)

A spatial aggregation index for effective fallow decision in paddy irrigation demand planning - Ming-Daw Su; Mei-Chun Lin; Chun-Hung Lin; Shih-Fu Wang; Tzai-Hung Wen; Hsin-I Hsieh (Paddy and Water Environment, 2012)

Effect of pH on the Analysis of 2-MIB and Geosmin in Water - Wen-Hsing Hsieh; Wei-Nung Hung; Gen-Shuh Wang; Shu-Ting Hsieh; Tsair-Fuh Lin (Water, Air, & Soil Pollution, 2012)

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

HepG2 cells infected with Klebsiella pneumoniae show DNA laddering at apoptotic and necrotic stages - Pei-Yin Yang; Wen-Xin Chen; Fong-Yin Chang; Hui-Wen Chen; Chun-Hung Lin; Yu-Chun Hsu; June Hsieh Wu (Apoptosis, 2012)

Suburban atmospheric visibility sensing by an image degradation processor: model development and field test - Chin-Hsiang Luo; Kuo-Hung Lin; Che-Yen Wen; Shih-Hsuan Chiu; Chung-Shin Yuan; Shinhao Yang (International Journal of Remote Sensing, 2011)

Attribute-Based Design Space: Materials-Science-Based Quality-By-Design for Operational Flexibility and Process Portability - James N. Michaels; Holly Bonsignore; Buffy L. Hudson-Curtis; Steven Laurenz; Hung-Ren Homer Lin; Thomas Mathai; Girish Pande; Ashlesh Sheth; Omar Sprockel (Journal of Pharmaceutical Innovation, 2011)

Avian reovirus S1133-induced DNA damage signaling and subsequent apoptosis in cultured cells and in chickens - Ping-Yuan Lin; Hung-Jen Liu; Ching-Dong Chang; Chi-I Chang; Jue-Liang Hsu; Ming-Huei Liao; Jeng-Woei Lee; Wen-Ling Shih (Archives of Virology, 2011)

Nitric oxide activates superoxide dismutase and ascorbate peroxidase to repress the cell death induced by wounding - Chih-Ching Lin; Pei-Ju Jih; Hsin-Hung Lin; Jeng-Shane Lin; Ling-Lan Chang; Yu-Hsing Shen; Shih-Tong Jeng (Plant Molecular Biology, 2011)

Factors affecting lipid accumulation by Nannochloropsis oculata in a two-stage cultivation process - Chia-Hung Su; Liang-Jung Chien; James Gomes; Yu-Sheng Lin; Yuan-Kun Yu; Jhang-Song Liou; Rong-Jhih Syu (Journal of Applied Phycology, 2011)

Molecular evolution of a family of resistance gene analogs of nucleotide-binding site sequences in Solanum lycopersicum - Pei-Chun Liao; Kuan-Hung Lin; Chin-Ling Ko; Shih-Ying Hwang (Genetica, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Phylogeography and the genetic structure of the land-locked freshwater prawn Macrobrachium asperulum (Crustacea: Decapoda: Palaemonidae) in Taiwan - Min-Yun Liu; Chyng-Shyan Tzeng; Hung-Du Lin (Hydrobiologia, 2011)

Assessing the potential exposure risk and control for airborne titanium dioxide and carbon black nanoparticles in the workplace - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2011)

Characterization of a salt-tolerant xylanase from Thermoanaerobacterium saccharolyticum NTOU1 - Kuo-Sheng Hung; Shiu-Mei Liu; Tsuei-Yun Fang; Wen-Shyong Tzou; Fu-Pang Lin; Kuang-Hui Sun; Shye-Jye Tang (Biotechnology Letters, 2011)

2010 oil spill: trajectory projections based on ensemble drifter analyses - Yu-Lin Chang; Leo Oey; Fang-Hua Xu; Hung-Fu Lu; Ayumi Fujisaki (Ocean Dynamics, 2011)

Decreased expression of Flightless I, a gelsolin family member and developmental regulator, in early-gestation fetal wounds improves healing - Cheng-Hung Lin; James M. Waters; Barry C. Powell; Ruth M. Arkell; Allison J. Cowin (Mammalian Genome, 2011)

A Protocol for Characterizing the Impact of Collateral Flow after Distal Middle Cerebral Artery Occlusion - Richard Anthony DeFazio; Sean Levy; Carmen L. Morales; Rebecca V. Levy; Hung W. Lin; Tatjana Abaffy; Kunjan R. Dave; Brant D. Watson; Miguel A. Perez-Pinzon; Victoria Ohanna (Translational Stroke Research, 2011)

Population structure of Nouelia insignis (Asteraceae), an endangered species in southwestern China, based on chloroplast DNA sequences: recent demographic shrinking - Xun Gong; Shan-Shan Luan; Kuo-Hsiang Hung; Chi-Chuan Hwang; Chung-Jean Lin; Yu-Chung Chiang; Tzen-Yuh Chiang (Journal of Plant Research, 2011)

Microbial functional diversity, metabolic quotient, and invertase activity of a sandy loam soil as affected by long-term application of organic amendment and mineral fertilizer - Junli Hu; Xiangui Lin; Junhua Wang; Jue Dai; Ruirui Chen; Jiabao Zhang; Ming Hung Wong (Journal of Soils and Sediments, 2011)

Phylogenetic position of a threatened stag beetle, Lucanus datunensis (Coleoptera: Lucanidae) in Taiwan and implications for conservation - Chung-Ping Lin; Jen-Pan Huang; Yat-Hung Lee; Ming-Yu Chen (Conservation Genetics, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Trace Analysis of N-Nitrosamines in Water Using Solid-Phase Microextraction Coupled with Gas Chromatograph–Tandem Mass Spectrometry - Hsu-Wen Hung; Tsair-Fuh Lin; Chuen-Huey Chiu; Ya-Chi Chang; Tung-Ying Hsieh (Water, Air, & Soil Pollution, 2010)

Prospective variants screening of connexin genes in children with hearing impairment: genotype/phenotype correlation - Jiann-Jou Yang; Wen-Hung Wang; Yen-Chun Lin; Hsu-Huei Weng; Jen-Tsung Yang; Chung-Feng Hwang; Che-Min Wu; Shuan-Yow Li (Human Genetics, 2010)

Transferability of rice SSR markers to bamboo - Shu-Yun Chen; Yu-Tsung Lin; Chia-Wei Lin; Wei-Yu Chen; Chih Hung Yang; Hsin-Mei Ku (Euphytica, 2010)

Planning for Implementation of Riparian Buffers in the Feitsui Reservoir Watershed - Chia-Ling Chang; Tsung-Hung Hsu; Yunn-Jiin Wang; Jen-Yang Lin; Shaw L. Yu (Water Resources Management, 2010)

Therapeutic HPV DNA vaccines - Ken Lin; Elena Roosinovich; Barbara Ma; Chien-Fu Hung; T.-C. Wu (Immunologic Research, 2010)

Quantitative trait loci influencing fruit-related characteristics of tomato grown in high-temperature conditions - Kuan-Hung Lin; Wei-Lung Yeh; Huei-Mei Chen; Hsiao-Feng Lo (Euphytica, 2010)

Identification of Flooding-Response Genes in Eggplant Roots by Suppression Subtractive Hybridization - Kuan-Hung Lin; Chun-Heng Lin; Ming-Tsir Chan; Hsiao-Feng Lo (Plant Molecular Biology Reporter, 2010)

Cloning, expression and physiological analysis of broccoli catalase gene and Chinese cabbage ascorbate peroxidase gene under heat stress - Kuan-Hung Lin; Ho-Chang Huang; Ching-Yun Lin (Plant Cell Reports, 2010)

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

Porcine lactoferrin as feedstuff additive elevates avian immunity and potentiates vaccination - Che-Ming Hung; Shinn-Chih Wu; Chih-Ching Yen; Ming-Fong Lin; Yi-Wen Lai; Yu-Tang Tung; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2010)

Response surface optimization of dissolved oxygen and nitrogen sources for the biodegradation of MTBE and BTEX - Chi-Wen Lin; Chia-Hsien Yen; Hung-Chun Lin; Dang-Thuan Tran (Biodegradation, 2010)

Isolation of new esters from the stems of Cinnamomum reticulatum Hay - Iung-Jr Lin; Wen-Li Lo; Yi-Chen Chia; Lee-Yu Huang; Thau-Ming Cham; Wan-Shan Tseng; Yu-Ting Yeh; Hung-Chun Yeh; Yau-Der Wang; Chung-Yi Chen (Natural Product Research, 2010)

A storm event-based approach to TMDL development - Tsung-Hung Hsu; Jen-Yang Lin; Tsu-Chuan Lee; Harry X. Zhang; Shaw L. Yu (Environmental Monitoring and Assessment, 2010)

Monoamine oxidase A gene polymorphisms and enzyme activity associated with risk of gout in Taiwan aborigines - Hung-Pin Tu; Albert Min-Shan Ko; Shu-Jung Wang; Chien-Hung Lee; Rod A. Lea; Shang-Lun Chiang; Hung-Che Chiang; Tsu-Nai Wang; Meng-Chuan Huang; Tsan-Teng Ou; Gau-Tyan Lin; Ying-Chin Ko (Human Genetics, 2010)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Fractionated evaluation of immunohistochemical hormone receptor expression enhances prognostic prediction in breast cancer patients treated with tamoxifen as adjuvant therapy - Ching-hung Lin; Huang-chun Lien; Fu-chang Hu; Yen-shen Lu; Sung-hsin Kuo; Ling-chu Wu; San-lin You; Ann-lii Cheng; King-jen Chang; Chiun-sheng Huang (Journal of Zhejiang University-SCIENCE B, 2010)

A Non-fluorescent Derivative from Derivatizing trans, trans-Muconic Acid with 2-(2-Naphthoxy)ethyl-2-(piperidino)ethanesulfonate - Tang-Chia Chung; Wung-Pung Su; Hwang-Shang Kou; Yu-Ting Lin; Min-Yuan Hung; Hsin-Lung Wu (Journal of Fluorescence, 2010)

FORMOSAT-3/COSMIC observations of the ionospheric auroral oval development - Ho-Fang Tsai; Jann-Yenq Liu; Chien-Hung Lin; Mei-Lan Hsu (GPS Solutions, 2010)

Phylogeography of Hemibarbus labeo (Cyprinidae): secondary contact of ancient lineages of mtDNA - Chung‐Jian Lin; Hung‐Du Lin; Jiang‐Ping Wang; Seau‐Chiou Chao; Tzen‐Yuh Chiang (Zoologica Scripta, 2010)
Lin, C.‐J., Lin, H.‐D., Wang, J.‐P., Chao, S.‐C. & Chiang, T.‐Y. (2007). Phylogeography of Hemibarbus labeo (Cyprinidae): secondary contact of ancient lineages of mtDNA. — Zoologica Scripta, 39 , 23–35. Nucleotide sequences of the D‐loop control region of mtDNA were used to assess the genetic structure and phylogeography of Hemibarbus labeo in Mainland China and Taiwan. A hierarchical analysis of molecular variance of populations in 11 major streams from three geographical regions revealed significant structuring among populations and geographical regions. High levels of nucleotide diversity ( π = 1.88%) and haplotype diversity ( h = 96 ± 0.009%) suggest a large effective population size. A maximum likelihood tree based on mtDNA variation identified two ancient mtDNA lineages, which split approximately 3.39 million years ago. Overlapping distribution of the major lineages displayed low correspondence with geographical regions and reflects a scenario of secondary mergence after long isolation. Gene genealogy further revealed a unidirectional migration. Nevertheless, there existed a phylogeographical structure that mostly agreed with a biogeographical hypothesis. That is, within each lineage, a close phylogeny between populations of the River‐Campagna and East‐Pacific regions was supported by the mtDNA gene genealogy, although monophyly of each geographical region was not supported. The degree of genetic differentiation was correlated with geographical distances between populations, displaying a pattern of ‘isolation by distance’. Gene genealogy of mtDNA revealed that Yangtzejiang population may act as a divergence centre of H. labeo . In addition, Taiwan population was colonized via a recent a founder event, likely from population Yangtzejiang River about 131 000 years before present. Low haplotype number and genetic variability also suggested possible bottleneck events in the Rongjiang and Dazhangjiang populations.

Therapeutic potential of olfactory ensheathing cells in neurodegenerative diseases - Shao-Chih Chiu; Huey-Shan Hung; Shinn-Zong Lin; Esheral Chiang; Demeral David Liu (Journal of Molecular Medicine, 2009)

Determination of shallow water depth using optical satellite images - Hung-Ming Kao; Hsuan Ren; Chao-Shing Lee; Chung-Pa Chang; Jiun-Yee Yen; Tang-Huang Lin (International Journal of Remote Sensing, 2009)

Alterations in Trace Elements and Oxidative Stress in Uremic Patients with Dementia - Chih-Hung Guo; Wang-Sheng Ko; Pei-Chung Chen; Guoo-Shyng W. Hsu; Chia-Yeh Lin; Chia-Liang Wang (Biological Trace Element Research, 2009)

Effects of the multiple polyadenylation signal AAUAAA on mRNA 3′-end formation and gene expression - Hsin-Hung Lin; Li-Fen Huang; Hsiao-Chien Su; Shih-Tong Jeng (Planta, 2009)

Bovine ephemeral fever virus-induced apoptosis requires virus gene expression and activation of Fas and mitochondrial signaling pathway - Chi-Hung Lin; Wen-Ling Shih; Feng-Lang Lin; Yao-Ching Hsieh; Yur-Ren Kuo; Ming-Huei Liao; Hung-Jen Liu (Apoptosis, 2009)

Isolation and characterization of 15 microsatellite loci from Caridina gracilipes (Atyidae, Decapoda) - Chiao-Chuan Han; Cheng-Sheng Chang; Tzen-Yuh Chiang; Ping-Han Chung; Hung-Du Lin (Conservation Genetics, 2009)

Single-Trial Analysis of Cortical Oscillatory Activities During Voluntary Movements Using Empirical Mode Decomposition (EMD)-Based Spatiotemporal Approach - Po-Lei Lee; Li-Zen Shang; Yu-Te Wu; Chih-Hung Shu; Jen-Chuen Hsieh; Yung-Yang Lin; Chi-Hsun Wu; Yu-Lu Liu; Chia-Yen Yang; Chia-Wei Sun; Kuo-Kai Shyu (Annals of Biomedical Engineering, 2009)

Risk-based assessment of arsenic-affected aquacultural water in blackfoot disease hyperendemic areas - Cheng-Shin Jang; Kao-Hung Lin; Chen-Wuing Liu; Ming-Chao Lin (Stochastic Environmental Research and Risk Assessment, 2009)

Bovine ephemeral fever virus-induced apoptosis requires virus gene expression and activation of Fas and mitochondrial signaling pathway - Chi-Hung Lin; Wen-Ling Shih; Feng-Lang Lin; Yao-Ching Hsieh; Yur-Ren Kuo; Ming-Huei Liao; Hung-Jeng Liu (Apoptosis, 2009)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)

Detection of race 1 strains of Ralstonia solanacearum in field samples in Taiwan using a BIO-PCR method - Chih-Hung Lin; Shih-Tien Hsu; Kuo-Ching Tzeng; Jaw-Fen Wang (European Journal of Plant Pathology, 2009)

Rotavirus infection increases the risk of bacteremia in children with nontyphoid Salmonella gastroenteritis - T.-Y. Hung; M.-C. Liu; C.-F. Hsu; Y.-C. Lin (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Analyzing the shear strength parameters of the Chiu-fen-erh-shan landslide: integrating strong-motion and GPS data to determine the best-fit accelerogram - Jian-Hong Wu; Hung-Ming Lin (GPS Solutions, 2009)

Active extracts of wild fruiting bodies of Antrodia camphorata (EEAC) induce leukemia HL 60 cells apoptosis partially through histone hypoacetylation and synergistically promote anticancer effect of trichostatin A - Mei-Chin Lu; Ying-Chi Du; Jiunn-Jye Chuu; Shiuh-Lin Hwang; Pao-Chuan Hsieh; Chih-Sheng Hung; Fang-Rong Chang; Yang-Chang Wu (Archives of Toxicology, 2009)

Isolation and characterization of microsatellite loci in the commercially important mudshrimp Austinogebia edulis (Upogebiidae) using PCR-based isolation of microsatellite arrays (PIMA) - Tzen-Yuh Chiang; Hung-Du Lin; Tin-Yam Chan; Cheng-Yu Hung; Feng-Jiau Lin (Conservation Genetics, 2008)

Isolation and characterization of microsatellite loci in the endangered freshwater fish Varicorhinus alticorpus (Cyprinidae) - Tzen-Yuh Chiang; Teh-Wang Lee; Feng-Jiau Lin; Kuo-Hua Huang; Hung-Du Lin (Conservation Genetics, 2008)

Isolation and characterization of 11 polymorphic microsatellite loci from Fatsia polycarpa (Araliaceae), an element of evergreen forests in Taiwan - Chi-Chun Huang; Kuo-Hsiang Hung; Tsai-Wen Hsu; Kuo-Hsiung Wang; Chi-Yung Lin; Tzen-Yuh Chiang (Conservation Genetics, 2008)

Isolation and characterization of microsatellite loci in the endangered freshwater fish Pararasbora moltrechti (Cyprinidae) using PCR-based isolation of microsatellite arrays (PIMA) - Hung-Du Lin; Teh-Wang Lee; Fang-Jiao Lin; Chung-Jian Lin; Tzen-Yuh Chiang (Conservation Genetics, 2008)

Relationships between physiological responses and presyncope symptoms during tilting up in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2008)

Interleukin-1 receptor antagonist restores homeostatic function and limits multiorgan damage in heatstroke - Kun-Hung Shen; Chen-Kuei Chang; Mao-Tsun Lin; Ching-Ping Chang (European Journal of Applied Physiology, 2008)

Tetraiodothyroacetic acid, a small molecule integrin ligand, blocks angiogenesis induced by vascular endothelial growth factor and basic fibroblast growth factor - Shaker A. Mousa; Joel J. Bergh; Emie Dier; Abdelhadi Rebbaa; Laura J. O’Connor; Murat Yalcin; Ahmad Aljada; Evgeny Dyskin; Faith B. Davis; Hung-Yung Lin; Paul J. Davis (Angiogenesis, 2008)

Spatiotemporal distribution of arsineic species of oysters (Crassostrea gigas) in the coastal area of southwestern Taiwan - Chen-Wuing Liu; Yung-Kay Huang; Yu-Mei Hsueh; Kao-Hung Lin; Cheng-Shin Jang; Lan-Ping Huang (Environmental Monitoring and Assessment, 2008)

Mammalian Ste20-like protein kinase 3 mediates trophoblast apoptosis in spontaneous delivery - Hung-Yi Wu; Chia-Ying Lin; Tze-Yi Lin; Tai-Chang Chen; Chiun-Jye Yuan (Apoptosis, 2008)

Identification and phylogenetic analysis of orf virus from goats in Taiwan - Kun-Wei Chan; Jen-Wei Lin; Shu-Hwae Lee; Chih-Jung Liao; Meng-Chun Tsai; Wei-Li Hsu; Min-Liang Wong; Hung-Chang Shih (Virus Genes, 2007)

Development of a biofeedback tilt-table for investigating orthostatic syncope in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2007)

Culture Duration Modulates Collagen Hydrolysate-Induced Tissue Remodeling in Chondrocyte-Seeded Agarose Hydrogels - Kenneth W. Ng; Justin D. Saliman; Evan Y. Lin; Lauren Y. Statman; Lindsay E. Kugler; Sean B. Lo; Gerard A. Ateshian; Clark T. Hung (Annals of Biomedical Engineering, 2007)

Increase of multi-metal tolerance of three leguminous plants by arbuscular mycorrhizal fungi colonization - Ai-Jun Lin; Xu-Hong Zhang; Ming-Hung Wong; Zhi-Hong Ye; Lai-Qing Lou; You-Shan Wang; Yong-Guan Zhu (Environmental Geochemistry and Health, 2007)

New Molecular Insights into Cellular Survival and Stress Responses: Neuroprotective Role of Cellular Prion Protein (PrPC) - Raymond Yen-Yu Lo; Woei-Cherng Shyu; Shinn-Zong Lin; Hsiao-Jung Wang; Shun-Sheng Chen; Hung Li (Molecular Neurobiology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

New Molecular Insights into Cellular Survival and Stress Responses: Neuroprotective Role of Cellular Prion Protein (PrPC) - Raymond Yen-Yu Lo; Woei-Cherng Shyu; Shinn-Zong Lin; Hsiao-Jung Wang; Shun-Sheng Chen; Hung Li (Molecular Neurobiology, 2007)

The Valuation of Health Effects Caused by Stationary Sources–Related SO2 Emissions: The Adaptation of Impact Pathway Approach in Taiwan - Sheng-Lung Lin; Kuan-Hung Lin (Environmental Monitoring and Assessment, 2007)

Summer distribution and geochemical composition of suspended-particulate matter in the east china sea - Jia-Jang Hung; Chia-Lin Chan; Gong-Ching Gong (Journal of Oceanography, 2007)

Effects of magnesium sulfate on dynamic changes of brain glucose and its metabolites during a short-term forced swimming in gerbils - Shiu-Min Cheng; Dar-Yu Yang; Chien-Pin Lee; Hung-Chuan Pan; Mao-Tsun Lin; Ssu-Hua Chen; Fu-Chou Cheng (European Journal of Applied Physiology, 2007)

The functional haplotype of peptidylarginine deiminase IV (S55G, A82V and A112G) associated with susceptibility to rheumatoid arthritis dominates apoptosis of acute T leukemia Jurkat cells - Hui-Chih Hung; Chien-Yu Lin; Ya-Fan Liao; Pei-Chen Hsu; Gregory J. Tsay; Guang-Yaw Liu (Apoptosis, 2007)

Identification and phylogenetic analysis of orf virus from goats in Taiwan - Kun-Wei Chan; Jen-Wei Lin; Shu-Hwae Lee; Chih-Jung Liao; Meng-Chun Tsai; Wei-Li Hsu; Min-Liang Wong; Hung-Chang Shih (Virus Genes, 2007)

Purification of a trypsin inhibitor from sweet potato in an aqueous two phase system - Kuen-Shan Jaw; Lin Hung Chou; Shiao-Ming Chang; Kow-Jen Duan (Biotechnology Letters, 2006)

Avian Reovirus activates a novel proapoptotic signal by linking Src to p53 - Lin Ping-Yuan; Liu Hung-Jen; Lai Meng-Jiun; Yu Feng-Ling; Hsu Hsue-Yin; Lee Jeng-Woei; Shih Wen-Ling (Apoptosis, 2006)

Antizyme, a natural ornithine decarboxylase inhibitor, induces apoptosis of haematopoietic cells through mitochondrial membrane depolarization and caspases’ cascade - G.-Y. Liu; Y.-F. Liao; P.-C. Hsu; W.-H. Chang; M.-C. Hsieh; C.-Y. Lin; T.-C. Hour; M.-C. Kao; G. J. Tsay; H.-C. Hung (Apoptosis, 2006)

Streptococcal pyrogenic exotoxin B causes mitochondria damage to polymorphonuclear cells preventing phagocytosis of Group A streptococcus - Chuan Chiang-Ni; Chih-Hung Wang; Pei-Jane Tsai; Woei-Jer Chuang; Yee-Shin Lin; Ming-T. Lin; Ching-Chuan Liu; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2006)

Downlink power control in multi-code CDMA for mobile medicine - Chin-Feng Lin; Wen-Thong Chang; Hsin-Wang Lee; Shih-Ii Hung (Medical & Biological Engineering & Computing, 2006)

A GIS Process for Delimitating Areas Potentially Endangered by Debris Flow - Fan-Chieh Yu; Chien-Yuan Chen; Tien-Chien Chen; Feng-Yi Hung; Sheng-Chi Lin (Natural Hazards, 2006)

Stable RNA Interference in Spodoptera frugiperda Cells by a DNA Vector-based Method - Chih-Chien Lin; John T. -A. Hsu; Kai-Ling Huang; Hung-Kuan Tang; Yiu-Kay Lai (Biotechnology Letters, 2006)

Inhibitory effect of trilinolein on endothelin-1-induced c-fos gene expression in cultured neonatal rat cardiomyocytes - Hung-Yu Yang; Ju-Chi Liu; Yen-Ling Chen; Cheng-Hsien Chen; Heng Lin; Jia-Wei Lin; Wen-Ta Chiu; Jin-Jer Chen; Tzu-Hurng Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Gene stacking in Phalaenopsis orchid enhances dual tolerance to pathogen attack - Yuan-Li Chan; Kuang-Hung Lin; Sanjaya; Li-Jen Liao; Wen-Huei Chen; Ming-Tsair Chan (Transgenic Research, 2005)

Expression studies of mutations underlying Taiwanese Hunter syndrome (mucopolysaccharidosis type II) - Jui-Hung Chang; Shuan-Pei Lin; Shu-Chuan Lin; Kai-Li Tseng; Chia-Ling Li; Chih-Kuang Chuang; Guey-Jen Lee-Chen (Human Genetics, 2005)

Anti-hepatitis B surface antigen IgG1 subclass is predominant in individuals who have recovered from hepatitis B virus infection, chronic carriers and vaccinees - Lina Wang; Shyh-Jye Lin; Ju-Hsin Tsai; Chung-Hung Tsai; Chung-Chuan Tsai; Chi-Chiang Yang (Medical Microbiology and Immunology, 2005)

Factors affecting macroalgal distribution in a eutrophic tropical lagoon in Taiwan - Hsing-Juh Lin; Jia-Jang Hung (Marine Biology, 2004)

A G-Quadruplex Ligand 3,3′-Diethyloxadicarbocyanine Iodide Induces Mitochondrion-Mediated Apoptosis But Not Decrease of Telomerase Activity in Nasopharyngeal Carcinoma NPC-TW01 Cells - Chung-Pin Li; Jen-Hsin Huang; Ai-Chi Chang; Yi-Mei Hung; Chao-Hsiung Lin; Yee Chao; Shou-Dong Lee; Jacqueline Whang-Peng; Tze-Sing Huang (Pharmaceutical Research, 2004)

Surfactant proteinA and B genetic variants predispose to idiopathic pulmonary fibrosis - Moises Selman; Hung-Mo Lin; Martha Montao; Audrey L. Jenkins; Andrea Estrada; Zhenwu Lin; Guirong Wang; Susan L. DiAngelo; Xiaoxuan Guo; Todd M. Umstead; C. Max Lang; Annie Pardo; et al. (Human Genetics, 2003)

Lipid peroxidation and cell death mechanisms in pulmonary epithelial cells induced by peroxynitrite and nitric oxide - Yuan-Soon Ho; Hung-Bin Liou; Jen-Kun Lin; Jiiang-Huei Jeng; Min-Hsiung Pan; Yu-Ping Lin; How-Ran Guo; Sheng-Yow Ho; Ching-Chang Lee; Ying-Jan Wang (Archives of Toxicology, 2002)

Assessment of Treatment Alternatives for Laboratory COD Wastewater: a Practical Comparison with Emphasis on Cost and Performance - Shing Tet Leong; S. Muttamara; Preecha Laortanakul; Hung-Ta Lin (Environmental Monitoring and Assessment, 2002)

Calyculin A Sensitive Protein Phosphatase Is Required for Bacillus anthracis Lethal Toxin Induced Cytotoxicity - Jyh-Hwa Kau; Ching-Gong Lin; Hsin-Hsien Huang; Hui-Ling Hsu; Kuo-Ching Chen; Yu-Ping Wu; Hung-Chi Lin (Current Microbiology, 2002)

Genetic variations in the cholesteryl ester transfer protein gene and high density lipoprotein cholesterol levels in Taiwanese Chinese - Lung-An Hsu; Yu-Lin Ko; Kuang-Hung Hsu; Yu-Hsien Ko; Ying-Shiung Lee (Human Genetics, 2002)

Early genes responsive to abscisic acid during heterophyllous induction in Marsilea quadrifolia - Ting-Chang Hsu; Hung-Chi Liu; Jang-Shiun Wang; Rung-Wu Chen; Ying-Chuan Wang; Bai-Ling Lin (Plant Molecular Biology, 2001)

Identifications, Classification, and Evolution of the Vertebrate α-Amino-3-Hydroxy-5-Methyl-4-Isoxazole Propionic Acid (AMPA) Receptor Subunit Genes - Yu-Chia Chen; Shieh-Shiuh Kung; Bo-Yuan Chen; Chi-Chang Hung; Chun-Chen Chen; Tzi-Yuan Wang; Yi-Mi Wu; Wei-Hsiang Lin; Chyng-Shyan Tzeng; Wei-Yuan Chow (Journal of Molecular Evolution, 2001)

Trophic functioning and nutrient flux in a highly productive tropical lagoon - Hsing-Juh Lin; Jia-Jang Hung; Kwang-Tsao Shao; Fancy Kuo (Oecologia, 2001)

The Heterogeneity in Risk Factors of Lung Cancer and the Difference of Histologic Distribution between Genders in Taiwan - Chien-Hung Lee; Ying-Chin Ko; Li Shu-Chuan Cheng; Ying-Chao Lin; Hsiang-Ju Lin; Ming-Shyan Huang; Jhi-Juh Huang; Eing-Long Kao; Hwei-Zu Wang (Cancer Causes & Control, 2001)

Pharmacokinetic Features and Metabolism of Calphostin C, A Naturally Occurring Perylenequinone with Antileukemic Activity - Chun-Lin Chen; Hung-Liang Tai; De-Min Zhu; Fatih M. Uckun (Pharmaceutical Research, 1999)